Intrafollicular hormonal environment of equine follicles aspirated for In Vitro Embryo production - K. Malin; A. de la Fuente; S. Meyers; K. Takahashi; S. Martin-Pelaez; C. Renaudin; G. Dujovne; B. Heil; T. de Castro; A.J. Conley; P. Dini (Journal of Equine Veterinary Science, 2026)

Short-term air exposure triggers redox metabolic shifts in the reef-building coral Pavona cactus - Luiza de Castro Mastrangelo Dias; Marina Minari; Carol Cristina Vágula de Almeida Silva; Beatriz Rodrigues Guarinão; Luís Felipe Barcena Albertoni; Lucas do Nascimento Lima; Daniel C. Moreira; Marcelo Hermes-Lima; Helen Sadauskas-Henrique (Journal of Experimental Marine Biology and Ecology, 2026)

In situ insights into spatial and temporal expressions of mesenchymal stem cell markers during human skeletal development - Juan Sebastián Arbeláez-Teuzaba; Derna Luz Castro; Jorge Andrés Franco-Zuluaga; Katherin Niño-Traslaviña; Johana María Guevara-Morales; Carlos Javier Almaciga-Díaz; Mercedes Olaya-C; María Lucía Gutiérrez-Gómez (Tissue and Cell, 2026)

Development and implementation of an automatic lahar monitoring system at Misti volcano, Arequipa, Peru - Juan C. Espinoza; Armando Castro; Marco Rivera; Erik Vargas (Journal of South American Earth Sciences, 2026)

Natural deep eutectic solvents (NADES): dual functionality in the extraction and stabilization of polyphenols, terpenoids and nitrogen compounds - Gerardo Valles-Salas; Juliana Morales-Castro; Claudia I. Gamboa-Gómez; Blanca E. Morales-Contreras; Walfred Rosas-Flores; L. Araceli Ochoa-Martínez; Juan C. Contreras-Esquivel; Ana M. Ávila-Galván; Orlando A. Manzanares-Meza (Food Chemistry, 2026)

Chemical composition of fine particulate matter and all-cause mortality of older lung cancer patients - Yaguang Wei; Jiaowei Gong; Edgar Castro; Min Zhang; Robert O. Wright; Christine C. Ekenga; Joel D. Schwartz (Environmental Research, 2026)

Integrating cytotoxicity and NMR-based metabolomics to uncover bioactive aporphine alkaloids and pentacyclic triterpenoids from Siparuna guianensis - Salva Asghar; Cibele A. Cesila; Gracimerio J. Guarneire; Samira C. C. Ludgero; Sandra B. R. Castro; Alessandra P. Carli; Caio César S. Alves; Danielle F. Dias; Marisi G. Soares; Nerilson M. Lima (Natural Product Research, 2026)

121 Extended incubation induces equine sperm hyperactivation and tyrosine phosphorylation as potential predictors of vitro fertilization success - R.A. Gonzalez-Castro; C. Porflidt; A.L. Ash; C. Elliot; E.M. Carnevale (Journal of Equine Veterinary Science, 2026)

Divergent PXR Function in Seals: Endocrine Adaptation or Functional Loss? - Inês Amorim; Diogo Oliveira; L. Filipe C. Castro; Raquel Ruivo; Mónica Marques (Environmental Toxicology and Pharmacology, 2026)

When taxonomy lags behind evolution: Conservation implications of cryptic diversity in the Iberian rabbit - Rafael Villafuerte; Paulo C. Alves; Miguel Carneiro; Francisca Castro; Pedro J. Esteves; Julia E. Fa; Nuno Ferrand; Vicente Piorno; João Queiros; Carlos Rouco; Patricia H. Vaquerizas; Miguel Delibes-Mateos (Biological Conservation, 2026)

Photocatalytic caffeine degradation and toxicity reduction using reduced graphene oxide-modified zinc telluride - A. J. Vilvert; P. D. Macruz; R. P. Nippes; H. C. L. Geraldino; L. V. de Castro-Hoshino; I. R. Bautitz; J. C. G. Moraes (International Journal of Environmental Science and Technology, 2026)
The occurrence of emerging pollutants in aquatic matrices has raised environmental concern because of their persistence and potential toxicity. This study assessed caffeine degradation and toxicity reduction using zinc telluride functionalized with reduced graphene oxide as heterogeneous photocatalyst. The catalysts were synthesized by the wet impregnation method with excess solvent, and characterized by physicochemical and optical techniques. The results indicated zinc telluride nanoparticles distributed on the surface of reduced graphene oxide sheets, together with changes in textural and optical properties, including a lower band gap for the composites. Photocatalytic tests were performed using a mercury vapor lamp emitting ultraviolet–visible radiation, with the main emission at 365 nm. The effects of reduced graphene oxide content, catalyst loading, initial caffeine concentration, and pH variation were evaluated. Under the tested experimental conditions, the composite containing 1.0% reduced graphene oxide showed the highest degradation performance, reaching 93% caffeine degradation in 85 min. The degradation profile was best described by the half-order kinetic model. The reduced photoluminescence intensity suggests lower electron–hole recombination, although direct confirmation of reactive species requires complementary analyses. Toxicity tests indicated lower Artemia salina mortality and improved Lactuca sativa germination after treatment with the 1.0% reduced graphene oxide-modified zinc telluride catalyst. The results indicate that reduced graphene oxide incorporation can improve caffeine photodegradation and reduce toxicity under the evaluated conditions.

Evaluation of water quality from tubular wells in Brazil - G. G. O. de Souza; J. W. G. Castro; R. S. da Cadorso; E. M. de Lima; J. F. L. de Pereira; M. P. da Silva; Y. T. C. da Santos; F. G. Rodriguês; J. G. M. da Costa; H. D. M. Coutinho; G. B. Brito (International Journal of Energy and Water Resources, 2026)

Legacy Pb–Zn mine tailings as persistent sources of bioaccessible potentially toxic elements in urban dust: geochemical signatures, exposure pathways, and human health risks - Edvaldo Renner da Costa Cardoso; Rugana Imbaná; Ésio de Castro Paes; Isabela C. F. Vasques; Oldair Vinhas Costa; Thomas Vincent Gloaguen; Emanuelle Mercês Barros Soares (Environmental Monitoring and Assessment, 2026)
Abandoned mine tailings, rich in potentially toxic elements (PTEs), can be redistributed in urban areas through atmospheric resuspension. This process serves as a dynamic geochemical compartment linking legacy contamination to human exposure. This study investigated the occurrence, oral bioaccessibility, ecological significance, and human health risks of PTEs in urban dust from Boquira, a former Pb–Zn mining district in northeastern Brazil. Eighteen urban dust samples and reference soils from uncontaminated areas were collected and analyzed for pseudo-total concentrations of Pb, Zn, Cd, Cu, Mn, Fe, and Al. Analyses were conducted using microwave-assisted acid digestion and X-ray fluorescence spectrometry (XRF). Geochemical indices, including the geoaccumulation index (I geo ), contamination factor (CF), enrichment factor (EF), and ecological risk index (Er), were used to evaluate anthropogenic enrichment and its ecological implications. Oral bioaccessibility was assessed using a simplified dilute nitric acid extraction method that simulates gastric conditions. Elevated enrichment and contamination indices revealed substantial anthropogenic inputs, particularly for Pb and Zn, indicating the long-term environmental persistence of mining-derived particulates. Pb had the highest mean oral bioaccessibility (~ 75%), followed by Cu (54.8%), Mn (28.1%), and Zn (27.0%), indicating the predominance of highly reactive and physiologically available metal-bearing phases. Human health risk assessment identified oral ingestion as the dominant exposure pathway, compared to dermal exposure, with children presenting substantially higher risks than adults. Non-carcinogenic risk thresholds (HI > 1) were exceeded for children, primarily due to Pb exposure, whereas carcinogenic risk associated with Cd ingestion exceeded acceptable limits for both population groups. The results demonstrate that legacy mine tailings in Boquira remain environmentally active decades after mine closure, sustaining chronic atmospheric redistribution of bioaccessible PTEs into urban areas.

Simultaneous effusive and explosive activity in moderate-magnitude rhyolite eruptions: H2O and hydrogen isotopic investigation of the 1250 CE eruptions in Lipari, Sicily - Sebastian C. Walter; Jonathan M. Castro; Ilya N. Bindeman (Bulletin of Volcanology, 2026)
Three of the most recent rhyolite eruptions in Europe occurred approximately 800 years ago on the island of Lipari, Aeolian Islands, Sicily. These eruptions produced ash and lava deposits that share many of the physical and chemical traits known to exist in hybrid explosive-effusive silicic systems like the Mono Craters and Medicine Lake (USA), in addition to the recently active rhyolite volcanoes Chaitén (2008) and Cordón Caulle (2011), Chile. Here, we present a study on the microtextures, H 2 O concentrations, and δD values of pyroclastic and effusive deposits of three rhyolite eruptions on Lipari (Lami, Forgia Vecchia, and Rocche Rosse). Textural features of obsidian pyroclasts are, within our parameters of analysis, identical among the three centers. The three vents furthermore display overlapping bulk H 2 O concentrations (0.08–1.22 wt.%) that are in turn similar to previous studies on Lipari and other systems. Hydrogen isotope ratios (δD) decrease from −50.9 to −104.9 ‰ as magmatic water drops from 1.22 to 0.08 wt.%. Modeling of these geochemical trends implies that all erupted products degassed along a single coherent trend. This is consistent with a manner of eruption that would have involved simultaneous and repetitive explosive and effusive emission of isotopically heterogeneous gas from a single magma source. Collectively, our observations and analysis point to hybrid effusive-pyroclastic activity and support previous interpretations that Lipari’s three youngest rhyolitic centers were co-eruptive. This, in turn, implies that more than half of the island would have been affected by direct impacts of a single rhyolitic fissure event at ~ 1250 C E.

More diverse and structurally complex forests are less tightly coupled to ENSO forcing - Pablo Salazar-Zarzosa; Salvador Arenas-Castro; Cristina C. Bastias; David Urquiza Muñoz; Aurelio Diaz Herraiz; Jorge Duran; Yuliana Mendoza; Anke Jentsch; Peter Wolff; Antonio Velasco; Gaston Cruz; Jose Luis Quero (Remote Sensing Applications: Society and Environment, 2026)

Trophic ecology of two discarded elasmobranchs (Scyliorhinus canicula and Torpedo marmorata) in a NE Atlantic trawl fishery (Gulf of Cádiz) - C. Fernández-Oliveras; C. Rodríguez-García; J. Sarmiento-Carbajal; R. Cabrera-Castro (Marine Environmental Research, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Dynamic remodeling in lipophilic metabolites during Coffea canephora maturation: A lipidomic study - Marcos V.V. Lyrio; João V.M. de Almeida; Eric C. Gier; Samuel G. Moore; Henzo P. Salvador; Fábio L. Partelli; Facundo M. Fernández; Wanderson Romão; Eustáquio V.R. de Castro (Food Chemistry, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Effect of sodium bicarbonate on performance and markers of kidney and gastrointestinal injury during repeated sprints in the heat - Jonathan W. Specht; Marissa Ramirez; Jennifer Raef; Mackenzie Schwartz; Alyssa R. Bailly; Oscar Chavez; Ozan Kumbasar; Jade X. Dawson; Jessica Apodaca; Raul Freire; Whitley C. Atkins; Flávio de Castro Magalhães; et al. (European Journal of Applied Physiology, 2026)
Purpose We tested the hypotheses that sodium bicarbonate (SB) supplementation improves performance, reduces markers of acute kidney injury (AKI) risk, and increases markers of acute gastrointestinal injury (AGI) during repeated sprints in the heat. Methods Using a double-blind design, 10 recreationally endurance-trained participants ingested 0.2 g/kg of body weight of SB or placebo before cycling in the heat (dry-bulb: 40 °C, relative humidity: 20%). Exercise bouts included a 22-min warm-up, then 4-sets of 5 × 6-sec maximal-effort standing cycling sprints. Core temperature (Tc) was measured at baseline, end of warm-up, after set two of sprints, and post-exercise bouts. Urine and plasma collected pre-ingestion and pre-, post-, and 1-h post-exercise were analyzed for markers of AKI risk, AGI, and endotoxemia. Results SB increased peak (average difference between conditions: 21 ± 11 W, condition effect: p = 0.02) and average ( p = 0.03) power across the sprints. Tc increased from pre- to post-exercise (placebo: Δ1.3 ± 0.3 °C, SB: Δ1.4 ± 0.4 °C, time effect: p < 0.001), but there were no effects of condition or interaction. Exercise increased the primary marker of AKI (urinary IGFBP7×TIMP-2, time effect: p = 0.005) but not urinary NGAL. There were no condition or interaction effects for either AKI marker. Plasma I-FABP, a marker of AGI, increased post-exercise bouts (placebo: Δ291 ± 550 pg/mL, SB: Δ397 ± 482 pg/mL, p = 0.03), with no condition or interaction effects. There were no significant effects for markers of endotoxemia (LBP, sCD14). Conclusions SB supplementation improves repeat sprint performance in the heat without altering Tc, markers of AKI risk, or markers of AGI.

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Phylogenomic insights into species boundaries and population structure in South American silversides (Odontesthes, Atherinopsidae) - Yanina F. Briñoccoli; Mariano González-Castro; Eva C. Rueda; Gustavo M. Somoza; Guillermo Ortí; Yamila P. Cardoso (Hydrobiologia, 2026)

Hafnium and silicon isotope evidence for multiple unsilicified basaltic sources at the origin of Rhyacian TTG magmas in the Mineiro Belt (Brazil) - Syro Lacerda; Martin Guitreau; Leonardo Gonçalves; Hugo Moreira; Cristiane C. Gonçalves; Stéphany Rodrigues Lopes; Sandro Mauri; Marco Aurélio Pinheiro; Cassiano Costa e Castro; Régis Doucelance (Geochimica et Cosmochimica Acta, 2026)

Optimization of wastewater treatment plant considering the uncertainty of treatment process effectiveness - Jannsen Arnier P. Friala; Ashlee Julienne I. Sigua; Francis Dominic S. Escalona; Adriane Paul C. Castro; Jeremy Gabriel Uy; Jayne Lois San Juan (Environmental Modelling & Software, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Petasma as a Reliable External Indicator of Male Sexual Maturity in Penaeus schmitti : Integrating Morphological, Biometric and Histological Analyses - H. Castro‐Neto; C. Craveiro; M. G. do Rêgo; P. G. V. Oliveira; R. Soares; S. Peixoto (Fisheries Management and Ecology, 2026)
Understanding male sexual maturity in penaeid shrimp is crucial for stock assessment and size‐based management; however, maturity criteria remain heavily biased toward females and rarely validated for males. This study evaluated whether petasma fusion is a reliable external indicator of male sexual maturity in white shrimp Penaeus schmitti from Northeast Brazil and estimated size at first maturation using an integrative morphometric, histological, and statistical approach. Forty‐five males were classified according to petasma condition, morphometrically measured, histologically examined along the reproductive tract, and analyzed using individual‐level binomial logistic regression. The estimated cephalothorax length at first maturation was CL 50 = 2.24 cm (95% CI: 2.06–2.43), with a strong model performance (Nagelkerke R 2 = 0.80). Histological analysis revealed complete categorical agreement between external morphology and internal reproductive status: all males with unfused petasma lacked mature spermatozoa and exhibited only early germ cells, whereas all males with fused petasma presented the complete spermatogenic series and fully differentiated spermatozoa in the terminal ampulla. The relationship between petasma length and body size showed negative allometry, indicating a proportionally smaller investment in petasma growth relative to somatic growth. ANCOVA detected a significant maturity effect on the intercept, but not on the slope, demonstrating a discrete proportional change in petasma dimensions at maturation, rather than a change in growth trajectory. These findings demonstrate that petasma fusion is a robust and nondestructive indicator of physiological maturity in male P. schmitti . The results of the analysis combining petasma, histology, and length at first maturity indicated that petasma is a reliable indicator for validating physiological maturity and that male reproductive indicators should be formally incorporated into penaeid fishery management structures.

A novel hunting‐by‐riding association of reef fishes mediated by habitat complexity - Guilherme M. Castro; Ivan M. Carneiro; Fernando C. Cardoso; Rodrigo L. Moura (Ecology, 2026)

Non‐Stationary Dry‐Spell Hazard Probabilities for Spain - S. M. Vicente‐Serrano; S. Beguería; A. Royo; A. El Kenawy; M. Franquesa; A. Halifa‐Marin; M. Adell‐Michavila; A. Crespillo; D. Pérez‐Pajuelo; F. Domínguez‐Castro; C. Azorin‐Molina; L. Gimeno; et al. (International Journal of Climatology, 2026)
This study provides a comprehensive assessment of long‐term changes in dry‐spell dynamics across Spain for the period 1961–2024, using both classical non‐parametric methods and a novel non‐stationary probabilistic framework applied to exceedance series of dry‐spell durations. Using daily precipitation data from a dense network of quality‐controlled stations, dry‐spells were identified based on four thresholds (0.1, 1, 5, and 10 mm) to characterize their duration statistics, and generalized Pareto distributions (GPDs) were fitted under both stationary and non‐stationary specifications. A systematic percentile‐based evaluation was performed to determine optimal exceedance thresholds, and a bootstrap‐based significance test was applied to compare stationary and non‐stationary return levels. Complementary analyses examined trends in annual frequency, mean duration, and maximum dry‐spell length. Results consistently reveal that dry‐spell behaviour across Spain is dominantly stationary. Only a very small fraction of stations show significant non‐stationary effects in the GPD location parameter, whereas non‐stationary scale, shape, or full‐parameter models provide no robust improvement and introduce substantial uncertainty. Traditional trend analyses corroborate this finding: most stations (> 70%–85%, depending on threshold) exhibit no statistically significant changes in dry‐spell frequency, mean duration, or maximum duration. Spatial patterns of change are weak, and return levels associated with long recurrence periods (e.g., 50 years) remain highly stable throughout 1961–2024. Overall, these results support long‐term stationarity in the probability of extreme dry‐spells across Spain.

Bacterial Diversity in Leaf-Cutter Ant Species: Host-Microbe Interactions and Environmental Effects - Alexandra Gianaris; Manuela O. Ramalho; Amanda A. de Oliveira; Maria Santina de Castro Morini; Cintia Martins; Odair C. Bueno (Neotropical Entomology, 2026)
Historically, studies have sought to identify host-specific factors in host-microbe interactions as a means of understanding evolutionary success. The genus Atta , comprising leaf-cutter ants, is native to the southern Neotropics and obligately mutualistic with cultivated fungi. It hosts a remarkably diverse range of bacterial communities, yet this variability remains poorly understood. Using high-throughput amplicon sequencing of the 16S rRNA genes of the whole worker, we showed significant difference between the bacterial communities among 4 dominant Atta species: Atta sexdens (Linnaeus), Atta laevigata (Smith), Atta capiguara (Gonçalves), and Atta bisphaerica (Forel). We also discovered significant differences in bacterial communities from laboratory conditions, pesticide treatment, and the fungal garden symbiont of Atta sexdens . Surprisingly, bacterial communities of Atta sexdens kept in the laboratory were not significantly different from pesticide-treated Atta sexdens , laying the groundwork for potential refinement of standard research methods.

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

Bioluminescent diversity and ecotourism potential in the Juréia-Itatins Ecological Station, integrating conservation and sustainable development - Danilo T. Amaral; Rodrigo O. Castro; João Roberto Fentanes-Machado; Lara C. Muniz; Isabel A.S. Bonatelli (Journal for Nature Conservation, 2026)

Effect of graphene quantum dot size on the capacitance of rGO-based supercapacitors fabricated with a sustainable electrolyte (seawater) - R.A. Mendoza-Jiménez; J. Oliva; T.A. Esquivel-Castro; C. Rodriguez-Gonzalez; P. Salas (Chemical Engineering Journal, 2026)

Green synthesis of biogenic silver nanoparticles from Agave potatorum leaves and their potent antifungal activity against Neocosmospora sp. and Fusarium nirenbergiae - Aida-Rubí Cruz-Luna; Miguel C. Gutiérrez; Muzaffer A. Karaaslan; Delia Soto-Castro; Alfonso Vásquez-López (Biocatalysis and Agricultural Biotechnology, 2026)

Fucoidans from the brown seaweeds Undaria pinnatifida and Fucus vesiculosus as inhibitors of coagulant and phospholipase A2 activities of pit viper Lachesis muta venom and purified enzymes - Camila Castro-Pinheiro; Eladio F. Sanchez; Corinna A. Dwan; Barbara C. Wimmer; Alan T. Critchley; André L. Fuly (Journal of Applied Phycology, 2026)
Snakebite envenomation is a neglected tropical disease and incidents of the pit viper Lachesis muta cause hemorrhage, muscle damage, blood coagulation disturbances, and even death; the proteases and phospholipase A 2 (PLA 2 ) of snake venoms contribute to such toxic effects. This work evaluated the inhibitory effect of commercial fucoidans from two species of brown seaweeds Fucus vesiculosus (FVF) and Undaria pinnatifida (UPF) against the coagulant and PLA 2 activity of Lachesis muta venom and two purified enzymes, a thrombin-like enzyme and PLA 2 , denoted TLE–1 and LM-PLA 2 –I, respectively. Fucus vesiculosus and U. pinnatifida fucoidans were incubated with L. muta venom and enzymes for 5 min at 37 °C, followed by assays, including the plasma and fibrinogen coagulation, hydrolysis of the substrates of proteases (S–2238 and S–2288), and hydrolysis of the substrate of PLA 2 enzymes, NBD-PC. Fucus vesiculosus and U. pinnatifida fucoidans inhibited the plasma coagulation of L. muta venom, but not the coagulation of TLE–1. However, both fucoidans fully prevented the coagulation of fibrinogen caused by L. muta venom and TLE–1. Fucus vesiculosus and U. pinnatifida fucoidans inhibited 60% and 40% hydrolysis of S–2238 of L. muta venom and TLE–1, respectively. Using the substrate S–2288, the fucoidans did not affect the hydrolysis of L. muta venom and inhibited 40% of hydrolysis caused by TLE–1. Fucus vesiculosus and U. pinnatifida fucoidans inhibited 40% and 20% of the PLA 2 activity of L. muta venom and LM-PLA 2 –I, respectively. These two fucoidans should be investigated as complementary or potential adjuvants for SBE inflicted by L. muta venom in more detail.

Detection of Viruses of Public Health Importance in Wastewater Samples Using Conventional PCR Techniques and a Targeted Enrichment Whole Genome Sequencing Panel - Gonzalo M. Castro; Florencia Mallou; Gisella Masachessi; María C. Frutos; Verónica E. Prez; Tomás Poklepovich; Silvia V. Nates; María B. Pisano; Viviana E. Ré (Food and Environmental Virology, 2026)

Encapsulated Amazonian Microalgae Reduce Ammonia and Improve Survival of Female Poecilia reticulata During Simulated Transport - Marianela Cobos; Marcos J. Guerra; Leonardo J. Pizarro; Gladys R. Panduro; Danitza E. Ampudia; Freddy O. Espinoza-Campos; Carlos G. Castro; Juan C. Castro (Fishes, 2026)
The accumulation of un-ionized ammonia (NH3) during the transport of live ornamental fish poses a critical threat to animal welfare and post-transport survival. This study evaluated the efficacy of calcium alginate-encapsulated native Amazonian microalgae, Ankistrodesmus sp., Chlorella sp., Scenedesmus sp., and Synechococcus sp., for NH3 bioremediation during a 15-day simulated transport of female Poecilia reticulata. Biometric endpoints were selected using a four-criterion framework, identifying specific growth rate by weight (SGRW), specific growth rate by length (SGRL), and Fulton’s condition factor (K) as essential non-redundant parameters. Time-weighted average (TWA) NH3 served as the primary dose variable for four-parameter log-logistic modeling fitted to biological replicate means (n = 15). Ankistrodesmus sp. and Scenedesmus sp. maintained 97.8% survival and restricted TWA NH3 to 0.036 and 0.047 mg/L, respectively, whereas the empty capsule control reached 6.7% survival and 0.150 mg/L TWA NH3. Kruskal–Wallis tests on biological replicate means confirmed significant treatment effects on all biometric endpoints (SGRW: H(4) = 13.50, ε2 = 0.950; SGRL: H(4) = 13.50, ε2 = 0.95; p

Lab-on-a-chip-compatible graphene oxide coatings via SAW atomization for supporting cell proliferation - Olga V. Balachova; Andrea C. Dorion Rodas; Sergey M. Balashov; Daniel D. da Purificação; Luciana D. Trino Albano; Caio C. de Lima Silva; Gabriel C. Kokkonias e Castro; Juliana K. M. Barboza Daguano (In vitro models, 2026)

Sex‐Specific Atlantic Salmon Upstream Passage and Fallback at a Natural Cascade After Dam Removal - Kurt C. Heim; Jonah L. Withers; William R. Ardren; Laurie A. Earley; David Minkoff; Theodore Castro‐Santos (Fisheries Management and Ecology, 2026)
In the Boquet River (NY, USA) a low‐head dam set above a ~200‐m bedrock cascade was removed in 2015. We used radio‐telemetry to assess landlocked Atlantic salmon passage at the remaining cascade (2020, 2022). Across years, 52% of males (13/25) attempted cascade passage whereas females made no discernable attempts (0/11). Attempt probability increased with stream discharge and decreased with fish size, though overall passage success was low (1/36). Shallow depths—likely owing to an artificially widened channel—appear to be limiting passage. Additionally, we transported fish upstream but observed high fallback (72%) that was associated with fish size and energetic status. Following dam removal, this cascade continues to limit upstream passage resulting in increased vulnerability to angling during migratory delay. Overall, we highlight the importance of follow‐up studies after dam removal, and that further modifications at this site may be required to improve passage.

The haunting challenge of the trends and pathway assessments on newly introduced non-indigenous species in European seas - Okko Outinen; Peter A.U. Stæhr; Romeu S. Ribeiro; Aina Carbonell; Robert Comas-González; Lydia Png-Gonzalez; Maite Vázquez-Luis; Ann-Britt Florin; Rahmat Naddafi; Arjan Gittenberger; Hans Jakobsen; Ana C. Costa; et al. (Marine Pollution Bulletin, 2026)

Toxicological profiling of nutraceutical-grade curcumin-loaded solid lipid nanoparticles using Caco-2 cells and zebrafish (Danio rerio) embryo models - Raquel F.S. Gonçalves; Joana Ribeiro; Joana T. Martins; Marisa Sárria Pereira de Passos; Andreia Castro Gomes; António A. Vicente; Ana C. Pinheiro (Toxicology in Vitro, 2026)

Towards the design of a selective trap for an invasive snake - Marta López-Darias; Jorge Fernando Saavedra Bolaños; José Miguel Sánchez Rivero; Andrea Castro Martín; Julien C. Piquet; Borja Maestresalas; Ramón Gallo-Barneto (Journal of Environmental Management, 2026)

New findings of pseudotachylytes and their paleoseismic significance, Sierras Pampeanas of San Juan, Argentina - Gladis N. Palacio Balderramo; Brígida Castro de Machuca; Ana C. Mugas Lobos; Gustavo F. Ortíz; Gimena M. Bazán; Cristian E. Robledo (Journal of South American Earth Sciences, 2026)

Wildfire causes in mainland Portugal: Municipal-scale hotspots and non-stationary spatial drivers - A.N. Nunes; L. Lourenço; Meira Castro A. C. (Journal of Environmental Management, 2026)

The dynamics of coastal macroalgal assemblages after the Fundão dam disaster: challenges and lessons from impact assessment - Ivan M. Carneiro; Guilherme M. Castro; Fernando C. Cardoso; Julia P. Curvêllo; Rodrigo T. Carvalho; Leonardo T. Salgado; Julia Kaiser; Paulo S. Salomon; Rodrigo L. Moura (Environmental Monitoring and Assessment, 2026)
Anthropogenic marine disasters impair biodiversity, ecosystem services provisioning, and socioeconomic development, with long-lasting consequences. Robust impact assessment, however, depends on understanding the spatiotemporal variability of the indicators used to detect change. Here, we present the results of a monitoring program (2018–2025) targeted at two Coastal and Marine Protected Areas located 40 km south of the Doce River mouth (Eastern Brazil), which were affected by the discharge of iron ore tailings from the Fundão dam collapse in 2015. Besides assessing the dynamics of the benthic assemblages, we revealed a high variability among sampling units (residual), along with relevant variability across seasons, sites, and their interactions. Wave height and distance from rivers were the most influential drivers explaining assemblage variability. Before–after contrasts based on pre-disaster data from the literature indicate shifts in the assemblage structure. However, because baseline data are limited, the observed changes cannot be conclusively attributed to the disaster. An overview of marine areas under long-term ecological monitoring in Brazil revealed a concerning mismatch with the distribution of mining, oil and gas, port, and nuclear activities. Rethinking funding for baseline data collection and monitoring of disaster-prone marine areas, primarily from industries that are often responsible for marine disasters, constitutes a necessary step toward effective solutions.

Translational medicine protocol for proteomics clinical research on snakebite envenoming: contributions for develop studies in mechanisms and new biomarkers - Joeliton S. Cavalcante; Juliana Sartorelo Almeida; João Victor C. Coutinho; Edgar E. Neri Castro; Manuela B. Pucca; Alejandro Alagón; Rui Seabra Ferreira Junior (Archives of Toxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Dendropsophin 1, an antimicrobial peptide from skin secretion of the tree frog Dendropsophus columbianus, exhibits tissue repair potential - Isabella S. Cassimiro; Bruno A. Ferreira; Simone R. Deconte; Taís C. Lima; Francyelle B.R. Moura; Mariana S. Castro; Fernanda A. Araújo (Toxicon, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Nutritional consumption of phenolic compounds-rich clarified açaí juice (Euterpe oleracea) elicits anxiolytic and antidepressant effects during adolescence in rats - Taiana C. Vilhena Carvalheiro-Simas; Marta Eduarda Oliveira Barbosa; Lucas Villar Pedrosa da Silva Pantoja; Luiza Fernanda Ramos Soares; Lucas Benedito Gonçalves Quadros; Luiz Menezes Matos Netto; Carlos Augusto Ribeiro Barros; Luís Eduardo de Oliveira Teixeira; Pedro Iuri Castro da Silva; Jofre Jacob da Silva Freitas; Geanne Matos de Andrade; Cristiane S.F. Maia; et al. (Food Research International, 2026)

Ecotrends: an R package for estimating habitat suitability trends over time - Neftalí Sillero; João Alírio; Nuno Garcia; Inês Freitas; João C. Campos; Lia Bárbara Duarte; Isabel Pôças; Ana Cláudia Teodoro; Salvador Arenas-Castro; A.Márcia Barbosa (Ecological Modelling, 2026)

A spatial regression analysis of the association between PM2.5 and early childhood development outcomes in South Africa using the 2021 Thrive by Five Index - Junita Henry; Yazan Alwadi; Marcia C. Castro (Atmospheric Environment, 2026)

Influence of almond’s canopy-induced shadows on actual evapotranspiration estimation by the TSEB model using sUAS multispectral and thermal imagery - M. R. Duran-Gomez; A. Torres-Rua; L. Hipps; W. Kustas; N. E. Bambach; K. Knipper; I. Wright; A. J. McElrone; J. H. Prueger; J. G. Alfieri; C. Coopmans; K. Meza; et al. (Irrigation Science, 2026)
Over the past decade, the estimation of water requirements in almond orchards has improved through the application of remote sensing models like the Two-Source Energy Balance (TSEB) model using various remote sensing platforms. However, there is limited understanding of how canopy-induced shadows influence surface reflectance and thermal infrared (TIR) signals particularly from small Unmanned Aircraft System (sUAS) imagery in energy balance models, and the effect on Latent Heat Flux (LE) estimations. This study evaluates LE estimates from the Priestley-Taylor TSEB model (TSEB-PT) with and without shadow filtering using sUAS-based multispectral and TIR imagery. It establishes a baseline for the impact of shadow filtering on model inputs and performance. Datasets were collected in 2021 and 2022, as part of the USDA led Tree-crop Remote sensing of Evapotranspiration eXperiment (T-REX) in almonds orchards across California. LAI-2200 C Plant Canopy Analyzer measurements facilitated the calibration of an empirical Leaf Area Index (LAI) model based on canopy fractional cover (FC) and NDVI (R 2 = 0.68). Shadow filtering caused land surface temperature (LST) differences up to 5 °C in young to semi-mature orchards (FC 0.40–0.80). In contrast, mature orchards (FC > 0.80) showed minimal influence due to the limited shadow occurrence on the imagery. Shadows appeared to reduce surface albedo (α alb ), mainly in interrow areas, thereby affecting the absorption of radiation and the partitioning of energy balance components. Their presence in sUAS imagery also hindered canopy delineation, impacting the accuracy of key TSEB inputs derived from canopy physical characteristics. Thus, the influence of shadow on TSEB estimated LE was more significant in lower fractional tree covers. While LE estimated by TSEB-PT without shadow filtering showed better agreement with observations, combining instantaneous TIR imagery with solar-noon shortwave data is recommended for accurate ETa assessment using sUAS datasets. These baseline results can be improved with more advanced formulations, supporting continued research on E/T partitioning and water stress in almond orchards under varying environmental conditions, particularly when there is advection of hot dry air.

Time-Series Niche Modelling Reveals Declining Tendencies of Habitat Suitability and Ecological Functions in a Mountainous Protected Area - Inês Freitas; João Alírio; Nuno Garcia; João C. Campos; Salvador Arenas-Castro; Isabel Pôças; Lia Duarte; Ana C. Teodoro; Neftalí Sillero (Environmental Management, 2026)
Monitoring biodiversity in protected areas is essential to mitigate biodiversity loss and evaluate the effectiveness of conservation policies. Integrating satellite remote sensing technologies, ecological niche models, and time-series analyses of biodiversity trends offers a fast and robust approach for assessing habitat suitability changes and species vulnerability over time. In this study, we implemented a framework combining these tools to monitor biodiversity in the Montesinho/Nogueira Special Conservation Area (Northeast Portugal). Using the MaxEnt algorithm, we generated ecological niche models for 342 species based on a time series (2001–2023) of remote sensing data from the Moderate-Resolution Imaging Spectroradiometer (MODIS) sensor. We analysed habitat suitability trends with the Mann-Kendall test to detect changes in habitat quality, as a metric of species vulnerability for individual species, five major taxonomic groups (vascular flora, amphibians, reptiles, birds, and mammals), functional groups (e.g. climate affinity, habitat type, diet, activity, reproduction), and conservation status (regional and European levels). Our study revealed a significant decline in habitat suitability over the past two decades, impacting all taxonomic groups and ecological functions. We observed a high variability in habitat suitability trends among species and taxonomic/functional groups, highlighting the complexity of biodiversity responses to environmental changes. Functional traits such as climatic affinity, trophic level or habitat specialisation were associated with variable rates of habitat decline, with species of Atlantic affinity, species associated with croplands and wetlands, and species specialised in insectivorous diets being at higher risk. Overall, these findings emphasise the need for comprehensive biodiversity monitoring programmes and demonstrate the utility of our approach to inform evidence-based conservation strategies in protected areas globally.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Extracellular vesicle microRNAs as an epigenetic biosignature of arsenic-associated diabetes in the Strong Heart Study - Christian K. Dye; Allison Kupsco; Gabriela L. Jackson; Ronald A. Glabonjat; Abbas Hakim; Anelizze Castro-Martinez; Louise C. Laurent; Jason G. Umans; Walter Goessler; Shelley A. Cole; Andrea A. Baccarelli; Ana Navas-Acien; et al. (Environmental Research, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Seasonal variations in biofiltration efficiency of fish farm effluents using Ulva spp. - Cristina Rodríguez; N. L. Arroyo; M. C. Castro; A. Hernández de Rojas; X. Moreno-Ventas (Journal of Applied Phycology, 2026)
Intensive aquaculture generates nutrient-rich effluents that contribute to eutrophication if discharged untreated. Seaweed cultivation offers a sustainable approach to mitigate this impact while producing valuable biomass. This study evaluated the seasonal biofiltration efficiency and biomass production of Ulva spp. under simulated flatfish aquaculture effluent conditions using two experimental designs: parallel tanks and serial tanks with varying hydraulic retention times (HRTs). Ulva spp. showed higher nutrient removal and growth in summer compared to winter. In the parallel system, ammonium and phosphate removal exceeded 70% in summer but dropped below 50% in winter. In the serial system, nutrient removal peaked at a 24 h HRT, with ammonium and phosphate removal above 90%, while longer retention (36 h) did not improve performance. Biomass production followed a similar seasonal pattern, with higher yields in spring and summer. These results demonstrate that Ulva spp. are effective biofilters for aquaculture effluents, with performance strongly influenced by season and HRT. A two-tank serial configuration with 24 h HRT optimizes nutrient removal without compromising biomass production, providing useful insights for the design of sustainable seaweed-based biofiltration systems.

When Good Fit Goes Bad: Identifying and Minimising Overfitting in Ecological Niche Models - Diana Sousa‐Guedes; A. Márcia Barbosa; Salvador Arenas‐Castro; João C. Campos; Neftalí Sillero (Journal of Biogeography, 2026)
Aim To synthesise current understanding of overfitting as a pervasive and often underdiagnosed problem in correlative ecological niche models (ENMs), and to assess its consequences for model interpretation, generalisation and transferability under contemporary data and methodological practices. Location Worldwide. Methods We reviewed the ENM literature, synthesising theoretical and empirical studies that address the detection and treatment of overfitting. We examined diagnostic approaches, including spatially and environmentally structured cross‐validation, and evaluated modelling practices related to sampling bias, predictor choice, study area definition, model complexity and regularisation. Results Common warning signs of overfitting include large discrepancies between training and testing performance, fragmented or ecologically implausible prediction maps and unrealistic response curves. Spatially and environmentally structured cross‐validation approaches are effective for assessing data independence and diagnosing inflated performance estimates. Although multiple mitigation strategies can reduce overfitting, the persistent lack of generalisation often reflects limitations related to data quality, spatial and environmental scale, and violated ecological assumptions rather than modelling choices alone. Main Conclusions Predictive accuracy alone is insufficient for evaluating correlative ENMs. Ecological plausibility, interpretability and consistency with known species distributions are equally important for assessing model reliability. We advocate for iterative model evaluation, explicit consideration of ecological assumptions, and transparent reporting as best practices to improve the trustworthiness and transferability of ENMs in ecological research and conservation planning.

Evaluating factors affecting the sample processing for trace analysis of organophosphate tri- and di-esters in seawater: Application in the Loire estuary (France) - P. Zapata-Corella; M. Velázquez-Gómez; C. Pollono; J. Castro-Jiménez (Marine Pollution Bulletin, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Stock identification of the striped mullet Mugil incilis (Actinopterygii: Mugilidae) using truss network, morphometric relationships, and probabilistic models in three regions of the Colombian Caribbean. - K.E. Carrillo-Castro; P. del Monte-Luna; C. Cardenas-Uribe; y.H. Castillo-Navarro (Fisheries Research, 2026)

Reproductive success over Calliandra fasciculata Benth. floral anthesis: evidence of adaptive generalization - Rodrigo Santiago; Pedro J. Bergamo; Vinícius L.G. Brito; Marsal D. Amorim; Lucas B. Castro; Sabrina A. Lopes; Cinthia S. Novaes; Larissa C. Mendes; Gizele C.A. Silva; Danila M. Silva; Ilmara A.O. Ferreira; Bernardo O. Dias; et al. (Flora, 2025)

Zeolites for use in environmentally sustainable sensors for hazardous pesticides: A review on reliability and potential perspectives in nanotechnology - Ever Estrada-Cabrera; Alejandra Castro-Carranza; Jairo C. Nolasco; Jürgen Gutowski; Cynthia Armendariz-Arnez (Environmental Nanotechnology, Monitoring & Management, 2025)

Andrographolide increases adult hippocampal neurogenesis and prolongs contextual fear memory - Laura F. Jaimes; Matheus C. Passos; Lara M. Z. Mansk; Caio M. de Castro; Julián T. F. Vega; Leonardo de O. Guarnieri; Flávio A. G. Mourão; Alexander Birbrair; Victor R. Santos; Márcio F. D. Moraes; Grace S. Pereira (Psychopharmacology, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Developing science-informed maps and climate service for extreme rainfall in Spain - S. M. Vicente-Serrano; S. Beguería; F. Reig; A. Royo; M. Arretxea; M. Gil; B. Latorre; A. El Kenawy; M. Franquesa; A. Halifa-Marin; M. Adell-Michavila; A. Crespillo; et al. (Natural Hazards, 2025)
This study introduces the first high-resolution hazard probability maps of extreme precipitation for Spain, marking a significant step toward a national climate service for hydrometeorological extremes. Using long-term daily precipitation records from a dense network of stations and incorporating topographic data, the methodology combines the Generalized Pareto distribution with universal kriging to spatially interpolate distribution parameters. These maps offer reliable estimates of extreme precipitation quantiles, validated against station-level observations, and are based on a stationary modelling framework—an approach supported by recent findings showing the temporal stability of such extremes in Spain and considered more robust than non-stationary alternatives. Distinct spatial patterns emerge, with intense daily precipitation distributed mainly along the Mediterranean coast and high total event precipitation in the northwest and southwest, reflecting the influence of varied weather systems. To support decision-making, the study aggregates these high-resolution data at the provincial level, aligning risk information with administrative boundaries, and enhancing its relevance for policy and planning. Furthermore, the maps are made accessible via an interactive online platform ( https://retornolluvias.csic.es ), enabling users to explore localized hazard probabilities, thereby supporting adaptation in water management and civil protection, among others.

Phylogenetic Relationships of the Moles and their Relatives (Talpidae): Insights from Mitogenomes - Sara Sampaio; André Gomes-dos-Santos; L. Filipe C. Castro; Jonathan J. Hughes; Ivan N. Bolotov; Viatcheslav V. Rozhnov; Marina V. Rutovskaya; Ilia G. Meschersky; Joana Paupério; Paulo C. Alves; Jeremy B. Searle; Manuel Lopes-Lima (Evolutionary Biology, 2025)

Soil fertilization potential and nutrient dynamics of organic fertilizers derived from sugarcane residues under techno-economic and environmental assessment - Thais G. Carpanez; Livia M.C. Castro; Bruna L. Moreira; Julia B.L.S. Carneiro; Eduarda V.S. Gomes; Marcelo H. Otenio; Jonathas B.G. Silva; Julio C. Balarini; Fernanda R.C. Damasceno; Miriam C.S. Amaral; Victor Rezende Moreira (Chemosphere, 2025)

Silver nanoparticles enhance plant biomass of Laelia rubescens Lindl. during in vitro culture by positive effects on root growth performance - Alberto Mayo-Mosqueda; Jericó Bello-Bello; Emanuel Hernández-Nuñez; Jesús Arreola-Enriquez; Julia C. Alcudia-Pérez; Angela F. Ku-González; Greta H. Rosas-Saito; Randy Ortíz-Castro; Fulgencio Alatorre-Cobos (South African Journal of Botany, 2025)

Interannual variability in dissolved organic matter (DOM) concentration and quality in shallow water bodies of Tierra del Fuego (Argentina) - Patricia E. Garcia; Maria V. Castro; María C. Maluendez Testoni; Patricia Rodríguez (Limnologica, 2025)

Polyphenol profile and associated antioxidant, antiproliferative and anti-inflammatory activities of Mexican Opuntia fruits - N.C. Castro-Alatorre; C. Jiménez-Martínez; J. Girón-Calle; A.G. Garzón; S.R. Drago; J. Vioque (Food Bioscience, 2025)

Antioxidant, UV-blocking, and biodegradable pectin films containing selenium nanoparticles for sustainable food packaging - Guilherme A.M. Jesus; Michael C. Castro; Paulo R. Souza; Johny P. Monteiro; Roberta M. Sabino; Shyam S. Sablani; Alessandro F. Martins; Elton G. Bonafé (Food Hydrocolloids, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Influence of Inorganic Nutrients on a North Atlantic Microbial Community’s Response to Ocean Alkalinity Enhancement - Inês de Castro; Susana C. Ribeiro; António Louvado; Newton Carlos Marcial Gomes; Mário Cachão; Paulo F. Silva Borges; Eduardo Brito de Azevedo; Joana Barcelos e Ramos (Oceans, 2025)
Ocean Alkalinity Enhancement (OAE) is a promising carbon dioxide removal strategy, but its ecological impacts on marine microbial communities under varying nutrient conditions remain poorly understood. We conducted laboratory incubations using a natural North Atlantic microbial assemblage to investigate the response to OAE under both natural and nutrient-enriched regimes. We tracked phytoplankton and bacterioplankton dynamics, biomass, and leucine aminopeptidase (LAP) and alkaline phosphatase (ALP) activity as indicators of organic matter remineralization. OAE consistently reduced phytoplankton abundance in both nutrient regimes, potentially due to CO2 limitation, resulting in lower production of phytoplankton-derived organic matter. This reduction was reflected in decreased LAP activity and shifts in the relative abundance of phytoplankton-associated bacterial taxa. These findings indicate that OAE can directly affect phytoplankton through carbonate chemistry alterations, with potential microbial responses largely mediated by changes in organic matter availability. While short-term microbial disruptions were modest, the ecological consequences of altered bloom dynamics should be carefully considered in future OAE deployment strategies.

Antibacterial marinopyrroles and pseudilins act as protonophores - Chambers C. Hughes; Gabriel Castro-Falcón; Jan Straetener; Jan Bornikoel; Daniela Reimer; Trevor N. Purdy; Anne Berscheid; Florence M. Schempp; Dennis Y. Liu; Roger G. Linington; Heike Brötz-Oesterhelt (Phytochemistry Letters, 2025)

Peroxymonosulfate activation by nitrogen-doped sludge from drinking water treatment for organic pollutants removal - Camilo C. Castro-Jiménez; Nancy Acelas; Ricardo A. Torres-Palma; Julio C. Saldarriaga-Molina; Edwin F. García (Journal of Water Process Engineering, 2025)

Consumption of yogurts containing buriti pulp and fermented milks containing orange bagasse increases the response of the endogenous antioxidant system and the expression of heat shock proteins in healthy rats - Juliana S. Graça; Bruna G. Castro; Caroline Heckler; Patrícia B. Batista; Rafael L. Camargo; Marianna M. Furtado; Luísa Freire; Mayra F. Melo; Maria Paula M.B.B. Gonçalves; Amanda M.T.M. Moya; Cínthia B.B. Cazarin; Tatiana C. Pimentel; et al. (Food Research International, 2025)

Valorization of sludge from an industrial treatment plant as a carbocatalyst for degrading pharmaceuticals in aqueous solutions - Isabella Escobar; Camilo C. Castro-Jiménez; Jazmín Porras; María Isabel Mejía; Efraím A. Serna-Galvis; Sebastián Pérez; Juan Muñoz-Saldaña; Ricardo A. Torres-Palma; Nancy Acelas (Chemical Engineering Journal, 2025)

AT1 receptors play a role in sepsis-induced vasoplegia by increasing iNOS expression in the perivascular adipose tissue - Wanessa M. C. Awata; Gustavo F. Pimenta; Thales M. H. Dourado; Kathleen A. Paulino; Marcela M. Blascke de Mello; Lucas C. Pinheiro; Michele M. Castro; Carlos R. Tirapelli (Pflügers Archiv - European Journal of Physiology, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Morphological Characterization of the Sensilla from the Antennal Flagella, Maxillary Palps, and Aculei, and Electroantennogram Responses of Anastrepha obliqua (Diptera: Tephritidae) to Host Volatiles - Ricardo Castro-Torres; Luz Neri Benítez-Herrera; Julio C. Rojas (Neotropical Entomology, 2025)

Enhanced biodegradation of petroleum in seawater using an autochthonous microbial consortium from the northeast coast of Brazil affected by the Venezuelan oil spill - José Evandro S. Pereira; João Vitor B. Borowski; Amanda P. Napp; Maiara M. Oliveira; Igor D.A. Ribeiro; Luzia Gabrielle Z. de Castro; Charley C. Staats; Augusto Schrank; Luciane M.P. Passaglia; Vânia Maria Maciel Melo; Lucymara Fassarella Agnez-Lima; Marilene H. Vainstein (Chemosphere, 2025)

Multi-tissue transcriptome of Brycon amazonicus (Spix & Agassiz, 1829): insights into lipid metabolism in an Amazonian fish - Renato Barbosa Ferraz; Elsa Froufe; L. Filipe C. Castro; Manuel Nande; Karine Vasconcelos Costa; Raimundo de Jesus Tavares Diniz Neto; Óscar Monroig; André Gomes-dos-Santos (Marine Genomics, 2025)

Telenutrition as a Solution to Dietitian Shortages in Rural Hospitals: A Pilot Implementation Study - N. Jouzi; M. Castro; C. Johnson (Journal of the Academy of Nutrition and Dietetics, 2025)

Evaluation of resistance to charcoal rot in different phenological stages of the common bean crop - Jane C. S. Santos; Jerônimo C. Borel; Antonio E. S. Costa; Amanda N. Menezes; Mateus S. Castro; Kethelen G. S. Viana; Francine H. Ishikawa (European Journal of Plant Pathology, 2025)

First report of biological contaminants in household water in the Philippines and long-term viability of Acanthamoeba species in one-year-old household water sediment - Frederick R. Masangkay; Rafaella Maxine N. Almeda; Alianna Louise M. Abustan; Sarah Veronica F. Almendrala; Jan Camille B. Bathan; Jowey Shekainah C. Belandres; Maria Allana Angela M. Buenaventura; Lea May F. Cabansag; Gemina Bienne V. Caralian; Mikhaella Denise V. Cueva; Leizette P. Cata-Al; Rance Leander H. Clemente; et al. (Science of The Total Environment, 2025)

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Size Structure of Hawksbill Turtles (Eretmochelys imbricata) from Taxidermied Specimens in Private Collections Captured Along the Western Coast of the Gulf of California - Francisco Omar López-Fuerte; Roberto Carmona; Sergio Flores-Ramírez; Melania C. López-Castro (Journal of Marine Science and Engineering, 2025)
Human exploitation has been a major driver of marine turtle population declines, particularly affecting naturally scarce species such as the pantropical hawksbill turtle. Although hawksbill sea turtles have been documented in the Gulf of California since the early 20th century, data on their historical demography during periods of high exploitation in this region are nonexistent. We investigated the size structure of hawksbill turtles from the Western Central Gulf of California by examining a unique sample of decorative taxidermies, corresponding to 31 specimens captured during fishing operations near Santa Rosalía, Baja California Sur, Mexico, between 1980 and 1990. An analysis of the curved carapace measures revealed a length range (nuchal notch to posterior of supracaudals) of 29.5–59.5 cm (mean = 38.75 ± 6.67 cm) and a width range of 25.0–51.5 cm (mean = 33.63 ± 5.66 cm), with 87% of specimens having lengths between 30 and 45 cm. Based on the carapace length measurements, we estimated the ages to be between 7 and 20 years, indicating that the population included juveniles. Our findings provide baseline data for an understudied period and region, suggesting that this area previously served as an important juvenile habitat. These results contribute essential historical demographic information for conservation planning.

Ocean liming effect on a North Atlantic microbial community: changes in composition and rates - Inês de Castro; Susana C. Ribeiro; António Louvado; Newton Carlos Marcial Gomes; Mário Cachão; Eduardo Brito de Azevedo; Joana Barcelos e Ramos (Frontiers in Marine Science, 2025)
The ongoing rise in atmospheric CO 2 levels and the consequent global warming make it increasingly difficult to maintain the global temperature within the 1.5 - 2°C target set by the Paris Agreement. Therefore, strategies to remove carbon dioxide from the atmosphere are being developed, with ocean alkalinity enhancement (OAE) gaining most attention. Within OAE, ocean liming- the addition of quicklime (CaO) or hydrated lime (Ca(OH) 2 )- can not only remove CO 2 from the atmosphere but potentially counteract the effects of ocean acidification. Although quite attractive, these technologies have yet to be tested regarding ecological safety and efficacy. Here we report the impacts of ocean liming on the abundance, composition and extracellular enzymatic activity (EEA) rates of a North Atlantic planktonic community. The results demonstrate that OAE led to a decreased phytoplankton development, mainly diatoms. The bacterial response to OAE was community-specific, with a consistent increase in the relative abundance of the order Oceanospirillales. OAE also led to increased EEA rates, especially within the bacterial community. These findings suggest that while initial effects on phytoplankton may be limited, the specific impacts on bacterial groups suggest that OAE could influence the remineralization of organic matter. If our results apply to other communities, OAE might initially affect marine microbial dynamics, but further studies are needed to determine if these effects are long-term.

Ethanol-induced dysfunction of the mesenteric perivascular adipose tissue is driven by mineralocorticoid receptors - Ivis V. O. Martins; Thales M. H. Dourado; Gustavo F. Pimenta; Marcela M. Blascke de Mello; Aline G. Fedoce; Wanessa M. C. Awata; Michele M. Castro; Rita C. Tostes; Carlos R. Tirapelli (Pflügers Archiv - European Journal of Physiology, 2025)

Ecological legacies in a tropical savanna: woody layer responses to long-term changes in soil chemistry - Isabela B. Castro; Leonardo Ferreira-Sousa; Thiago R. B. Mello; Alexandra Martins; Mercedes M. C. Bustamante (Oecologia, 2025)

Lower inoculum sizes of phosphorus-solubilizing bacteria benefit maize growth and soil enzyme activity in P-fertilized soils - Sofia I. A. Pereira; Ana S. S. Sousa; Aldo B. Felpeto; Andreia Miguel; João C. Pinto; Paula M. L. Castro; Helena Moreira (Symbiosis, 2025)

First evidence of lead-induced impairment of intestinal digestive enzyme activity in birds - Ana C. Castro-Guijarro; Rodolfo J. Arias; Noelia C. Fernández; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Antidiuretic hormone concentrations in dogs with heart disease and relationship to serum chloride - A.N. Harris; C. Hanner; A. Cooper; R.A. Castro; D.B. Adin (Journal of Veterinary Cardiology, 2025)

Life cycle assessment and life cycle costing of the electrochemical production of peroxosulfates - A. Rodríguez-Gómez; M.P. Castro; C. Sáez; M.A. Rodrigo; C.M. Fernández-Marchante (Chemical Engineering Journal, 2025)

Techno-economic assessment of rice straw biorefineries to produce ethanol with co-production of xylitol and phenolic acids - Rafael C. de Assis Castro; Camilo E. Cabrera Camacho; Inês C. Roberto; Solange I. Mussatto (Biomass and Bioenergy, 2025)

Body development, ingestive behaviour, and physiological responses of Nelore and Crossbred heifers - C. S. Santos; A. R. D. L. Souza; A. L. J. Ferraz; F. A. M. Sterza; R. V. Rohod; M. F. Castro; L. S. Amorim; M. C. E. Queiroz; G. B. Almeida; M. V. M. Oliveira; A. R. D. Santos; D. M. Oliveira (Tropical Animal Health and Production, 2025)

Exopolysaccharides of Ganoderma lucidum Activate the NLRP3 Inflammasome, Modulating Phagocytes and the Response of Mice to Infection with Cryptococcus neoformans - Pedro H. M. Bürgel; Raffael J. A. de Castro; Angelina M. Basso; Luísa C. Coelho; Clara L. F. Marina; Isaque M. Siqueira; Alysia V. Gonzales; Pavel Kucheryavy; Vitor H. Pomin; Elaine Rosechrer Carbonero; Aldo H. Tavares; Anamélia Lorenzetti Bocca (Mycopathologia, 2025)

How septoria leaf blotch affects nitrogen dynamics, grain yield and protein concentration in wheat - S. I. Golik; A. C. Castro; H. M. Pardi; M. R. Simón (Cereal Research Communications, 2025)

Wastewater-Based Epidemiology for Analysis of Human Papillomavirus Infections in a Uruguayan Urban Area - C. Fernandez-Sabatella; G. Corrales; L. Monzon; E. Andrade; N. Sica; E. Cardozo; N. Baccardatz; J. Jacques; S. Castro; M. Castells; M. Victoria; R. Colina (Food and Environmental Virology, 2025)

Challenges for coral restoration in Southwestern Atlantic reefs: guidelines for ethical and sustainable practices - Miguel Mies; Guilherme O. Longo; Adalto Bianchini; Emiliano N. Calderon; Clovis B. Castro; Samuel C. Faria; Ronaldo B. Francini-Filho; Flávia M. Guebert; Marcelo V. Kitahara; Carlos H. F. Lacerda; Tito M. C. Lotufo; Laura F. B. Marangoni; et al. (Biodiversity and Conservation, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

The use of egg quality parameters to evaluate the effect of a diet supplemented with algae and antioxidants in turbot (Scophthalmus maximus) - S. Ramos-Júdez; E. Fatsini; C. Marrero-Alemán; C. García-Pichel; P. Parente; D. Medina; C. Castro; E. Cabrita; C. C.V. Oliveira (Aquaculture, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Effects of dietary supplementation with slow-release urea coated with carnauba wax on intake, ingestive behavior, selectivity, ruminal parameters, performance and carcass traits of lambs - Tainan da Silva Batista; Leilson R. Bezerra; Pedro H.S. Mazza; Analivia M. Barbosa; Beatriz S.C. de Castro; Melissa D. Ferrer; Ana Carolina Ferreira; Jasiel S. de Morais; Edson C. da Silva Filho; Ronaldo L. Oliveira (Small Ruminant Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Porcine circovirus type 2 (PCV2) in Brazil in the past 55 years (1967-2022): evolutionary rates and patterns - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; B. V. Lago; R. L. Silveira; T. X. Castro (Archives of Virology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

A “light in the darkness”: First transcriptomic data from deep-sea spiny eels (Notacanthus, Notacanthiformes) - André Gomes-dos-Santos; André M. Machado; Francisco Baldó; Juan Carlos Arronte; L. Filipe C. Castro; David Barros-García (Marine Genomics, 2025)

Eco-friendly catalyst design: Transforming volcanic lava ashes into sustainable synthesis of glycerol carbonate from glycerol in one pot solvent-free route - Isack Kandola; Thomas Kivevele; Askwar Hilonga; Baraka Kichonge; Paulo Maina; Rose C. Ramkat; Orlando Castro-Ocampo; Cornelio Delesma; Jesús Muñiz; Patrick U. Okoye (Journal of Environmental Chemical Engineering, 2025)

Bio-desulfurization of different vulcanized rubber blends: An ecofriendly approach for end-of-life tires waste pollution - R. Andler; C. Cancino; F. González-Arancibia; J. Rojas; R. Castro; D. Kasai; V. Sanhueza (Journal of Environmental Chemical Engineering, 2025)

Effects of digestate soil amendment on the fate of trace metals and on the soil microbial community - Veronica Baldasso; Maria Paola Tomasino; Stéphanie Sayen; Emmanuel Guillon; Luigi Frunzo; Carlos A.R. Gomes; Maria João Alves; Ricardo Castro; Ana Paula Mucha; C. Marisa R. Almeida (Environmental Pollution, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Can macro- or meso-scale coping capacity variables improve the classification of building flood losses? - D. Rodríguez Castro; M. Cools; S. Roucour; P. Archambeau; D. Molinari; A. R. Scorzini; C. Dessers; S. Erpicum; M. Pirotton; J. Teller; B. Dewals (Natural Hazards, 2025)

Regulatory role of annexin A1 in NLRP3 inflammasome activation in atopic dermatitis: insights from keratinocytes in human and murine studies - Rebeca D. Correia-Silva; Mab P. Corrêa; Maria Eduarda de Castro; Joaquim S. Almeida; Solange C. G. P. D’Ávila; Sonia M. Oliani; Karin V. Greco; Cristiane D. Gil (Journal of Molecular Medicine, 2025)

Cloning and comparative analysis of the retinoid X receptor in two marine gastropods with varying sensitivity to imposex under tributyltin contamination - Sebastián Giulianelli; Raquel Ruivo; Teresa Neuparth; Luís Filipe C. Castro; Gregorio Bigatti; Miguel M. Santos (Environmental Science and Pollution Research, 2025)

Dietary profiles of wild carnivores and Blastocystis occurrence: The case of the endangered Iberian lynx (Lynx pardinus) and systematic review - Javier Caballero-Gómez; Gabriel Ávalos; Pablo Matas-Méndez; Ana M. Figueiredo; Sabrina Castro-Scholten; Débora Jiménez-Martín; Pamela C. Köster; Mónica Santín; Begoña Bailo; David Cano-Terriza; Pedro Sarmento; Nuno Neves; et al. (Research in Veterinary Science, 2025)

Cover crops enhance soil health, crop yield and resilience of tropical agroecosystem - Victória Santos Souza; Lucas Pecci Canisares; Bruna Emanuele Schiebelbein; Darliane de Castro Santos; Rafael Braghieri Menillo; C. Roberto Pinheiro Junior; Maurício Roberto Cherubin (Field Crops Research, 2025)

Assessment of Hepatitis E Virus RNA Detection in Meat Samples: Optimization of Pre-analytical Conditions - Guadalupe Di Cola; Anabella C. Fantilli; Gonzalo Rodríguez-Lombardi; Kevin A. Rucci; Gonzalo Castro; Santiago Mirazo; Silvia Viviana Nates; María Belén Pisano; Viviana E. Ré (Food and Environmental Virology, 2025)

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

Monte Carlo simulation of community microgrid operation: Business prospects in the Brazilian regulatory framework - Francisco C.R. Coelho; Fernando A. Assis; José Filho C. Castro; Antonio R. Donadon; Ronaldo A. Roncolatto; Vittoria E.M.S. Andrade; Pedro A.C. Rosas; Silvangela L.S.L. Barcelos; Osvaldo R. Saavedra; Rafael G. Bento; Rafael K. Carneiro; Pablo F. Hernandez; et al. (Utilities Policy, 2025)

Green extraction strategies to obtain bioactive compounds from ‘Charelo’ vine shoots - Camila C. Muñoz-Realpe; María del Mar Contreras; Alfonso M. Vidal; Eulogio Castro; Inmaculada Romero (Sustainable Chemistry and Pharmacy, 2025)

Distribution and bioconcentration of semivolatile organic compounds (SVOCs) in soils and vascular plant Colobanthus quitensis from Sub-Antarctic and Antarctic regions - C. Egas; T. Luarte; R. Vargas; E. Castro-Nallar; K. Pozo; P. Přibylová; J. Martiník; M. Molina-Montenegro; C. Galbán-Malagón (Science of The Total Environment, 2025)

Effect of penicillamine, hypotaurine and epinephrine (PHE) and pH on stallion sperm during in vitro capacitation - R. Gonzalez-Castro; C. Porflidt; E. Carnevale (Journal of Equine Veterinary Science, 2025)

Histopathological and diagnostic aspects of glanders based on a case series from Brazil - A.F.C. Nassar; D.P. Chiebao; C. Del Fava; S. Miyashiro; V. Castro; R.A. Ogata; J.M. Yamamora; C.A.S. Monteiro; E.J.B. Monteiro (Journal of Equine Veterinary Science, 2025)

Escherichia coli-associated granulomatous diseases in three cats - Milena C. Paz; Igor R. Santos; Lucas T. de Castro; Gabriela Hartmann; Luan C. Henker; Jacqueline Raiter; Regina T. Kemper; Júlia G. Wronski; Eryca C. Lamego; Luiza da Rosa Robusto; Luciana Sonne; David Driemeier; et al. (Journal of Comparative Pathology, 2025)

Nocardiosis in domestic ferrets (Mustela putorius furo) - Carles Juan-Sallés; Luary C. Martínez-Chavarría; Andrés Montesinos; Jacobo Giner; Xavier Valls; Javier Bermúdez; Rigoberto Hernández-Castro; María Ardiaca; Vicente González; José Villora; Alberto Marco (Journal of Comparative Pathology, 2025)

Deployment of portable, modular gas samplers as part of an atmospheric tracer experiment - Khiloni A. Shah; Nathan D. Anderson; Paul M. Baltoi; JohnPeter Bekker; Sarah T. Castro; Grayson N. Constantine; George J. Coutoumanos; Ethan P. Fowler; Kevin A. Guerra; Clayton C. Hudson; Nicholas M. Kaitschuck; John B. Lyle; et al. (Journal of Environmental Radioactivity, 2025)

Nowhere to hide: massive corals’ mortality after cumulative heat stress in a putative climate change refugium - Fernando C. Cardoso; Ivan M. Carneiro; Guilherme M. Castro; Gabriel O. Cardoso; Aline Shimada; Myllena S. Pereira; Livia B. Villela; Paulo S. Salomon; Rodrigo L. Moura (Coral Reefs, 2025)

Assessing spatial and temporal trends over time in potential species richness using satellite time-series and ecological niche models - Nuno Garcia; João C. Campos; João Alírio; Lia B. Duarte; Salvador Arenas-Castro; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Biodiversity and Conservation, 2025)
Assessing biodiversity in protected areas is essential for effective conservation management. However, conventional methods for estimating species richness can lead to inaccurate assessments of biodiversity in these regions. To address this, we present a complementary approach to assess potential species richness at a 1 km resolution in the special conservation area of Montesinho/Nogueira (SAC-MN; Portugal), based on a spatial and temporal estimates of species richness trends over time (2001–2021). We compiled 10,190 species occurrence records from four taxonomic groups: amphibians, reptiles, birds, and mammals. We created correlative ecological niche models (MaxEnt) with a time series of satellite-remote sensing variables (SRS-ENMs) using Google Earth Engine (GEE). We calculated annual potential species richness (PSR) maps by stacking the SRS-ENMs and identified positive and negative trends with the Mann–Kendall test. Each species’ ecological niche model revealed unique patterns of habitat suitability within SAC-MN over time. The eastern and western boundaries of SAC-MN revealed an increase in PSR, while the central area indicated PSR declines. Each group displayed different trends in PSR: birds and mammals were more similar between them than amphibians and reptiles. This approach provides ecologists and conservationists with valuable tools to evaluate PSR and trends over time, offering crucial insights for decision-makers and stakeholders to support local biodiversity conservation efforts.

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Biosynthesis of long-chain polyunsaturated fatty acids in the nereid polychaete Hediste diversicolor: Molecular cloning and functional characterisation of three fatty acyl elongases and two front-end desaturases - Andrea Villena-Rodríguez; Juan C. Navarro; Francisco Hontoria; L. Filipe C. Castro; Arne M. Malzahn; Andreas Hagemann; Óscar Monroig (Aquaculture, 2025)

Spatial and temporal variation of microplastic in mussels from intertidal and subtidal banks in the Southwestern Atlantic Ocean - Mariana B.P. Otegui; María A. Castro; María C. Yuvero; Juliana Giménez (Science of The Total Environment, 2025)

Beyond the threshold - Different accumulation of organochlorine compounds in common dolphins (Delphinus delphis) inhabiting continental and insular ecosystems in the Northeast Atlantic - Raul Valente; Nara de Oliveira-Ferreira; Rita Ferreira; Ana M. Correia; Bárbara M.R. Manhães; Ágatha Gil; Annalisa Sambolino; Elitieri B. Santos-Neto; L. Filipe C. Castro; Haydée A. Cunha; Alexandre F. Azevedo; Ana Dinis; et al. (Environmental Pollution, 2025)

Optical immunosensor panel using quantum dot-antibody conjugates for highly sensitive detection of carbohydrate antigen 19–9 (CA19-9) - Daniela Oliveira; Pedro Oliveira; Ana Xu; Eduarda Rodrigues; Susana G. Guerreiro; Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ana Margarida L. Piloto (Analytica Chimica Acta, 2025)

Environmental factors determining the distribution of Limnoperna fortunei and its impact on benthic communities in the reservoirs of the Rio Negro (Uruguay)) - L. Capurro; J. Pereira; M. Castro; C. Ferrer; D. Fabián; P. Muniz; E. Brugnoli (Biological Invasions, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A Probabilistic View of Forbidden Links: Their Prevalence and Their Consequences for the Robustness of Plant–Hummingbird Communities - François Duchenne; Elisa Barreto; Esteban A. Guevara; Holger Beck; Carolina Bello; Rafaela Bobato; Daniela Bôlla; Emanuel Brenes; Nicole Büttner; Ana P. Caron; Nelson Chaves‐Elizondo; María J. Gavilanes; et al. (Ecology Letters, 2025)
The presence in ecological communities of unfeasible species interactions, termed forbidden links, due to physiological or morphological exploitation barriers has been long debated, but little direct evidence has been found. Forbidden links are likely to make ecological communities less robust to species extinctions, stressing the need to assess their prevalence. Here, we used a dataset of plant–hummingbird interactions, coupled with a Bayesian hierarchical model, to assess the importance of exploitation barriers in determining species interactions. We found evidence for exploitation barriers between flowers and hummingbirds across the 32 studied communities; however, the proportion of forbidden links changed drastically among communities because of changes in trait distributions. The higher the proportion of forbidden links, the more they decreased network robustness because of constraints on interaction rewiring. Our results suggest that exploitation barriers are not rare in plant–hummingbird communities and have the potential to limit the rescue of species experiencing partner extinction.

Exploring the potential of a waste-derived bone char for pharmaceuticals adsorption in saline-based wastewater - Catarina Miranda; Francesca Scalera; Andreana Piancastelli; Robert C. Pullar; Maria Elizabeth Tiritan; Clara Piccirillo; Paula M.L. Castro; Catarina L. Amorim (Sustainable Chemistry and Pharmacy, 2024)

Monitoring macroplastics in aquatic and terrestrial ecosystems: Expert survey reveals visual and drone-based census as most effective techniques - L. Gallitelli; P. Girard; U. Andriolo; M. Liro; G. Suaria; C. Martin; A.L. Lusher; K. Hancke; MCM Blettler; O. Garcia-Garin; I.E. Napper; L. Corbari; et al. (Science of The Total Environment, 2024)

Living between sand and waves: Age and feeding habits of sand sole (Pegusa lascaris, Risso 1810) and brill (Scophthalmus rhombus, Linnaeus, 1758) on the beaches of the Gulf of Cádiz (Southwest Iberian Peninsula) - C. Rodríguez-García; M. Jiménez-Cobo; R. Cabrera-Castro (Regional Studies in Marine Science, 2024)

Modeling sediment movement in the shallow-water framework: A morpho-hydrodynamic approach with numerical simulations and experimental validation - E. Guerrero Fernández; M.J. Castro Díaz; Y. Wei; C. Moore (Ocean Modelling, 2024)

Paleoproterozoic sediment-derived magmas reveal a late orogenic stage in the southern São Francisco Craton, Brazil: Evidence from petrogenesis of the 2.0 Ga Cupim Pluton leucogranites - Syro Lacerda; Martin Guitreau; Leonardo Gonçalves; Hugo Moreira; Cristiane C. Gonçalves; Marco Aurélio Pinheiro; Cassiano Costa e Castro; Régis Doucelance (Lithos, 2024)

Thinking big: The role of mega trails in creating meaning and sense of place to conserve large landscapes - Ernesto B. Viveiros-de-Castro; Taylor V. Stein; Martha C. Monroe (Journal of Outdoor Recreation and Tourism, 2024)

Detection of fusarium wilt-induced physiological impairment in strawberry plants using hyperspectral imaging and machine learning - P. Castro-Valdecantos; G. Egea; C. Borrero; M. Pérez-Ruiz; M. Avilés (Precision Agriculture, 2024)
Strawberry ( Fragraria x ananassa ) is a crop affected by various soil-borne fungal pathogens with mostly non-specific foliar symptoms and often requiring laboratory isolation for correct diagnosis. Moreover, these nonspecific foliar symptoms, appreciated by the human eye, appear after some time following infection by the pathogen. Early detection of plant diseases is one of the primary objectives in agriculture because it may contribute to identifying more tolerant cultivars in breeding programs and optimise pesticide use in agricultural production with earlier applications in emerging disease foci. New technologies, such as remote sensing and machine learning (ML) algorithms, have arisen as potential tools to improve the ability to detect and classify different crop diseases. The combined use of hyperspectral imagery and ML algorithms were investigated to detect and classify the physiological stress caused by early infections of Fusarium wilt in strawberry plants. Six ML models, namely artificial neural network, decision tree, K-nearest neighbour, support vector machine, multinomial logistic regression and Naïve Bayes were developed to estimate physiological stress associated with Fusarium wilt disease. The results showed that stomatal conductance (g s ) and photosynthesis ( A ) declined even without visual symptoms of the disease. Among the six ML models evaluated, the artificial neural network model showed the highest classification performance with an overall accuracy of 81%, regardless of the physiological parameter utilized for model training. Moreover, the artificial neural network accurately predicted the absolute values of both physiological parameters (g s and A) based on the complete spectral signature from visually healthy foliar tissue, achieving coefficients of determination of 84% and 81%, respectively. Consequently, ML models utilizing physiological response data and hyperspectral imaging exhibited remarkable robustness, facilitating the estimation of Fusarium wilt severity in strawberry plants even without visual symptoms.

Unravelling epigenetic mechanisms in Cerastoderma edule genome: a comparison of healthy and neoplastic cockles - Alejandro Viña-Feás; Javier Temes-Rodríguez; André Vidal-Capón; Samuel Novas; Jorge Rodríguez-Castro; Ana Pequeño-Valtierra; Juan José Pasantes; Jose M. C. Tubío; Daniel Garcia-Souto (Molecular Genetics and Genomics, 2024)
Cancer is a multifaceted genetic disease characterized by the acquisition of several essential hallmarks. Notably, certain cancers exhibit horizontal transmissibility, observed across mammalian species and diverse bivalves, the latter referred to as hemic neoplasia. Within this complex landscape, epigenetic mechanisms such as histone modifications and cytosine methylation emerge as fundamental contributors to the pathogenesis of these transmissible cancers. Our study delves into the epigenetic landscape of Cerastoderma edule , focusing on whole-genome methylation and hydroxymethylation profiles in heathy specimens and transmissible neoplasias by means of Nanopore long-read sequencing. Our results unveiled a global hypomethylation in the neoplastic specimens compared to their healthy counterparts, emphasizing the role of DNA methylation in these tumorigenic processes. Furthermore, we verified that intragenic CpG methylation positively correlated with gene expression, emphasizing its role in modulating transcription in healthy and neoplastic cockles, as also highlighted by some up-methylated oncogenic genes. Hydroxymethylation levels were significantly more elevated in the neoplastic samples, particularly within satellites and complex repeats, likely related to structural functions. Additionally, our analysis also revealed distinct methylation and activity patterns in retrotransposons, providing additional insights into bivalve neoplastic processes. Altogether, these findings contribute to understanding the epigenetic dynamics of bivalve neoplasias and shed light on the roles of DNA methylation and hydroxymethylation in tumorigenesis. Understanding these epigenetic alterations holds promise for advancing our broader understanding of cancer epigenetics.

Polymorphic pseudogenes in the human genome - a comprehensive assessment - Mónica Lopes-Marques; M. João Peixoto; David N. Cooper; M. João Prata; Luísa Azevedo; L. Filipe C. Castro (Human Genetics, 2024)
Background: Over the past decade, variations of the coding portion of the human genome have become increasingly evident. In this study, we focus on polymorphic pseudogenes, a unique and relatively unexplored type of pseudogene whose inactivating mutations have not yet been fixed in the human genome at the global population level. Thus, polymorphic pseudogenes are characterized by the presence in the population of both coding alleles and non-coding alleles originating from Loss-of-Function (LoF) mutations. These alleles can be found both in heterozygosity and in homozygosity in different human populations and thus represent pseudogenes that have not yet been fixed in the population. Results: A methodical cross-population analysis of 232 polymorphic pseudogenes, including 35 new examples, reveals that human olfactory signalling, drug metabolism and immunity are among the systems most impacted by the variable presence of LoF variants at high frequencies. Within this dataset, a total of 179 genes presented polymorphic LoF variants in all analysed populations. Transcriptome and proteome analysis confirmed that although these genes may harbour LoF alleles, when the coding allele is present, the gene remains active and can play a functional role in various metabolic pathways, including drug/xenobiotic metabolism and immunity. The observation that many polymorphic pseudogenes are members of multigene families argues that genetic redundancy may play a key role in compensating for the inactivation of one paralogue. Conclusions: The distribution, expression and integration of cellular/biological networks in relation to human polymorphic pseudogenes, provide novel insights into the architecture of the human genome and the dynamics of gene gain and loss with likely functional impact.

Strong climate mitigation potential of rewetting oil palm plantations on tropical peatlands - Nisa Novita; Adibtya Asyhari; Rasis P. Ritonga; Adi Gangga; Gusti Z. Anshari; Joni Jupesta; Jennifer C. Bowen; Nurul Silva Lestari; J. Boone Kauffman; Alison M. Hoyt; Clarice R. Perryman; Israr Albar; et al. (Science of The Total Environment, 2024)

Sediment recycling during the Holocene marine transgression in Ría de Vigo (NW Iberia): multiproxy evidence and environmental implications - C. Muñoz Sobrino; A. Castro-Parada; V. Cartelle; N. Martínez-Carreño; C. Delgado; N. Cazás; I. Lázaro; S. García-Gil (Quaternary Science Reviews, 2024)

The rheology of rhyolite magma from the IDDP-1 borehole and Hrafntinnuhryggur (Krafla, Iceland) with implications for geothermal drilling - Fabian B. Wadsworth; Jérémie Vasseur; Yan Lavallée; Kai-Uwe Hess; Jackie E. Kendrick; Jonathan M. Castro; Daniel Weidendorfer; Shane M. Rooyakkers; Annabelle Foster; Lucy E. Jackson; Ben M. Kennedy; Alexander R.L. Nichols; et al. (Journal of Volcanology and Geothermal Research, 2024)

Anatomopathological characterization of hepatic lesions of feline infectious peritonitis in cats - Fernanda G. Cony; Vanessa C. Pereira; Mônica Slaviero; Rafael P. Lima; Lucas T. de Castro; José T.R. de Moraes; João M.G. Aliardi; David Driemeier; Luciana Sonne; Welden Panziera; Saulo P. Pavarini (Journal of Comparative Pathology, 2024)

Emotional attachment and philosophical worldviews explain human connectedness to nature in abandoned rural Spain - C. López-Zayas; A. J. Castro; J. M. Requena-Mullor; M. D. López-Rodríguez; E. Garau; C. Quintas-Soriano (Sustainability Science, 2024)
Land abandonment and rural depopulation are escalating worldwide, presenting sustainability dilemmas for both rural and urban regions. However, there remains a dearth of research on the sociocultural dimensions of abandonment from a local standpoint. This investigation focuses on a case study conducted in southeastern Spain, wherein a social survey was used to evaluate the perspectives of local communities concerning human–nature interconnectedness, land abandonment, and their impacts on quality of life. A survey campaign was administered in the case study region during the spring of 2021, and 122 surveys were collected. The findings identify, in the context of the progressive abandonment of rural lands in Spain, key factors that explain the desire of local people to inhabit and not abandon rural regions in southeastern Spain. Our results also show a strong connection between people and nature in rural Spain, which is explained by the capacity of locals to form relational values in rural environments and the existence of philosophical worldviews and emotional attachments to rural lifestyles. However, barriers to not abandoning rural environments were also identified, including a lack of professional and economic opportunities. Our results suggest that the mitigation of depopulation in rural areas in Spain requires actions to foster land stewardship and address socioeconomic imbalances.

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Evolution of the transtensional Barreirinhas pull-apart system in the Brazilian Equatorial margin and its correlation with the African conjugate counterpart - David L. de Castro; Diógenes C. Oliveira; Francisco H.R. Bezerra (Tectonophysics, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Useful properties of phenomenological-based models - Estefania Aguirre-Zapata; Laura Lema-Perez; Lina Gomez-Echavarria; Hector Botero-Castro; Juan C. Maya; Farid Chejne; Hernan Alvarez (Ecological Modelling, 2024)

Protease inhibitors characterisation by SDS-PAGE and MALDI-TOF from Alocasia macrorrhizos and their modulation of macrophage immune-inflammatory properties - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2024)

Characterization of SimulCam, a standoff Raman system for scientific support of SuperCam operations on Mars - Jose A. Manrique; Guillermo Lopez-Reyes; Marco Veneranda; Aurelio Sanz-Arranz; Juan Sancho Santamaria; Sofia Julve-Gonzalez; Ivan Reyes-Rodríguez; Teresa Fornaro; Juan Manuel Madariaga; Gorka Arana; Kepa Castro; Ivair Gontijo; et al. (Advances in Space Research, 2024)

P13-07 Uranium and kidney cancer: insights from genetically engineered mouse models in the UKCAN project - L. De Castro; O. Claude; M. Brisset; C. Gillot; A. Manoury; A. Sache; F. Voyer; D. Suhard; V. Monceau; C. Bouvier-Capely; C. Ibanez; Y. Guéguen (Toxicology Letters, 2024)

“Architecture, construction system and functioning of the roman saltworks of O Areal (Vigo-Galicia-Spain). A reference in the investigation of salt production in the roman world” - Juan C. Castro Carrera (Quaternary Science Reviews, 2024)

Low-cost environmental enrichment reduces stereotypical behaviors in the blue-fronted parrot Amazona aestiva and the yellow-faced amazon Alipiopsitta xanthops - Valentina Maria Apolinário Miranda de Sousa; Bruna Almeida; Mariela C. Castro; Gisela Sobral (Ornithology Research, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Weed species classification with UAV imagery and standard CNN models: Assessing the frontiers of training and inference phases - G.A. Mesías-Ruiz; I. Borra-Serrano; J.M. Peña; A.I. de Castro; C. Fernández-Quintanilla; J. Dorado (Crop Protection, 2024)

Dynamic shifts of functional diversity through climate-resilient strategies and farmland restoration in a mountain protected area - João C. Campos; João Alírio; Salvador Arenas-Castro; Lia Duarte; Nuno Garcia; Adrián Regos; Isabel Pôças; Ana C. Teodoro; Neftalí Sillero (Journal of Environmental Management, 2024)

Comparison of direct and indirect soil organic carbon prediction at farm field scale - C. Segura; A.L. Neal; L. Castro-Sardiňa; P. Harris; M.J. Rivero; L.M. Cardenas; J.G.N. Irisarri (Journal of Environmental Management, 2024)

Anatomy, histology and ultrastructure of the digestive tract in Andean fish (Trichomycterus bogotensis) and ecological implications - M. Ortiz-Ruiz; C. López-Flórez; M. I. Castro-Rebolledo; B. Baldisserotto; E. Gómez-Ramírez (Zoomorphology, 2024)
Trichomycterus bogotensis is one of the three species of fish that inhabit the Colombian Andes. However, several aspects of its basic biology, including its digestive system, are unknown. The morphology and histology of the digestive system are of great importance for understanding a species’ feeding habits and food preferences. Thus, this study aimed to perform a morphological description of the digestive tract of T. bogotensis . The gastrointestinal tract of seven specimens was processed for paraffin histology, high-resolution optical microscopy, and transmission electron microscopy. Anatomically, T. bogotensis exhibits a terminal mouth with villiform teeth, a narrow esophagus, a large and muscular stomach, and a short intestine. Histology and ultrastructure revealed a tissue organization similar to that reported for other Silurids, composed of four layers: mucosal, submucosal, muscular, and serosa. The anatomical and histological characteristics suggest that T. bogotensis is a benthic species with a tendency to carnivory.

Aging- and alcohol-associated spatial transcriptomic signature in mouse acute pancreatitis reveals heterogeneity of inflammation and potential pathogenic factors - Rachel R. Tindall; Yuntao Yang; Isabella Hernandez; Amy Qin; Jiajing Li; Yinjie Zhang; Thomas H. Gomez; Mamoun Younes; Qiang Shen; Jennifer M. Bailey-Lundberg; Zhongming Zhao; Daniel Kraushaar; et al. (Journal of Molecular Medicine, 2024)
The rapidly aging population is consuming more alcohol, leading to increased alcohol-associated acute pancreatitis (AAP) with high mortality. However, the mechanisms remain undefined, and currently there are no effective therapies available. This study aims to elucidate aging- and alcohol-associated spatial transcriptomic signature by establishing an aging AAP mouse model and applying Visium spatial transcriptomics for understanding of the mechanisms in the context of the pancreatic tissue. Upon alcohol diet feeding and caerulein treatment, aging mice (18 months) developed significantly more severe AAP with 5.0-fold increase of injury score and 2.4-fold increase of amylase compared to young mice (3 months). Via Visium spatial transcriptomics, eight distinct tissue clusters were revealed from aggregated transcriptomes of aging and young AAP mice: five acinar, two stromal, and one islet, which were then merged into three clusters: acinar, stromal, and islet for the comparative analysis. Compared to young AAP mice, > 1300 differentially expressed genes (DEGs) and approximately 3000 differentially regulated pathways were identified in aging AAP mice. The top five DEGs upregulated in aging AAP mice include Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp with heterogeneous distributions among the clusters. Taken together, this study demonstrates spatial heterogeneity of inflammatory processes in aging AAP mice, offering novel insights into the mechanisms and potential drivers for AAP development. Key messages Mechanisms regarding high mortality of AAP in aging remain undefined. An aging AAP mouse model was developed recapturing clinical exhibition in humans. Spatial transcriptomics identified contrasted DEGs in aging vs. young AAP mice. Top five DEGs were Mmp8 , Ppbp , Serpina3m , Cxcl13 , and Hamp in aging vs. young AAP mice. Our findings shed insights for identification of molecular drivers in aging AAP.

Recovering and reusing water, H2SO4, nickel and cobalt from gold mining wastewater using air-gap membrane distillation and solvent extraction - Victor R. Moreira; Livia M.C. Castro; Julio C. Balarini; Tania L.M. Santos; Míriam C.S. Amaral (Desalination, 2024)

Assessing the dynamics of common dolphin ( Delphinus delphis ) mother‐calf pairs along the south coast of Portugal using unmanned aerial vehicles - Joana Castro; André Cid; Alicia Quirin; Fábio L. Matos; Rui Rosa; Heidi C. Pearson (Marine Mammal Science, 2024)
Maternal grouping dynamics involve trade‐offs between: (1) infant protection from predation (predation hypothesis), (2) infant protection from male harassment (infant safety hypothesis), and (3) reducing scramble competition for prey resources (foraging‐type scramble competition hypothesis). Using unmanned aerial vehicles, we assessed grouping dynamics in common dolphin ( Delphinus delphis ) groups containing mother‐calf pairs to address these hypotheses. We analyzed social aspects and structural group elements using generalized additive mixed models and modeled group formation using multinomial generalized estimating equations. Calf proportion was higher in very compact groups and in groups of 10–20 individuals but decreased in larger groups. The frequency of socio‐sexual behaviors increased in larger groups and decreased in groups with higher calf proportion. Calf distance to its nearest neighbor decreased with increasing group size and cohesion. With a higher proportion of calves, scatter (versus parallel) formation was less frequent. A calf's nearest neighbor was most often (55.4%) a nonmother. Calves showed a preference for being in the front center of the group. These results offer strong support for the predation and infant safety hypotheses and partial support for the foraging‐type scramble competition hypothesis. This work provides insight into the adaptive function of maternal strategies in a small delphinid.

Polycyclic aromatic hydrocarbons in seawater after the mysterious oil spill of 2019 on the Pernambuco coast, northeast Brazil - Thayane Cristina da S. Moreira; Ana Flávia B. de Oliveira; Pedro Gabriel C. de Lucena; Estefani S. do Nascimento; Leonardo M.F. de Almeida; Cristiane Maria V. de Araújo-Castro; Lino Angel V. Rojas; Gilvan T. Yogui; Eliete Zanardi-Lamardo; Jandyson M. Santos (Marine Pollution Bulletin, 2024)

Fangs and foliage: Unearthing the haemotoxic secrets of cannabis-dwelling rattlesnakes - Lachlan A. Bourke; Christina N. Zdenek; Tam M. Huynh; Wayne C. Hodgson; Alejandro Alagón; Edgar N. Castro; Jason Jones; Bryan G. Fry (Toxicon, 2024)

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

Distribution, diversity and genetic structure of alders (Alnus lusitanica and A. glutinosa) in Spain - M. Angela Martín; R. Moreno; J.V. Die; A. Cabrera; P. Castro; M.D. Pérez; C. Palomino; B. Cuenca; F. Pérez; A. Solla (Forest Ecology and Management, 2024)

A multi-tissue de novo transcriptome assembly and relative gene expression of the vulnerable freshwater salmonid Thymallus ligericus - Giulia Secci-Petretto; Steven Weiss; André Gomes-dos-Santos; Henri Persat; André M. Machado; Inês Vasconcelos; L. Filipe C. Castro; Elsa Froufe (Genetica, 2024)
Freshwater ecosystems are among the most endangered ecosystems worldwide. While numerous taxa are on the verge of extinction as a result of global changes and direct or indirect anthropogenic activity, genomic and transcriptomic resources represent a key tool for comprehending species' adaptability and serve as the foundation for conservation initiatives. The Loire grayling, Thymallus ligericus , is a freshwater European salmonid endemic to the upper Loire River basin. The species is comprised of fragmented populations that are dispersed over a small area and it has been identified as a vulnerable species. Here, we provide a multi-tissue de novo transcriptome assembly of T. ligericus . The completeness and integrity of the transcriptome were assessed before and after redundancy removal with lineage-specific libraries from Eukaryota, Metazoa, Vertebrata, and Actinopterygii. Relative gene expression was assessed for each of the analyzed tissues, using the de novo assembled transcriptome and a genome-based analysis using the available T. thymallus genome as a reference. The final assembly, with a contig N50 of 1221 and Benchmarking Universal Single-Copy Orthologs (BUSCO) scores above 94%, is made accessible along with structural and functional annotations and relative gene expression of the five tissues (NCBI SRA and FigShare databases). This is the first transcriptomic resource for this species, which provides a foundation for future research on this and other salmonid species that are increasingly exposed to environmental stressors.

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Welfare assessment of Thoroughbred horses naturally infected with gastrointestinal parasites in Southern Brazil: Quantifying the host-parasite relationship - L.S. Abrahão Pires; C. Abrahão; L.L. Dias de Castro; J. Hammerschmidt; J. Antunes; C.F.M. Molento; M.B. Molento (Journal of Equine Veterinary Science, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Benefits of probiotic use on COVID-19: A systematic review and meta-analysis - Suelen Neris Almeida Viana; Tamires do Reis Santos Pereira; Janaína de Carvalho Alves; Caroline Tianeze de Castro; Lucas Santana C. da Silva; Lúcio Henrique Sousa Pinheiro; Mariana Nougalli Roselino (Critical Reviews in Food Science and Nutrition, 2024)

Differentiating Bagasse and Straw as Feedstocks for Sugarcane Cellulosic Ethanol: Insights from Pilot-Scale Pretreatments - Viviane M. Nascimento; Simone C. Nakanishi; Carlos Alberto de Oliveira Filho; Absai da Conceição Gomes; Aline Machado de Castro; Ana Paula Rodrigues Torres; Christian Alejandro Queipo; Danuza Nogueira Moyses; Felipe de Oliveira Brito; Luiz Fernando Martins Bandeira; Carlos Driemeier (BioEnergy Research, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Organophosphate ester additives and microplastics in benthic compartments from the Loire estuary (French Atlantic coast) - J. Castro-Jiménez; Y. Aminot; N. Bely; C. Pollono; B.I.T. Idjaton; L. Bizzozero; O. Pierre-Duplessix; N.N. Phuong; J. Gasperi (Marine Pollution Bulletin, 2024)

Trophic ecology of sympatric sea turtles in the tropical Atlantic coast of Brazil - Moises F. Bezerra; Cesar A. Barrios-Rodriguez; Carlos E. Rezende; Melania C. López-Castro; Luiz D. Lacerda (Marine Environmental Research, 2024)

An historical “wreck”: A transcriptome assembly of the naval shipworm, Teredo navalis Linnaeus, 1978 - André Gomes-dos-Santos; Marcos Domingues; Raquel Ruivo; Elza Fonseca; Elsa Froufe; Diana Deyanova; João N. Franco; L. Filipe C. Castro (Marine Genomics, 2024)

A whole-body transcriptome assembly of the annelid worm Hediste diversicolor - André M. Machado; Rodrigo Samico; Marcos Domingues; Andreas Hagemann; Luísa M.P. Valente; Arne M. Malzahn; André Gomes-dos-Santos; Raquel Ruivo; Juan Carlos Navarro; Óscar Monroig; L. Filipe C. Castro (Marine Genomics, 2024)

Polyhydroxyalkanoates production from a waste-derived feedstock driven by the reactor operating conditions: The role of biomass microbiome and its reactivation capacity - Eliana C. Guarda; Catarina L. Amorim; Gabriele Pasculli; Paula M.L. Castro; Claudia F. Galinha; Anouk F. Duque; Maria A.M. Reis (Journal of Cleaner Production, 2024)

Unravelling the main immune repertoire of Paracentrotus lividus following Vibrio anguillarum bath challenge - Sergio Fernández-Boo; André Machado; L. Filipe C. Castro; Rita Azeredo; Benjamin Costas (Fish & Shellfish Immunology, 2024)

Near-slope turbulence in a Rockall canyon - Hans van Haren; Gunnar Voet; Matthew H. Alford; Bieito Fernández-Castro; Alberto C. Naveira Garabato; Bethan L. Wynne-Cattanach; Herlé Mercier; Marie-José Messias (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Database of immature stage traits of Ephemeroptera, Plecoptera, and Trichoptera (EPT) genera for the Amazon - Natália Beatriz Barros Santos; Gabriel Martins Cruz; Josinete Sampaio Monteles; Ana Paula Justino de Faria; Viviane Caetano Firmino; Yulie Shimano; Victor Rennan Santos Ferreira; Ana Luiza-Andrade; Frederico Falcão Salles; Diego M. P. Castro; Fábio B. Quinteiro; Lucas R. C. Lima; et al. (Aquatic Sciences, 2024)

Evaluation of renal function in precarious workers exposed to heavy metals in vulnerable scenarios in the metropolitan area of San Luis Potosí, México - Mariana Alejandra Castro-Mejía; Kelvin Saldaña-Villanueva; Karen Beatriz Méndez-Rodríguez; Manolo Ortega-Romero; Olivier C. Barbier; Francisco Javier Pérez-Vázquez (Environmental Toxicology and Pharmacology, 2024)

Analysis of gaseous emission and particle number size distributions in metal casting processes with binder jetting moulds - C. Blanco-Alegre; A.I. Calvo; M.Á. Castro-Sastre; A.I. Fernández-Abia; P. Rodríguez-González; F. Oduber; A. Castro; J. Barreiro; R. Fraile (Building and Environment, 2024)

Large-scale crops are sources of polyphagous pest populations for small farmers at the landscape level: an isotope tracing model - Érika C. S. Castro; Nícholas F. Camargo; Danyelle R. Novaes; Marina A. M. Pereira; Gabriela B. Nardoto; Pedro H. B. Togni (Journal of Pest Science, 2024)

Effect of marine heatwaves and warming on kelp microbiota influence trophic interactions - Louise C. Castro; Adriana Vergés; Sandra C. Straub; Alexandra H. Campbell; Melinda A. Coleman; Thomas Wernberg; Peter Steinberg; Torsten Thomas; Symon Dworjanyn; Paulina Cetina‐Heredia; Moninya Roughan; Ezequiel M. Marzinelli (Molecular Ecology, 2024)
The range‐expansion of tropical herbivores due to ocean warming can profoundly alter temperate reef communities by overgrazing the seaweed forests that underpin them. Such ecological interactions may be mediated by changes to seaweed‐associated microbiota in response to warming, but empirical evidence demonstrating this is rare. We experimentally simulated ocean warming and marine heatwaves (MHWs) to quantify effects on two dominant temperate seaweed species and their microbiota, as well as grazing by a tropical herbivore. The kelp Ecklonia radiata 's microbiota in sustained warming and MHW treatments was enriched with microorganisms associated with seaweed disease and tissue degradation. In contrast, the fucoid Sargassum linearifolium 's microbiota was unaffected by temperature. Consumption by the tropical sea‐urchin Tripneustes gratilla was greater on Ecklonia where the microbiota had been altered by higher temperatures, while Sargassum 's consumption was unaffected. Elemental traits (carbon, nitrogen), chemical defences (phenolics) and tissue bleaching of both seaweeds were generally unaffected by temperature. Effects of warming and MHWs on seaweed holobionts (host plus its microbiota) are likely species‐specific. The effect of increased temperature on Ecklonia 's microbiota and subsequent increased consumption suggest that changes to kelp microbiota may underpin kelp‐herbivore interactions, providing novel insights into potential mechanisms driving change in species' interactions in warming oceans.

Chemical prospection and antioxidant activity of Humiria balsamifera (Aubl.) A. St. Hil. AND Hymenaea courbaril L. - Jhuliana Monteiro de Matos; Andressa Rose Castro Costa; Marciel Nascimento Justino; Marcos Bispo Pinheiro Camara; Osmar Luis Silva Vasconcelos; J. C. Marques; Clenilma Marques Brandão; Georgiana Eurides de Carvalho Marques (Natural Product Research, 2024)

Precision and accuracy of common coral reef sampling protocols revisited with photogrammetry - Ivan M. Carneiro; João A. Sá; Pamela M. Chiroque-Solano; Fernando C. Cardoso; Guilherme M. Castro; Paulo S. Salomon; Alex C. Bastos; Rodrigo L. Moura (Marine Environmental Research, 2024)

Bacterial nanocellulose spheres coated with meta acrylic copolymer: Vaccinium meridionale swartz extract delivery for colorectal cancer chemoprevention - M. Osorio; L. Posada; E. Martínez; V. Estrada; G. Quintana; Maria E. Maldonado; S. Peresin; J. Orozco; C. Castro (Food Hydrocolloids, 2024)

Carbon Dioxide and Nitrous Oxide Emissions from a Typical Sugarcane Soil in the Cauca River Valley, Colombia - Manuel C. Valencia-Molina; Jorge Chalco Vera; Sandra Loaiza; Catalina Trujillo; Bryan Munera; Mauricio Castro-Franco; Amanda Silva-Parra; Ngonidzashe Chirinda; Fernando Muñoz-Arboleda (Sugar Tech, 2024)
Sugarcane is an important crop for tropical countries and to accurately inventory its greenhouse gas (GHG) emissions baseline measurements are needed. In Colombia, sugarcane is one of the most important crops in terms of cultivated area and, paradoxically, scientific information reporting GHG emissions based on field measurements is almost nonexistent. The objective of this work was to quantify the direct emissions of carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) in the sugarcane-soil system of the Cauca river valley, Colombia. For this purpose, a field experiment was established in a typic haplustert soil cropped with sugarcane. The effects of nitrogen (N) fertilization and sampling site on its GHG emissions were tested using the closed static chamber method over a period of 211 days. The main cumulative emissions were 765.14 ± 34.1 g CO 2 –C m −2 and 125.4 ± 22.6 mg N 2 O–N m −2 . Overall, GHG emissions were modified by N fertilization, the sampling site, and their interaction. Nitrogen fertilization with urea increased mean and cumulative CO 2 and N 2 O emissions, especially at the row sampling site. This paper highlights the importance of considering these factors when the quantification of GHGs or a reduction of their associated uncertainties are required. This work reportss the first GHG emissions data for a typical sugarcane agroecosystem in Colombia.

Beyond fish oil: Assessing the implications of alternative dietary lipid sources for turbot (Scophthalmus maximus) on growth, nutrient utilization and muscle quality - M. Monteiro; A. Marques; R.S. Costa; M.A. Salgado; C. Castro; L. Conceição; L.M.P. Valente (Aquaculture, 2024)

Exploring the Experience of Neck Pain in Individuals With Episodic Migraine - Andrew Blumenfeld; Margaret Mordin; Katherine Kosa; Colleen Castro; Jonathan Stokes; Darshini Shah; Dawn C. Buse (Toxicon, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

The role of snow in scavenging aerosol particles: A physical-chemical characterization - C. Blanco-Alegre; A.I. Calvo; A. Castro; F. Oduber; E. Alonso-Blanco; C. Alves; M. Cerqueira; R. López; F. Lucarelli; S. Nava; G. Calzolai; R. Fraile (Science of The Total Environment, 2024)

Removing color while lowering toxicity: the case for decolorization of textile dyes and simulated effluents with yeasts - M. Mendes; A. C. Cassoni; S. Alves; P. Moreira; M. E. Pintado; P. M. L. Castro (International Journal of Environmental Science and Technology, 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

Heterogeneous photosensitization for water reuse in cellars: evaluation of silica, spongin, and chitosan as carrier material - Andreia D. Santos; Eduardo Pinho; Patrícia Reis; Rui C. Martins; Marta Gmurek; Anabela Nogueira; Sérgio Castro-Silva; Luís M. Castro; Rosa M. Quinta-Ferreira (Environmental Science and Pollution Research, 2023)
Photosensitization, a powerful oxidation reaction, offers significant potential for wastewater treatment in the context of industrial process water reuse. This environmentally friendly process can be crucial in reducing water consumption and industrial pollution. The ultimate goal is to complete process water reuse, creating a closed-loop system that preserves the inherent value of water resources. The photosensitized oxidation reaction hinges on three essential components: the photosensitizer, visible light, and oxygen. In this study, we assess the performance of three distinct materials—silica, chitosan, and spongin—as carrier materials for incorporating the phthalocyanine photosensitizer (ZnPcS 4 ) in the heterogenous photosensitization process. Among the three materials under study, chitosan emerged as the standout performer in reactor hydrodynamic performance. In the photooxidation process, the photosensitizer ZnPcS 4 exhibited notable efficacy, resulting in a significant reduction of approximately 20 to 30% in the remaining COD concentration of the cellar wastewater. Chitosan demonstrated exceptional hydrodynamic characteristics and displayed a favorable response to pH adjustments within the range of 8 to 10, outperforming the other two carrier materials. To further enhance the efficiency of continuous operation, exploring methods for mitigating photosensitizer bleaching within the reaction medium and investigating the impact of different pH values on the process optimization would be prudent.

Modeling the interannual variability in Maipo and Rapel river plumes off central Chile - Julio Salcedo-Castro; Antonio Olita; Freddy Saavedra; Gonzalo S. Saldías; Raúl C. Cruz-Gómez; Cristian D. De la Torre Martínez (Ocean Science, 2023)
River plumes have a direct influence on coastal environments, impacting coastal planktonic and benthic communities, including fishery resources. In general, the main drivers of river plume dynamics are the river discharge and the alongshore wind stress, whereas the tides and topography play a secondary role. In central Chile, rivers flowing into the eastern Pacific have a relatively short path on land, with a high slope and a mixed snow–rain regime. This study aims to understand the interannual variability in the plumes of the Maipo and Rapel rivers in the coastal/shelf area off central Chile and their influence on local ocean dynamics. We used the Coastal and Regional Ocean Community (CROCO) model, with 1 km horizontal resolution and 20 sigma levels, to simulate the ocean dynamics for the period 2003–2011. The results show that the plume's area coverage and coastal ocean salinity are strongly correlated with the river discharges. The predominant northeastward winds control the plumes' orientation toward the northwest. However, episodes of southeastward winds in winter can reverse the plumes' direction, promoting their attachment to the coast and southward transport. Results also show a salification trend linked to the severe droughts hitting central Chile during the studied period. This salification determines a change in local dynamics which could be more frequent in future scenarios of climate change with a significant lack of rain and river discharges along central Chile.

Combining computational tools and experimental studies towards endocrine disruptors mitigation: A review of biocatalytic and adsorptive processes. - Maria Cristina Silva; Alexandre A. de Castro; Karla Lara Lopes; Igor F. Lara Ferreira; Raphael Resende Bretz; Teodorico C. Ramalho (Chemosphere, 2023)

Characterization of gelatin films functionalized with silver nanoparticles or polysorbate 20 as UV–vis light controllers - Gonzalo Santos-López; Delia Soto-Castro; Frank Manuel León-Martínez; Ángel Ramón Hernández-Martínez; Miguel C. Gutiérrez (Food Packaging and Shelf Life, 2023)

RNA-Binding Proteins: A Role in Neurotoxicity? - Andrea Ocharán-Mercado; Jaqueline Loaeza-Loaeza; Yaneth Castro-Coronel; Leonor C. Acosta-Saavedra; Luisa C. Hernández-Kelly; Daniel Hernández-Sotelo; Arturo Ortega (Neurotoxicity Research, 2023)
Despite sustained efforts to treat neurodegenerative diseases, little is known at the molecular level to understand and generate novel therapeutic approaches for these malignancies. Therefore, it is not surprising that neurogenerative diseases are among the leading causes of death in the aged population. Neurons require sophisticated cellular mechanisms to maintain proper protein homeostasis. These cells are generally sensitive to loss of gene expression control at the post-transcriptional level. Post-translational control responds to signals that can arise from intracellular processes or environmental factors that can be regulated through RNA-binding proteins. These proteins recognize RNA through one or more RNA-binding domains and form ribonucleoproteins that are critically involved in the regulation of post-transcriptional processes from splicing to the regulation of association of the translation machinery allowing a relatively rapid and precise modulation of the transcriptome. Neurotoxicity is the result of the biological, chemical, or physical interaction of agents with an adverse effect on the structure and function of the central nervous system. The disruption of the proper levels or function of RBPs in neurons and glial cells triggers neurotoxic events that are linked to neurodegenerative diseases such as spinal muscular atrophy (SMA), amyotrophic lateral sclerosis (ALS), fragile X syndrome (FXS), and frontotemporal dementia (FTD) among many others. The connection between RBPs and neurodegenerative diseases opens a new landscape for potentially novel therapeutic targets for the intervention of these neurodegenerative pathologies. In this contribution, a summary of the recent findings of the molecular mechanisms involved in the plausible role of RBPs in RNA processing in neurodegenerative disease is discussed.

Community metabarcoding reveals the relative role of environmental filtering and spatial processes in metacommunity dynamics of soil microarthropods across a mosaic of montane forests - Víctor Noguerales; Emmanouil Meramveliotakis; Adrián Castro‐Insua; Carmelo Andújar; Paula Arribas; Thomas J. Creedy; Isaac Overcast; Hélène Morlon; Brent C. Emerson; Alfried P. Vogler; Anna Papadopoulou (Molecular Ecology, 2023)
Disentangling the relative role of environmental filtering and spatial processes in driving metacommunity structure across mountainous regions remains challenging, as the way we quantify spatial connectivity in topographically and environmentally heterogeneous landscapes can influence our perception of which process predominates. More empirical data sets are required to account for taxon‐ and context‐dependency, but relevant research in understudied areas is often compromised by the taxonomic impediment. Here we used haplotype‐level community DNA metabarcoding, enabled by stringent filtering of amplicon sequence variants (ASVs), to characterize metacommunity structure of soil microarthropod assemblages across a mosaic of five forest habitats on the Troodos mountain range in Cyprus. We found similar β diversity patterns at ASV and species (OTU, operational taxonomic unit) levels, which pointed to a primary role of habitat filtering resulting in the existence of largely distinct metacommunities linked to different forest types. Within‐habitat turnover was correlated to topoclimatic heterogeneity, again emphasizing the role of environmental filtering. However, when integrating landscape matrix information for the highly fragmented Quercus alnifolia habitat, we also detected a major role of spatial isolation determined by patch connectivity, indicating that stochastic and niche‐based processes synergistically govern community assembly. Alpha diversity patterns varied between ASV and OTU levels, with OTU richness decreasing with elevation and ASV richness following a longitudinal gradient, potentially reflecting a decline of genetic diversity eastwards due to historical pressures. Our study demonstrates the utility of haplotype‐level community metabarcoding for characterizing metacommunity structure of complex assemblages and improving our understanding of biodiversity dynamics across mountainous landscapes worldwide.

Isolation drives species gains and losses of insect metacommunities over time in a mountaintop forest archipelago - Pedro Giovâni da Silva; Marina do Vale Beirão; Flávio Siqueira de Castro; Lucas Neves Perillo; Flávio Camarota; Ricardo R. C. Solar; Geraldo Wilson Fernandes; Frederico de Siqueira Neves (Journal of Biogeography, 2023)
Aim We evaluated the effects of forest island size, isolation and area in the landscape driving temporal changes of insect biodiversity in a mountaintop forest archipelago. We expected that (i) in smaller, less isolated forest islands, changes in insect composition are more prominent, primarily driven by gains over time; (ii) more forest in the landscape leads to increased gains of vagile species over time, regardless of forest island size and isolation; (iii) less vagile groups undergo heterogenisation, while highly vagile groups experience homogenisation due to differing dispersal capabilities. Location Espinhaço Range Biosphere Reserve, Brazil. Taxon Insects. Methods We used ants, dung beetles, bees, wasps and butterflies as study models to represent a gradient of low‐to‐high dispersal capability. We evaluated the colonisation‐ and extirpation‐resultant components of temporal β‐diversity using area‐ and isolation‐related variables as predictors. Results Distinct colonisation‐ and extirpation‐resultant homogenisation and heterogenisation processes are acting according to each insect group, likely due to different dispersal capabilities. Species losses dominated in ants, with widespread and rare species being lost. Butterflies gained species, represented mainly by widespread species, leading to an increased colonisation‐resultant homogenisation. Distance to neighbouring forest islands was the underlying predictor affecting the temporal β‐diversity of insect groups, and also species gains and losses but differently according to the survey period. Effects of the forest amount in the landscape increased the temporal β‐diversity of bees and butterflies but decreased that of ants, dung beetles and wasps. Main Conclusions These findings provide valuable biogeographic insights into the complex interactions between forest island characteristics, landscape attributes, and dispersal capabilities that shape the temporal dynamics of insect biodiversity on mountaintops. Conserving the forest amount in the landscape and keeping forest connectivity among forest islands are necessary because the temporal dynamics of local colonisation and extirpation can depend on the organisms' dispersal capability.

Long‐term observed changes of air temperature, relative humidity and vapour pressure deficit in Bolivia, 1950–2019 - B. Fernández‐Duque; S. M. Vicente‐Serrano; O. Maillard; F. Domínguez‐Castro; D. Peña‐Angulo; I. Noguera; C. Azorin‐Molina; A. El Kenawy (International Journal of Climatology, 2023)
This study analyzes the long‐term observed changes of mean (Tmean), maximum (Tmax) and minimum (Tmin) air temperatures, relative humidity (RH) and vapour pressure deficit (VPD) at different elevation ranges across Bolivia from 1950 to 2019. The linear trends in air temperature series present a significant increase, with no substantial seasonal or spatial differences. On an annual basis, RH exhibited a non‐significant decrease (−0.08% decade −1 ), while VPD showed a significant increase (0.01 hPa decade −1 ) ( p

Fishers' communication as a critical factor for tuna catches and potential benefits of traceability draws small-scale Fishers to program - Edison D. Macusi; Miko Mariz C. Castro; Ivy M. Nallos; Christine P. Perales (Ocean & Coastal Management, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Results from the Radiation Assessment Detector on the International Space Station: Part 3, combined results from the CPD and FND - C. Zeitlin; A.J. Castro; K.B. Beard; B.M. Hayes; M. Abdelmelek; D. Laramore; A.S. Johnson; N. Stoffle; R.F. Wimmer-Schweingruber; S. Löffler; R.R. Rios (Life Sciences in Space Research, 2023)

Results from the Radiation Assessment Detector on the International Space Station, Part 2: The fast neutron detector - C. Zeitlin; A.J. Castro; K.B. Beard; M. Abdelmelek; B.M. Hayes; A.S. Johnson; N. Stoffle; R.R. Rios; M.A. Leitgab; D.M. Hassler (Life Sciences in Space Research, 2023)

Results from the Radiation Assessment Detector on the International Space Station: Part 1, the Charged Particle Detector - C. Zeitlin; A.J. Castro; K.B. Beard; M. Abdelmelek; B.M. Hayes; A.S. Johnson; N. Stoffle; R.R. Rios (Life Sciences in Space Research, 2023)

Encephalic meningioangiomatosis in a dog with high-grade undefined glioma - Brenda O. Silveira; Stella M.P. de Melo; Fernanda G. Cony; Guilherme C. Serena; Vanessa de C. Pereira; Lucas T. de Castro; Vitória S. Wodzik; Marcele B. Bandinelli; Welden Panziera; Saulo P. Pavarini (Journal of Comparative Pathology, 2023)

Trophic ecology of common bottlenose dolphins in a pelagic insular environment inferred by stable isotopes - Ester Dias; Morgane Dromby; Rita Ferreira; Ágatha Gil; Raquel Tejerina; L. Filipe C. Castro; Massimiliano Rosso; Isabel Sousa-Pinto; Joel C. Hoffman; Maria A. Teodósio; Ana Dinis; Filipe Alves (Hydrobiologia, 2023)
The common bottlenose dolphin ( Tursiops truncatus ) is a top marine predator widely dispersed in coastal and pelagic habitats and with a generalist feeding behavior. Yet, information on the trophic ecology of animals inhabiting pelagic environments is still scarce. Using carbon (δ 13 C: 13 C/ 12 C) and nitrogen (δ 15 N: 15 N/ 14 N) stable isotope ratios, we identified and quantified the main groups of prey assimilated by bottlenose dolphins inhabiting an oceanic habitat (Madeira Island, East Atlantic). Bottlenose dolphins assimilated pelagic, schooling fish (such as blue jack mackerel, Trachurus picturatus ) and mesopelagic and demersal squids, which reinforces the pelagic dietary composition of insular/oceanic dolphins. Also, intra-seasonal differences were found in their stable isotope ratios, which suggest intraspecific variability in the feeding behavior among individuals living in the same area. Sex was not the main factor contributing to these differences, suggesting the lack of trophic niche segregation between adult males and females in this offshore environment. Nonetheless, further studies including different life stages and information on the ecophysiological requirements are necessary to disclose the factors responsible for the observed variability. This study showed that insular dolphins fed primarily on economically important pelagic prey, highlighting the need of developing management strategies that integrate conservation in fisheries plans.

Neuropathological and sociodemographic factors associated with the cortical amyloid load in aging and Alzheimer’s disease - Sayonara P. da Silva; Carla C. M. de Castro; Lívia N. Rabelo; Rovena C. Engelberth; Bernardino Fernández-Calvo; Felipe P. Fiuza (GeroScience, 2023)

Age, growth, and feeding of boarfish, Capros aper (Linnaeus, 1758) in the Southwest of the Iberian Peninsula - J. Castro-Gutiérrez; A. García-González; C. Rodríguez-García; Á. R. Domínguez-Bustos; R. Cabrera-Castro (Marine Biology Research, 2023)

Multi-analytical characterization of an oncoid from a high altitude hypersaline lake using techniques employed in the Mars2020 and Rosalind Franklin missions on Mars - J. Huidobro; J.M. Madariaga; D. Carrizo; J.L. Laserna; F. Rull; J. Martínez-Frías; J. Aramendia; L. Sánchez-García; L. García-Gómez; F.A. Vignale; M.E. Farías; M. Veneranda; et al. (Analytica Chimica Acta, 2023)

P21-13: Evaluation of neurotoxicity induced by new generation carbamates in domestic animals - S. M. Gómez Castro; G. A. Martínez González; A. M. Velázquez Sanchez; C. Cuenca Verde; E. Angeles; V. H. Vázquez Valadez; F. Alba Hurtado; M. G. Prado Ochoa (Toxicology Letters, 2023)

When non-target wildlife species and alien species both affect negatively to an artisanal fishery: the case of trammel net in the Alboran Sea - José C. Báez; Juan A. Camiñas; Raquel Aguilera; Jairo Castro-Gutiérrez; Raimundo Real (Reviews in Fish Biology and Fisheries, 2023)
In the Northern Alboran Sea, artisanal small-scale fisheries using trammel nets suffer economic losses, and local fishermen see their way-of-life endangered, due to interactions with wildlife species such as alien species and dolphins. On the one hand, the alien seaweed Rugulopteryx okamurae , which was first recorded in the Alboran Sea in 2015, has undergone an intensive expansion in the sub-region, monopolizing the available seabed, causing radical changes in the underwater seascape and clogging the trammel nets. On the other hand, the damage caused to the fishing nets by dolphin fish predation is an ancient problem worldwide, but it is intensifying in the last years. The main objective of this study is to understand the main environmental and technical conditions that favor damages of fishing trammel nets in the Alboran Sea, which entails an important loss of catchability, due to (i) the clogging of the artisanal fishing trammel nets by invasive seaweed, and (ii) the breaking of the nets by dolphin predation. Through close monitoring of fishermen in port, we obtained direct information of 548 sets. Our results indicate that approximately 30% of trammel sets suffered a damage due to unwanted interaction with alien seaweeds and dolphins. As seaweeds invasion is a global problem while dolphin-fishing gear interaction is more local, we concluded that only a large-scale management of exotic algae, together with the involvement of local fishermen, could solve the economic problems of this activity.

Varietal response to soybean target spot (Corynespora cassiicola) in the Brazilian Neotropical Savannah - Érica de Castro Costa; Justino J. Dias-Neto; Lincoln V. A. S. Bizerra; Nédio Tormen; Pierce A. Paul; Adalberto C. Café-Filho (Phytoparasitica, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Geometric morphometrics as a tool to identify Dasypodini osteoderms: Implications for the oldest records of Dasypus - Juan S. Salgado-Ahumada; Marcos D. Ercoli; Alicia Álvarez; Mariela C. Castro; Martín R. Ciancio (Journal of Mammalian Evolution, 2023)

Ficus sect. Americanae ser. Kinuppii: a ramiflorous group of Neotropical fig trees - Leandro C. Pederneiras; Henrique B. Zamengo; Angelo Danilo Plata-Castro; Sergio Romaniuc-Neto; Vidal De F. Mansano (Brittonia, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Characterization and photocatalytic performance of cement mortars with incorporation of TiO2 and mineral admixtures - Rancés Castillo Lara; Gustavo de Castro Xavier; Maria C. Canela; Juliana Alves Carvalho; Jonas Alexandre; Afonso Rangel Garcez de Azevedo (Environmental Science and Pollution Research, 2023)

Intakes of Unprocessed and Minimally Processed and Ultraprocessed Food Are Associated with Diet Quality in Female and Male Health Professionals in the United States: A Prospective Analysis - Sinara Laurini Rossato; Neha Khandpur; Chun-Han Lo; Stela Maris Jezus Castro; Jean Philippe Drouin-Chartier; Laura Sampson; Changzheng Yuan; Cristiane Murta-Nascimento; Maria Antonieta Carvalhaes; Carlos Augusto Monteiro; Qi Sun; Teresa T. Fung; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Habitat use of nesting female olive ridley turtles (Lepidochelys olivacea) inferred by stable isotopes in eggs - Pâmela Soares de Castro Echevenguá; Roberta Petitet; Jaqueline C. Castilhos; Fábio Lira C. Oliveira; Leandro Bugoni (Journal of Experimental Marine Biology and Ecology, 2023)

Decay of Skin-Specific Gene Modules in Pangolins - Bernardo Pinto; Raul Valente; Filipe Caramelo; Raquel Ruivo; L. Filipe C. Castro (Journal of Molecular Evolution, 2023)
The mammalian skin exhibits a rich spectrum of evolutionary adaptations. The pilosebaceous unit, composed of the hair shaft, follicle, and the sebaceous gland, is the most striking synapomorphy. The evolutionary diversification of mammals across different ecological niches was paralleled by the appearance of an ample variety of skin modifications. Pangolins, order Pholidota, exhibit keratin-derived scales, one of the most iconic skin appendages. This formidable armor is intended to serve as a deterrent against predators. Surprisingly, while pangolins have hair on their abdomens, the occurrence of sebaceous and sweat glands is contentious. Here, we explore various molecular modules of skin physiology in four pangolin genomes, including that of sebum production. We show that genes driving wax monoester formation, Awat1/2 , show patterns of inactivation in the stem pangolin branch, while the triacylglycerol synthesis gene Dgat2l6 seems independently eroded in the African and Asian clades. In contrast, Elovl3 implicated in the formation of specific neutral lipids required for skin barrier function is intact and expressed in the pangolin skin. An extended comparative analysis shows that genes involved in skin pathogen defense and structural integrity of keratinocyte layers also show inactivating mutations: associated with both ancestral and independent pseudogenization events. Finally, we deduce that the suggested absence of sweat glands is not paralleled by the inactivation of the ATP-binding cassette transporter Abcc11 , as previously described in Cetacea. Our findings reveal the sophisticated and complex history of gene retention and loss as key mechanisms in the evolution of the highly modified mammalian skin phenotypes.

Antibiotics reduce Pocillopora coral‐associated bacteria diversity, decrease holobiont oxygen consumption and activate immune gene expression - Michael T. Connelly; Grace Snyder; Ana M. Palacio‐Castro; Phillip R. Gillette; Andrew C. Baker; Nikki Traylor‐Knowles (Molecular Ecology, 2023)
Corals are important models for understanding invertebrate host–microbe interactions; however, to fully discern mechanisms involved in these relationships, experimental approaches for manipulating coral–bacteria associations are needed. Coral‐associated bacteria affect holobiont health via nutrient cycling, metabolic exchanges and pathogen exclusion, yet it is not fully understood how bacterial community shifts affect holobiont health and physiology. In this study, a combination of antibiotics (ampicillin, streptomycin and ciprofloxacin) was used to disrupt the bacterial communities of 14 colonies of the reef framework‐building corals Pocillopora meandrina and P . verrucosa, originally collected from Panama and hosting diverse algal symbionts (family Symbiodiniaceae ). Symbiodiniaceae photochemical efficiencies and holobiont oxygen consumption (as proxies for coral health) were measured throughout a 5‐day exposure. Antibiotics altered bacterial community composition and reduced alpha and beta diversity, however, several bacteria persisted, leading to the hypothesis that these bacteria are either antibiotics resistant or occupy internal niches that are shielded from antibiotics. While antibiotics did not affect Symbiodiniaceae photochemical efficiency, antibiotics‐treated corals had lower oxygen consumption rates. RNAseq revealed that antibiotics increased expression of Pocillopora immunity and stress response genes at the expense of cellular maintenance and metabolism functions. Together, these results reveal that antibiotic disruption of corals' native bacteria negatively impacts holobiont health by decreasing oxygen consumption and activating host immunity without directly impairing Symbiodiniaceae photosynthesis, underscoring the critical role of coral‐associated bacteria in holobiont health. They also provide a baseline for future experiments that manipulate Pocillopora corals' symbioses by first reducing the diversity and complexity of coral‐associated bacteria.

True insights or ticking boxes? Rapid assessment of rights‐based management in artisanal fisheries - Andrés M. Cisneros‐Montemayor; Eréndira Aceves‐Bueno; Sergio Amezcua‐Castro; Alejandra Apolinar‐Romo; Frida Cisneros‐Soberanis; Gabriela A. Cuevas‐Gómez; Ingrid C. Cruz‐León; Javier De La Cruz‐González; Alejandro Espinoza‐Tenorio; Alejandro García‐Lozano; Pedro C. González‐Espinosa; Miguel A. Cisneros‐Mata (Fisheries Management and Ecology, 2023)
Rights‐based fisheries management (RBFM) seeks to create market incentives to reduce competition, avoid overexploitation, and increase economic efficiency. Particularly for artisanal fisheries, however, assumptions of RBFM may not be met and its use needs to be carefully considered. This study applies an existing tool (SEASALT) to evaluate the strength of RBFM based on attributes of security, exclusivity, fish mortality, scale, responsibility, limitations, and transferability. Results for 17 fisheries in Mexico show a positive (nonsignificant) relationship between the strength of RBFM and stock status, and no effect on prices or landed value. Real‐world fisheries governance systems are much more complex than the simple linkages between attributes implied in SEASALT, but results highlight pre‐existing monitoring and enforcement capacity as essential for successful RBFM. Transitions to RBFM may strengthen this capacity, but likely cannot create it where it does not already exist. Based on our findings, RBFM strategies may benefit from group quotas with limited transferability to avoid negative social outcomes from consolidation or rent capture by intermediaries; this could potentially build on the latent capacity of traditional community associations common in many artisanal fisheries.

Machine learning performance comparison for main propulsive shafting systems alignment - Diego L. Magalhães; Dionísio Henrique C. de S.S. Martins; Brenno M. Castro; Luiz A. Vaz; Ulisses A. Monteiro; Ricardo H.R. Gutiérrez (Ocean Engineering, 2023)

Assessment of drying conditions for storage of a yeast-based decolorization solution for application in textile industrial wastewater treatment plants - Marta Mendes; Ana C. Cassoni; Soraia Alves; Patrícia Moreira; Paula ML. Castro; Manuela E. Pintado (Fungal Biology, 2023)

Immobilized mesoporous materials for carvacrol delivery to the germination and early growth of tomato plants (Solanum Lycopersicum) - Tzipatly A. Esquivel-Castro; Jorge Oliva; Vicente Rodríguez-González; Haret C. Rosu (Environmental Research, 2023)

Influence of plant growth regulators on in vitro biomass production and biosynthesis of cytotoxic Amaryllidaceae alkaloids in Caliphuria tenera Baker - Lina M. Trujillo Chacón; Hawer Leiva; Isabel C. Zapata Vahos; Dagoberto Castro Restrepo; Edison Osorio (Biocatalysis and Agricultural Biotechnology, 2023)

Water reclamation via membrane distillation applied to textile dye wastewater using a commercial poly(vinylidene fluoride) membrane - H. Ramlow; B. de Castro Santos; C. M. Tolentino Filho; C. D. K. Cavalcanti; R. A. F. Machado; C. Marangoni (International Journal of Environmental Science and Technology, 2023)

Prevalence of latent Mycobacterium tuberculosis infection in hematopoietic stem cell transplantation comparing tuberculin skin test and interferon-gamma release assay - Victor A C Castro-Lima; Ana Paula T Santos; Priscila T Musqueira; Natalya Z Maluf; Jéssica F Ramos; Lívia Mariano; Vanderson Rocha; Silvia F Costa (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Dissolved organic matter (DOM) characterization in subantarctic shallow lakes and beaver ponds - María V. Castro; Patricia E. García; María C. Maluendez Testoni; Patricia Rodríguez (Aquatic Sciences, 2023)

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Phylogenomics and taxon-rich phylogenies of new and historical specimens shed light on the systematics of Hypnea (Cystocloniaceae, Rhodophyta) - Priscila Barreto de Jesus; Goia de Mattos Lyra; Hongrui Zhang; Mutue Toyota Fujii; Fabio Nauer; José Marcos de Castro Nunes; Charles C. Davis; Mariana Cabral Oliveira (Molecular Phylogenetics and Evolution, 2023)

Review of tectonic inversion of sedimentary basins in NE and N Brazil: Analysis of mechanisms, timing and effects on structures and relief - Francisco H. Bezerra; Fernando O. Marques; David L. Vasconcelos; Dilce F. Rossetti; Aline C. Tavares; Rubson P. Maia; David L. de Castro; Francisco C.C. Nogueira; Reinhardt A. Fuck; Walter E. Medeiros (Journal of South American Earth Sciences, 2023)

Contribution of TGFß and of a cocktail of TGFß and the pro-inflammatory cytokines IL-1, IL- 6 and TNFα to the establishment of a fibrotic phenotype in endometrial fibroblasts of mares - Yat S. Wong; Pamela Poblete; Lidice Mendez; Ana C. Mancanares; Lleretny Rodriguez-Alvarez; Fernando E. Saravia; Fidel O. Castro (Journal of Equine Veterinary Science, 2023)

Reproductive performance of hair ewes and rams implanted with melatonin previous to the anestrus season in northwest Mexico - José C. Leyva-Corona; Norberto I. Angulo-Valenzuela; Blanca M. Laborin-Escalante; Miguel A. Gastelum-Delgado; N. Jahzeel Silva-Avila; Pablo Luna-Nevárez; Carlos E. Aragón-López; Miguel A. Sánchez-Castro; Marcela I. Morales-Pablos (Tropical Animal Health and Production, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Ovicidal and residual effects of Moringa oleifera leaf ethanol extract on Tetranychus merganser (Trombidiformes: Tetranychidae) - Julio C. Chacón-Hernández; Rapucel T. Q. Heinz-Castro (Journal of Plant Diseases and Protection, 2023)

Responses of ground-dwelling birds and mammals to local environmental variables and human pressure in an Amazonian protected area - Carlos R. Brocardo; Dian C. P. Rosa; Arlison B. Castro; Clarissa Rosa; Kelly Torralvo; Pedro Pequeno; William E. Magnusson; Rodrigo F. Fadini (European Journal of Wildlife Research, 2023)

Assessment of virus concentration methods for detecting SARS-CoV-2 IN wastewater - André V. C. Ribeiro; Camille F. Mannarino; Eduardo S. G. de Castro; Tatiana Prado; Fernando C. Ferreira; Tulio M. Fumian; Marize P. Miagostovich (Brazilian Journal of Microbiology, 2023)

Environmental and biotic filters interact to shape the coexistence of native and introduced bees in northern Patagonian forests - Pablo M. Vergara; Andrés Fierro; Mario A. Carvajal; Alberto J. Alaniz; Francisco Zorondo-Rodríguez; María C. Cifuentes; Sergio A. Castro (Agriculture, Ecosystems & Environment, 2023)

Quantification of Wood Biomass in an Area of Sustainable Annual Production in the Brazilian Semiarid Region Aiming at Generating Renewable Energy - R. C. Santos; F. G. C. Pareyn; C. P. S. Santos; D. Minini; S. M. G. Rocha; F. J. O. Souza; L. F. C. Cezario; A. F. Dias Júnior; R. V. O. Castro (BioEnergy Research, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Diet rather than temperature determines the biochemical composition of the ragworm Hediste diversicolor (OF Müller, 1776) (Annelida: Nereidae) - Arne M. Malzahn; Andrea Villena-Rodríguez; Óscar Monroig; Åsmund Johansen; L. Filipe C. Castro; Juan C. Navarro; Andreas Hagemann (Aquaculture, 2023)

Spring plankton energy content by size classes in two contrasting environments of a high latitude ecosystem: The Beagle Channel - Daniel O. Bruno; Constanza Valencia-Carrasco; María A. Paci; Ezequiel Leonarduzzi; Leonardo Castro; Luciana Riccialdelli; Clara M. Iachetti; Andreana Cadaillon; Ricardo Giesecke; Irene R. Schloss; Carla F. Berghoff; Jacobo Martín; et al. (Journal of Marine Systems, 2023)

Authentication/discrimination, identification and quantification of cinnamon adulterants using NIR spectroscopy and different chemometric tools: A tutorial to deal with counterfeit samples - Rafael C. Castro; David S.M. Ribeiro; João L.M. Santos; Ricardo N.M.J. Páscoa (Food Control, 2023)

Quercetin decreases cardiac hypertrophic mediators and maladaptive coronary arterial remodeling in renovascular hypertensive rats without improving cardiac function - Eduardo Vieira da Rocha; Francisco Falchetti; Laena Pernomian; Marcela M. Blascke de Mello; Juliana M. Parente; Renato C. Nogueira; Beatriz Q. Gomes; Giuliana Bertozi; Jessica M. Sanches-Lopes; José Eduardo Tanus-Santos; Michele M. Castro (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Genetic population structure of Pseudoplatystoma corruscans (Siluriformes: Pimelodidae) and evidence of temporal variation in structure - Eva C. Rueda; Carolina B. Machado; Veronica Castro; Alline Braga‐Silva; Guillermo Ojeda; Facundo Vargas; Gisela Loretán; Patricia D. Freitas; Pedro M. Galetti; Guillermo Ortí (Journal of Fish Biology, 2023)
Surubim ( Pseudoplatystoma corruscans , Pimelodidae) are migratory catfish native to the rivers in the La Plata and São Francisco basins. They are piscivores that attain considerable body sizes and are a valuable economic resource. Surubim exhibits extensive migrations during its life cycle that may affect the population structure at vast geographic scales. The authors examined the genetic diversity and population genetic structure of P. corruscans using microsatellite markers from a comprehensive sampling of 260 individuals from the Upper and Lower Paraná River. They identified two well‐differentiated genetic clusters corresponding to a natural geographic barrier historically separating Upper and Lower Paraná regions. They also demonstrated temporal variation in population genetic structure at a site in Lower Paraná close to the confluence with the Paraguay River, most likely explained by the influx of migrant fishes at certain times of the year.

Metabolic profiling by LC-DAD-MS, FTIR, NMR and CE-UV of polyphenols with potential against skin pigmentation disorder - Isac H. Cordeiro; Nerilson M. Lima; Elaine C. Scherrer; Gabriela P. Carli; Teresinha de Jesus A. S. Andrade; Sandra B. R. Castro; Marcone A. L. de Oliveira; Caio Cesar S. Alves; Alessandra P. Carli (Natural Product Research, 2023)

Assessment of vapor pressure deficit variability and trends in Spain and possible connections with soil moisture - I. Noguera; S.M. Vicente-Serrano; D. Peña-Angulo; F. Domínguez-Castro; C. Juez; M. Tomás-Burguera; J. Lorenzo-Lacruz; C. Azorin-Molina; A. Halifa-Marín; B. Fernández-Duque; A. El Kenawy (Atmospheric Research, 2023)

First Confirmed Record of the Smalltooth Sand Tiger, Odontapis Ferox, in Galicia (NW Spain) - Gonzalo Mucientes; Nair Vilas-Arrondo; Giulia Secci-Petretto; Uxía Vázquez; Xabier Pin; Alfredo López; L. Filipe C. Castro; Elsa Froufe (Thalassas: An International Journal of Marine Sciences, 2023)
The smalltooth sand tiger shark Odontaspis ferox (Risso, 1810) appears to have an extensive and fragmented distribution in tropical and warm-temperate worldwide oceans. One female of O. ferox was caught and released by a small-scale fishery vessel in Ría de Arousa (Northwest of Spain), subsequently stranded still alive on the coast (42°33’18.4"N 8°49’18.3"O) after a few hours. The individual (336 cm total length, weight ~ 300 kg) was identified based on a collection of features including the characteristic dentition, body morphology and by molecular assignment. This is the first confirmed record of O. ferox in Galician waters. This finding complements the knowledge of the geographic distribution and occurrence of this rare and sparse species in the Northeastern Atlantic.

Invasive Aspergillosis in Patients with Acute Leukemia: Comparison Between Acute Myeloid and Acute Lymphoid Leukemia - Arnaldo L. Colombo; Maria Daniela Bergamasco; Simone A. Nouér; Paulo de Tarso Oliveira e Castro; Alessandro C. Pasqualotto; Flavio de Queiroz-Telles; Edson Abdala; Jessica F. Ramos; Diego R. Falci; Marcio Nucci (Mycopathologia, 2023)

Combined coagulation-electrocoagulation process using biocoagulant from the Opuntia ficus-indica for treatment of cheese whey wastewater - Hugo G. J. Pacheco; Naysha Y. Elguera; Midwar Ancco; Antonio E. L. F. Castro; Maria E. B. Meza; Vitor C. Almeida (Environmental Monitoring and Assessment, 2023)

Effects of different management strategies on long‐term trends of Australian threatened and near‐threatened mammals - Ayesha I. T. Tulloch; Micha V. Jackson; Elisa Bayraktarov; Alexander R. Carey; Diego F. Correa‐Gomez; Michael Driessen; Ian C. Gynther; Mel Hardie; Katherine Moseby; Liana Joseph; Harriet Preece; Andrés Felipe Suarez‐Castro; et al. (Conservation Biology, 2023)
Monitoring is critical to assess management effectiveness, but broadscale systematic assessments of monitoring to evaluate and improve recovery efforts are lacking. We compiled 1808 time series from 71 threatened and near‐threatened terrestrial and volant mammal species and subspecies in Australia (48% of all threatened mammal taxa) to compare relative trends of populations subject to different management strategies. We adapted the Living Planet Index to develop the Threatened Species Index for Australian Mammals and track aggregate trends for all sampled threatened mammal populations and for small ( 5500 g) from 2000 to 2017. Unmanaged populations (42 taxa) declined by 63% on average; unmanaged small mammals exhibited the greatest declines (96%). Populations of 17 taxa in havens (islands and fenced areas that excluded or eliminated introduced red foxes [ Vulpes vulpes ] and domestic cats [ Felis catus ]) increased by 680%. Outside havens, populations undergoing sustained predator baiting initially declined by 75% but subsequently increased to 47% of their abundance in 2000. At sites where predators were not excluded or baited but other actions (e.g., fire management, introduced herbivore control) occurred, populations of small and medium mammals declined faster, but large mammals declined more slowly, than unmanaged populations. Only 13% of taxa had data for both unmanaged and managed populations; index comparisons for this subset showed that taxa with populations increasing inside havens declined outside havens but taxa with populations subject to predator baiting outside havens declined more slowly than populations with no management and then increased, whereas unmanaged populations continued to decline. More comprehensive and improved monitoring (particularly encompassing poorly represented management actions and taxonomic groups like bats and small mammals) is required to understand whether and where management has worked. Improved implementation of management for threats other than predation is critical to recover Australia's threatened mammals.

A roadmap for the conservation of freshwater mussels in Europe - Ronaldo Sousa; Tadeusz Zając; Dariusz Halabowski; Olga V. Aksenova; Yulia V. Bespalaya; Francisco Carvalho; Paulo Castro; Karel Douda; Janine P. da Silva; Noé Ferreira‐Rodríguez; Juergen Geist; Clemens Gumpinger; et al. (Conservation Biology, 2023)
Europe has a long history of human pressure on freshwater ecosystems. As pressure continues to grow and new threats emerge, there is an urgent need for conservation of freshwater biodiversity and its ecosystem services. However, whilst some taxonomic groups, mainly vertebrates, have received a disproportionate amount of attention and funds, other groups remain largely off the public and scientific radar. Freshwater mussels (Bivalvia, Unionida) are an alarming example of this conservation bias and here we point out six conceptual areas that need immediate and long‐term attention: knowledge, threats, socioeconomics, conservation, governance and education. The proposed roadmap aims to advance research, policy and education by identifying the most pressing priorities for the short‐ and long‐term conservation of freshwater mussels across Europe.

Evaluation of lead exposition length on the liver and intestinal histoarchitecture of eared dove (Zenaida auriculata) - Verónica P. Filippa; Emilce L. Tabares; Ana C. Castro-Guijarro; Juan G. Chediack; Fabricio D. Cid (Environmental Science and Pollution Research, 2023)

Proximity to residential and workplace pesticides application and the risk of progression of Parkinson's diseases in Central California - Shiwen Li; Beate Ritz; Yufan Gong; Myles Cockburn; Aline Duarte Folle; Irish Del Rosario; Yu Yu; Keren Zhang; Emily Castro; Adrienne M. Keener; Jeff Bronstein; Kimberly C. Paul (Science of The Total Environment, 2023)

Changing risk of arboviral emergence in Catalonia due to higher probability of autochthonous outbreaks - L. López; C. Dommar; A. San José; L. Meyers; S. Fox; L. Castro; X. Rodó (Ecological Modelling, 2023)

Losartan impairs HTR-8/SVneo trophoblast migration through inhibition of angiotensin II-induced pro-inflammatory profile in human endometrial stromal cells - Rosario Macchi; Agustina D. Sotelo; Andrea C. Parrado; Luciana S. Salaverry; Guillermo A. Blanco; Marisa S. Castro; Estela B. Rey-Roldán; Andrea M. Canellada (Toxicology and Applied Pharmacology, 2023)

Effects of the COVID-19 pandemic on the behavior and physical health of dogs in Rio de Janeiro state: Reflections on the quality of life of dogs and their owners - Luana de Sousa Ribeiro; Guilherme M. Soares; Emmanuel Arnold; Maria C. Nobre e Castro (Journal of Veterinary Behavior, 2023)

Population dynamics and movements of Atlantic tarpon, Megalops atlanticus, in the Parnaíba Delta Protected Area, Brazil: challenges for local fishery management planning - Cezar A. F. Fernandes; Francisca E. A. Cunha; Carlos E. L. S. Silva; Alan C. S. Araújo; Rafael L. Pereira; Daniel F. Viana; Werlanne M. S. Magalhães; M. A. P. Gondolo; Daniel M. P. de Castro; Aaron Adams; Jiangang Luo; Jerald S. Ault; et al. (Environmental Biology of Fishes, 2023)

Influence of pigeon pea (Cajanus cajan) on oviposition behaviour of Diceraeus melacanthus stink bug, an important pest of soybean and maize crops in South America - M. Borges; M. F. F. Michereff; R. A. Laumann; G. T. Santana; B. S. Castro; C. C. Silva; M. C. Blassioli-Moraes (Arthropod-Plant Interactions, 2023)

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Short and long-term exposure to the pesticides fipronil and 2,4-D: Effects on behavior and life history of Daphnia magna - Raquel A. Moreira; Curro Polo-Castellano; Andrea Cordero-de-Castro; Mariana A. Dias; Thandy J.S. Pinto; Cassiana C. Montagner; Evaldo L.G. Espíndola; Julián Blasco; Cristiano V.M. Araújo (Chemosphere, 2023)

Bioaccessibility of phenolic compounds in L. varieties and Nied. after gastrointestinal digestion - Alba C. Durán-Castañeda; Alicia P. Cardenas-Castro; Jara Pérez-Jiménez; Ana M. Pérez-Carvajal; Jorge A. Sánchez-Burgos; Raquel Mateos; Sonia G. Sáyago-Ayerdi (Food Chemistry, 2023)

Risk scores’ performance and their impact on operative decision-making in left-sided endocarditis: a cohort study - A. Fernández-Cisneros; M. Hernández-Meneses; J. Llopis; E. Sandoval; D. Pereda; J. Alcocer; C. Barriuso; M. Castellá; J. Ambrosioni; J. M. Pericàs; B. Vidal; C. Falces; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
The accuracy of contemporary risk scores in predicting perioperative mortality in infective endocarditis (IE) remains controversial. The aim is to evaluate the performance of existent mortality risk scores for cardiovascular surgery in IE and the impact on operability at high-risk thresholds. A single-center retrospective review of adult patients diagnosed with acute left-sided IE undergoing surgery from May 2014 to August 2019 ( n = 142) was done. Individualized risk calculation was obtained according to the available mortality risk scores: EuroScore I and II, PALSUSE, Risk-E, Costa, De Feo-Cotrufo, AEPEI, STS-risk, STS-IE, APORTEI, and ICE-PCS scores. A cross-validation analysis was performed on the score with the best area under the curve (AUC). The 30-day survival was 96.5% (95%CI 91–98%). The score with worse area under the curve (AUC = 0.6) was the STS-IE score, while the higher was for the RISK-E score (AUC = 0.89). The AUC of the majority of risk scores suggested acceptable performance; however, statistically significant differences in expected versus observed mortalities were common. The cross-validation analysis showed that a large number of survivors (> 75%) would not have been operated if arbitrary high-risk threshold estimates had been used to deny surgery. The observed mortality in our cohort is significantly lower than is predicted by contemporary risk scores. Despite the reasonable numeric performance of the analyzed scores, their utility in judging the operability of a given patient remains questionable, as demonstrated in the cross-validation analysis. Future guidelines may advise that denial of surgery should only follow a highly experienced Endocarditis Team evaluation.

Influence of the Cape Angle and Flow Speed on Eddy Formation and Detachment: Experimental Results and Comparison with North Brazil Current Eddies - Raúl C. Cruz-Gómez; Julio Salcedo-Castro (Ocean Science Journal, 2022)

Marine turtle hotspots in the Gulf of Mexico and Mesoamerican Reef: Strengthening management and preparedness - Eduardo Cuevas; María de los Angeles Liceaga-Correa; Abigail Uribe-Martínez; Sandra A. Gallegos-Fernández; Félix Moncada-Gavilán; Raúl J. González-Díaz-Mirón; Melania C. López-Castro; Vicente Guzmán-Hernández; Martha López (Frontiers in Marine Science, 2022)
Marine turtles are of the highest ecological concern in terms of conservation and restoration programs and marine territorial ordering. Marine resource-extracting industries have severe negative impacts on their populations and their habitats. Thus, private industries and decision makers require the best and most robust spatially explicit scientific knowledge for a sustainable and responsible operation and government administration. Therefore, the identification of marine turtle hotspots is a strategic milestone for ecosystem management and an integral ecological knowledge about any region. We identified and delimited marine turtle hotspots in the Gulf of Mexico and Mesoamerican Reef. We analyzed satellite-tracked data of 178 individuals belonging to four marine turtle species. We used Brownian bridge movement models to estimate space use surfaces and map algebra to weight and merge layers of multiple species, life stages, and movement phases. The Yucatan Peninsula and central Veracruz in Mexico, along with the Florida Keys and Louisiana coast in the US, harbor the primary hotspots where marine turtles aggregate. We defined four primary hotspots used for migration in the western Gulf of Mexico, around the Yucatan Peninsula, a northern route following the Loop Current, and a southern one towards Gorda Bank, Central America. This study is the largest assessment of marine turtle hotspots in Mexico and Cuba and supports strategies for reinforcing regional management actions for their conservation, as well as a stronger response and preparedness for tackling anthropic threats to these species. This milestone contributes to extending the knowledge frontiers about these species to a new level.

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Microbiome signatures in Acropora cervicornis are associated with genotypic resistance to elevated nutrients and heat stress - Ana M. Palacio-Castro; Stephanie M. Rosales; Caroline E. Dennison; Andrew C. Baker (Coral Reefs, 2022)

Biological, morphological, and molecular characterization of the baculovirus PlxyMNPV_LBIV-11, and its virulence towards Plutella xylostella, Trichoplusia ni, and Spodoptera frugiperda larvae - Sandra Yazmín Jiménez-Hernández; Jonatan C. Rangel-Núñez; Jorge E. Ibarra; Ma Cristina Del Rincón-Castro (Archives of Microbiology, 2022)

The Technical and Economic Feasibility of the CENTEC Floating Offshore Wind Platform - Almudena Filgueira-Vizoso; Laura Castro-Santos; David Cordal Iglesias; Félix Puime-Guillén; Isabel Lamas-Galdo; Ana Isabel García-Diez; Emre Uzunoglu; Hugo Díaz; C. Guedes Soares (Journal of Marine Science and Engineering, 2022)
This paper defines a methodology for the economic feasibility analysis of a floating offshore wind farm composed of tensioned leg platforms, which are part of the EU ARCWIND research project. In this context, the phases and subphases of its life-cycle process are considered to deal with aspects such as bathymetry, characteristics of the platforms, distance from the farm to shore, distance from the farm to port and offshore wind speed. All the costs and other external parameters such as capital cost, electric tariff, interest rate, percentage of financing and corporate tax have been analysed to calculate the internal rate of return, net present value, discounted pay-back period and levelized cost of energy of the farm. This work studies a farm composed of TLP offshore wind platforms designed by CENTEC and located at Ribadeo in Spain. Results indicate the costs and the economic feasibility of this platform for deep waters. They indicate that the platform is economically feasible for the location selected.

Performance of Sentinel-2 SAFER ET model for daily and seasonal estimation of grapevine water consumption - Anderson L. S. Safre; Ayman Nassar; Alfonso Torres-Rua; Mayhar Aboutalebi; João C. C. Saad; Rodrigo L. Manzione; Antonio Heriberto de Castro Teixeira; John H. Prueger; Lynn G. McKee; Joseph G. Alfieri; Lawrence E. Hipps; Hector Nieto; et al. (Irrigation Science, 2022)

Improving the spatiotemporal resolution of remotely sensed ET information for water management through Landsat, Sentinel-2, ECOSTRESS and VIIRS data fusion - Jie Xue; Martha C. Anderson; Feng Gao; Christopher Hain; Kyle R. Knipper; Yun Yang; William P. Kustas; Yang Yang; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; Joseph G. Alfieri; et al. (Irrigation Science, 2022)
Robust information on consumptive water use (evapotranspiration, ET) derived from remote sensing can significantly benefit water decision-making in agriculture, informing irrigation schedules and water management plans over extended regions. To be of optimal utility for operational usage, these remote sensing ET data should be generated at the sub-field spatial resolution and daily-to-weekly timesteps commensurate with the scales of water management activities. However, current methods for field-scale ET retrieval based on thermal infrared (TIR) imaging, a valuable diagnostic of canopy stress and surface moisture status, are limited by the temporal revisit of available medium-resolution (100 m or finer) thermal satellite sensors. This study investigates the efficacy of a data fusion method for combining information from multiple medium-resolution sensors toward generating high spatiotemporal resolution ET products for water management. TIR data from Landsat and ECOSTRESS (both at ~ 100-m native resolution), and VIIRS (375-m native) are sharpened to a common 30-m grid using surface reflectance data from the Harmonized Landsat-Sentinel dataset. Periodic 30-m ET retrievals from these combined thermal data sources are fused with daily retrievals from unsharpened VIIRS to generate daily, 30-m ET image timeseries. The accuracy of this mapping method is tested over several irrigated cropping systems in the Central Valley of California in comparison with flux tower observations, including measurements over irrigated vineyards collected in the GRAPEX campaign. Results demonstrate the operational value added by the augmented TIR sensor suite compared to Landsat alone, in terms of capturing daily ET variability and reduced latency for real-time applications. The method also provides means for incorporating new sources of imaging from future planned thermal missions, further improving our ability to map rapid changes in crop water use at field scales.

Common dolphin (Delphinus delphis) fission–fusion dynamics in the south coast of Portugal - Joana Castro; Cláudia Faustino; André Cid; Alicia Quirin; Fábio L. Matos; Rui Rosa; Heidi C. Pearson (Behavioral Ecology and Sociobiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Morita–Baylis–Hillman adducts derived from thymol: synthesis, in silico studies and biological activity against Giardia lamblia - Francisco J. S. Xavier; Andressa B. Lira; Gabriel C. Verissimo; Fernanda S. de S. Saraiva; Abrahão A. de Oliveira Filho; Elaine M. de Souza-Fagundes; Margareth de F. F. M. Diniz; Maria A. Gomes; Aleff C. Castro; Fábio P. L. Silva; Claudio G. Lima-Junior; Mário L. A. A. Vasconcellos (Molecular Diversity, 2022)

Attitudes of Filipino parents of children with Down syndrome on noninvasive prenatal testing - Leniza G. de Castro-Hamoy; Ma-am Joy R. Tumulak; Maria Stephanie Fay S. Cagayan; Peter A. Sy; Nona Rachel C. Mira; Mercy Y. Laurino (Journal of Community Genetics, 2022)

A zebrafish pparγ gene deletion reveals a protein kinase network associated with defective lipid metabolism - Yan Zhao; L. Filipe C. Castro; Óscar Monroig; Xiaojuan Cao; Yonghua Sun; Jian Gao (Functional & Integrative Genomics, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Predicting in vitro fertilization success in the Brazilian public health system: a machine learning approach - Nayara C. N. Barreto; Giulia Z. Castro; Ramon G. Pereira; Francisco A. N. Pereira; Fernando M. Reis; Wagner M. Junior; Ines K. D. Cavallo; Karina B. Gomes (Medical & Biological Engineering & Computing, 2022)

Development of a composite material between bacterial cellulose and E crassipes, for the treatment of water contaminated by chromium (VI) - U. F. C. Sayago; Y. P. Castro (International Journal of Environmental Science and Technology, 2022)

Mapping Lioz Limestone in Monuments at Rio de Janeiro, Brazil - Amanda G. S. Mozer; Nuria F. Castro; Kátia L. Mansur; Roberto Carlos C. Ribeiro (Geoheritage, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Polyethylene microplastics and substrate availability can affect emergence responses of the freshwater insect Chironomus sancticaroli - Gleyson B. Castro; Aline C. Bernegossi; Mayara C. Felipe; Allan P. Ogura; Mara R. de Lima e Silva; Juliano J. Corbi (Ecotoxicology, 2022)

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Ambio fit for the 2020s - Erik Andersson; Wiebren J. Boonstra; Maricela de la Torre Castro; Alice C. Hughes; Ulrik Ilstedt; Arne Jernelöv; Bengt-Gunnar Jonsson; Zahra Kalantari; Carina Keskitalo; Emma Kritzberg; Thomas Kätterer; Jeffrey A. McNeely; et al. (Ambio, 2022)

Statistical Approaches Link Sources of Sediment Contamination in Subtropical Reservoirs to Land Use: an Example from the Itupararanga Reservoir (Brazil) - Daniele Frascareli; Erik Sartori Jeunon Gontijo; Sheila Cardoso Silva; Darllene Silveira Melo; Carolina de Castro Bueno; Vanessa C. Simonetti; Johannes A. C. Barth; Viviane Moschini Carlos; André Henrique Rosa; Kurt Friese (Water, Air, & Soil Pollution, 2022)

Effect of calving season on the parameters and components of the lactation curve in Holstein dairy cows managed in a semi-desert climate - Ricardo Zamorano-Algandar; Juan F. Medrano; Milton G. Thomas; R. Mark Enns; Scott E. Speidel; Miguel A. Sánchez-Castro; Guillermo Luna-Nevárez; José C. Leyva-Corona; Pablo Luna-Nevárez (Tropical Animal Health and Production, 2022)

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Evapotranspiration trends and variability in southeastern South America: The roles of land‐cover change and precipitation variability - Romina C. Ruscica; Anna A. Sörensson; Leandro B. Diaz; Carolina Vera; Aline Castro; Phillip Papastefanou; Anja Rammig; Luiz F. C. Rezende; Boris Sakschewski; Kirsten Thonicke; Nicolas Viovy; Celso von Randow (International Journal of Climatology, 2022)
Southeastern South America is subject to considerable precipitation variability on seasonal to decadal timescales and has undergone very heavy land‐cover changes (LCCs) since the middle of the past century. The influence of local LCC and precipitation as drivers of regional evapotranspiration (ET) long‐term trends and variability remains largely unknown in the region. Here, ensembles of stand‐alone dynamic global vegetation models (DGVMs) with different atmospheric forcings are used to disentangle the influence of those two drivers on austral summer ET from 1950 to 2010. This paper examines the influence of both the El Niño‐Southern Oscillation (ENSO) and the dipole‐like first‐mode of southeastern South American precipitation variability (EOF1) on regional ET. We found that in the lower La Plata Basin, ET was driven by precipitation variability and showed a positive summer trend. Moreover, the region showed marked seasonal anomalies during El Niño and La Niña summers but mainly during EOF1 phases. On the contrary, in the upper La Plata Basin, LCCs forced the negative summer ET trend and particularly reduced the summer anomalies of the late 1990s, a period of ENSO and EOF1‐positive phases. In the South Atlantic Convergence Zone region, the high ET uncertainty across ensemble members impeded finding robust results, which highlights the importance of using multiple DGVMs and atmospheric forcings instead of relying on single model/forcing results.

Assessing Caffeine and Linear Alkylbenzene Sulfonate Effects on Molting and Reproduction of Daphnia magna by Quantitative and Qualitative Approaches - Mara R. de Lima e Silva; Aline C. Bernegossi; Gleyson B. Castro; Allan P. Ogura; Juliano J. Corbi; Mayara C. Felipe (Water, Air, & Soil Pollution, 2022)

Primary and Secondary Compression of a Colombian Volcanic Ash Soil - Ayda Catalina Galvis-Castro; Julio E. Colmenares; Juan C. Garcia-Leal (Geotechnical and Geological Engineering, 2022)

Bioaerosol vertical fungal spores profile in Minas Gerais State, Brazil - Ana Paula Mendes Emygdio; Cristiane Degobbi; Federico Carotenuto; Dulcilena de Matos Castro e Silva; Thaysla Beluco Quintino; Rafael Henrique de Souza Zanetti; Mauricio C. Mantoani; Solana Meneghel Boschilia; Lara Chaves Carvalho Guerra; Pedro Leite da Silva Dias; Cindy E. Morris; Fábio Luiz Teixeira Gonçalves (Aerobiologia, 2022)

Impact of Dietary Condensed Tannins and Haemonchus contortus Infection in Growing Sheep: Effects on Nutrient Intake, Digestibility, and the Retention of Energy and Nitrogen - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; L. A. Sarmiento-Franco; J. Ventura-Cordero; P. G. González-Pech; J. J. Vargas-Magaña; J. F. J. Torres-Acosta (Acta Parasitologica, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Megabenthic communities distributed in the outer margins of the Yucatan shelf and their relationship to environmental variables - J Rubio-Polania; D Torruco-Gómez; A González-Solís; R Rodríguez-Canul; M Améndola-Pimenta; I Mariño-Tapia; J Herrera-Silveira; F Árcega-Cabrera; V Ceja-Moreno; J Romo-Alvarado; I Lizarraga-Castro; C Gutiérrez-Solís (Marine Biology Research, 2022)

Ant diversity studies in Brazil: an overview of the myrmecological research in a megadiverse country - F. A. Schmidt; C. R. Ribas; R. M. Feitosa; F. B. Baccaro; A. C. M. de Queiroz; T. G. Sobrinho; Y. Quinet; K. S. Carvalho; T. Izzo; M. S. de Castro Morini; A. Nogueira; H. M. Torezan-Silingardi; et al. (Insectes Sociaux, 2022)

Efficacy of high-intensity interval- or continuous aerobic-training on insulin resistance and muscle function in adults with metabolic syndrome: a clinical trial - Jaime Gallo-Villegas; Leonardo A. Castro-Valencia; Laura Pérez; Daniel Restrepo; Oscar Guerrero; Sergio Cardona; Yeliana L. Sánchez; Manuela Yepes-Calderón; Luis H. Valbuena; Miguel Peña; Andrés F. Milán; Maria C. Trillos-Almanza; et al. (European Journal of Applied Physiology, 2022)

Determination of Fipronil and Fipronil-Sulfone in Surface Waters of the Guandu River Basin by High-Performance Liquid Chromatography with Mass Spectrometry - Thais P. Ferreira; Glauco F. Bauerfeldt; Rosane N. Castro; Viviane S. Magalhães; Melina C. C. Alves; Fábio B. Scott; Yara P. Cid (Bulletin of Environmental Contamination and Toxicology, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A regionalized IO-model to value seasonal recreational ecosystem services in a mountain National Park in Spain - Víctor Martin Barroso; Mónica de Castro-Pardo; Pascual Fernández Martínez; João C. Azevedo (Journal of Mountain Science, 2022)

Resistance exercise intervention on muscular strength and power, and functional capacity in acute hospitalized older adults: a systematic review and meta-analysis of 2498 patients in 7 randomized clinical trials - Marcelo A. S. Carneiro; Cristiane M. C. Franco; Alan L. Silva; Pâmela Castro-e-Souza; Gabriel Kunevaliki; Mikel Izquierdo; Edilson S. Cyrino; Camila S. Padilha (GeroScience, 2021)

Association between high proviral load, cognitive impairment, and white matter brain lesions in HTLV-1-infected individuals - Rosangela Souza Kalil; Isabelle Vasconcellos; Carolina Rosadas; Andrea Cony; Dulcino P. Lima; Cassia C. Alves Gonçalves; Everton Batista; Maria Fernanda Grassi; Bernardo Galvão-Castro; Graham P.Taylor; Marzia Puccioni-Sohler (Journal of NeuroVirology, 2021)

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

In vitro and in vivo evaluation of anti-inflammatory activity and free radical scavenging potential of leaves extract from Anadenanthera colubrina - Oswaldo Cardoso Junior; Nerilson M. Lima; Marcos G. A. Silva; Virgilio B. Aguiar; Gabriela P. Carli; Elaine C. Scherrer; Sandra B. R. Castro; Caio C. Souza Alves; Marcone A. L. Oliveira; Alessandra P. Carli (Natural Product Research, 2021)

A network-based approach to identify protein kinases critical for regulating srebf1 in lipid deposition causing obesity - Shouxiang Sun; Xiaojuan Cao; L. Filipe C. Castro; Óscar Monroig; Jian Gao (Functional & Integrative Genomics, 2021)

Evaluation of Bacillus spp. isolates as potential biocontrol agents against charcoal rot caused by Macrophomina phaseolina on common bean - Yolani de J. Bojórquez-Armenta; Guadalupe A. Mora-Romero; Melina López-Meyer; Ignacio E. Maldonado-Mendoza; Claudia Castro-Martínez; Cecilia de los A. Romero-Urías; Jesús D. Cordero-Ramírez; Juan C. Martínez-Álvarez (Journal of General Plant Pathology, 2021)

Functional or Vestigial? The Genomics of the Pineal Gland in Xenarthra - Raul Valente; Filipe Alves; Isabel Sousa-Pinto; Raquel Ruivo; L. Filipe C. Castro (Journal of Molecular Evolution, 2021)

Effect of salinity on growth, survival, and serum osmolality of red snapper, Lutjanus campechanus - Harsha S. C. Galkanda-Arachchige; Robert P. Davis; Sidra Nazeer; Leonardo Ibarra-Castro; D. Allen Davis (Fish Physiology and Biochemistry, 2021)

Variation in susceptibility among three Caribbean coral species and their algal symbionts indicates the threatened staghorn coral, Acropora cervicornis, is particularly susceptible to elevated nutrients and heat stress - Ana M. Palacio-Castro; Caroline E. Dennison; Stephanie M. Rosales; Andrew C. Baker (Coral Reefs, 2021)

Activation of C–C motif chemokine receptor 2 modulates testicular macrophages number, steroidogenesis, and spermatogenesis progression - A. F. A. Figueiredo; N. T. Wnuk; C. P. Vieira; M. F. F. Gonçalves; M. R. G. Brener; A. B. Diniz; M. M. Antunes; H. M. Castro-Oliveira; G. B. Menezes; G. M. J. Costa (Cell and Tissue Research, 2021)

Amazonia as the Origin and Diversification Area of Didelphidae (Mammalia: Metatheria), and a Review of the Fossil Record of the Clade - Mariela C. Castro; Murilo J. Dahur; Gabriel S. Ferreira (Journal of Mammalian Evolution, 2021)
Didelphidae is the largest New World radiation of marsupials, and is mostly represented by arboreal, small- to medium-sized taxa that inhabit tropical and/or subtropical forests. The group originated and remained isolated in South America for millions of years, until the formation of the Isthmus of Panama. In this study, we present the first reconstruction of the biogeographic history of Didelphidae including all major clades, based on parametric models and stratified analyses over time. We also compiled all the pre-Quaternary fossil records of the group, and contrasted these data to our biogeographic inferences, as well as to major environmental events that occurred in the South American Cenozoic. Our results indicate the relevance of Amazonia in the early diversification of Didelphidae, including the divergence of the major clades traditionally ranked as subfamilies and tribes. Cladogeneses in other areas started in the late Miocene, an interval of intense shifts, especially in the northern portion of Andes and Amazon Basin. Occupation of other areas continued through the Pliocene, but few were only colonized in Quaternary times. The comparison between the biogeographic inference and the fossil records highlights some further steps towards better understanding the spatiotemporal evolution of the clade. Finally, our results stress that the early history of didelphids is obscured by the lack of Paleogene fossils, which are still to be unearthed from low-latitude deposits of South America.

Exhumation of an anatectic complex by channel flow and extrusion tectonics: structural and metamorphic evidence from the Porto–Viseu Metamorphic Belt, Central-Iberian Zone - T. Bento dos Santos; J. F. Rodrigues; P. Castro; B. Cotrim; I. Pereira; J. A. Ferreira; C. Meireles; N. Ferreira; P. Ferreira; A. Ribeiro; F. Guimarães (International Journal of Earth Sciences, 2021)

Counting Enchytraeus crypticus Juveniles in Chronic Exposures: An Alternative Method for Ecotoxicity Studies Using Tropical Artificial Soil - Mayara C. Felipe; Aline C. Bernegossi; Fernanda R. Pinheiro; Gleyson B. Castro; Lidia Moura; Marcelo Zaiat; Juliano J. Corbi (Bulletin of Environmental Contamination and Toxicology, 2021)

Selection of rhizobacteria isolates with bioherbicide potential against Palmer amaranth (Amarathus palmeri S. Wats.) - Candelario Verdugo-Navarrete; Ignacio E. Maldonado-Mendoza; Claudia Castro-Martínez; Karla Y. Leyva-Madrigal; Juan C. Martínez-Álvarez (Brazilian Journal of Microbiology, 2021)

Three new species of Trattinnickia. Studies in Neotropical Burseraceae XXX - Maria Fatima F. de Melo; Douglas C. Daly; João Ubiratam M. dos Santos; Karoline Castro da Silva (Brittonia, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Association of NFκβ, TNFα, IL-6, IL-1β, and LPL Polymorphisms with Type 2 Diabetes Mellitus and Biochemical Parameters in a Mexican Population - O. C. Martínez-Ramírez; D. A. Salazar-Piña; Ramos-García M. de Lorena; C. Castro-Hernández; L. Casas-Ávila; J. A. Portillo-Jacobo; J. Rubio (Biochemical Genetics, 2021)

Detection of porcine circovirus type 2 (PCV2) in the Philippines and the complexity of PCV2-associated disease diagnosis - Agnes dela Cruz; Chiara Palmieri; Rachel Azul; Christina Legaspi; Suzan Lola; Tamsin S. Barnes; Christopher R. Parke; Conny Turni; John I. Alawneh; Augusto S. Baluyut; Voltaire G. Basinang; Jose E. David; et al. (Tropical Animal Health and Production, 2021)

Be quick or be dead: high temperatures reduce Aedes aegypti (Diptera: Culicidae) larval development time and pyriproxyfen larvicide efficiency in laboratory conditions - Lidia Moura; Barbara L. de Nadai; Aline C. Bernegossi; Mayara C. Felipe; Gleyson B. Castro; Juliano J. Corbi (International Journal of Tropical Insect Science, 2021)

Molecular characterization of KPC-2-producing Klebsiella pneumoniae ST258 isolated from bovine mastitis - Jesús Silva-Sanchez; Humberto Barrios-Camacho; Emmanuel Hernández-Rodriguez; Josefina Duran-Bedolla; Alejandro Sanchez-Perez; Luary C. Martínez-Chavarría; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro; Ulises Garza-Ramos (Brazilian Journal of Microbiology, 2021)

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

Biotechnological Potential of Eugenol and Thymol Derivatives Against Staphylococcus aureus from Bovine Mastitis - Daiana O. S. Nunes; Rafaelle Vinturelle; Francislene J. Martins; Thiago F. dos Santos; Alessandra Leda Valverde; Carlos Magno R. Ribeiro; Helena C. Castro; Evelize Folly (Current Microbiology, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Cytotoxicity of glucoevatromonoside alone and in combination with chemotherapy drugs and their effects on Na+,K+-ATPase and ion channels on lung cancer cells - Naira Fernanda Zanchett Schneider; Danusa Menegaz; Andre Luiz Andreotti Dagostin; Lara Persich; Sayonarah C. Rocha; Ana Carolina Pacheco Ramos; Vanessa Faria Cortes; Carlos Frederico Leite Fontes; Rodrigo Maia de Pádua; Jennifer Munkert; Wolfgang Kreis; Fernão Castro Braga; et al. (Molecular and Cellular Biochemistry, 2021)

Miconia albicans and Curcuma longa herbal medicines positively modulate joint pain, function and inflammation in patients with osteoarthritis: a clinical study - Thiago P. O. Gomes; Jonathan I. N. Souza; Lucas C. Somerlate; Vanessa A. Mendonça; Nerilson M. Lima; Gabriela P. Carli; Sandra B. R. Castro; Teresinha de Jesus A. S. Andrade; João V. L. Dias; Marcone A. L. Oliveira; Caio C. S. Alves; Alessandra P. Carli (Inflammopharmacology, 2021)

Pathological characteristics, survival, and risk of breast cancer associated with estrogen and xenobiotic metabolism polymorphisms in Mexican women with breast cancer - O. C. Martínez-Ramírez; C. Castro-Hernández; R. Pérez-Morales; L. Casas-Ávila; Ramos-García M. de Lorena; A. Salazar-Piña; J. Rubio (Cancer Causes & Control, 2021)

Application of rhamnolipid surfactant for remediation of toxic metals of long- and short-term contamination sites - C. S. C. Lopes; D. B. Teixeira; B. F. Braz; R. E. Santelli; L. V. A. de Castilho; J. G. C. Gomez; R. P. V. Castro; L. Seldin; D. M. G. Freire (International Journal of Environmental Science and Technology, 2021)

Correction to: Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Bacterial Nanocellulose Mulch as a Potential Greener Alternative for Urban Gardening in the Small-Scale Food Production of Onion Plants - L. Cárcamo; S. Sierra; M. Osorio; J. Velásquez-Cock; L. Vélez-Acosta; C. Gómez-Hoyos; C. Castro; R. Zuluaga; P. Gañán (Agricultural Research, 2021)

Effects of Environmental Variables and Habitat Integrity on the Structure of the Aquatic Insect Communities of Streams in the Cerrado-Caatinga Ecotone in Northeastern Brazil - E. R. Castro; D. S. Veras; G. S. Lustosa; C. A. S. Azevêdo; L. Juen (Neotropical Entomology, 2021)

Recent developments combining ensemble smoother and deep generative networks for facies history matching - Smith W. A. Canchumuni; Jose D. B. Castro; Júlia Potratz; Alexandre A. Emerick; Marco Aurélio C. Pacheco (Computational Geosciences, 2021)

Silicic conduits as supersized tuffisites: Clastogenic influences on shifting eruption styles at Cordón Caulle volcano (Chile) - C. Ian Schipper; Jonathan M. Castro; Ben M. Kennedy; Hugh Tuffen; Jack Whattam; Fabian B. Wadsworth; Rebecca Paisley; Rebecca H. Fitzgerald; Emma Rhodes; Lauren N. Schaefer; Paul A. Ashwell; Pablo Forte; et al. (Bulletin of Volcanology, 2021)

Implications of the temporal variations of geoid heights over South American vertical reference frames - Henry D. Montecino Castro; Silvio Rogerio C. de Freitas (Arabian Journal of Geosciences, 2021)

Hepatitis C treatment outcome in former or current intravenous drug users coinfected with HIV, with or without directly observed therapy - R. Sarmento-Castro; J. Méndez; A. Horta; C. Gonçalves; O. Vasconcelos; J. Seabra; M. Abreu; M. J. Gonçalves; M. J. Santos; A. P. Tavares (Infectious Diseases, 2021)

Cubic-to-inverted micellar and the cubic-to-hexagonal-to-micellar transitions on phytantriol-based cubosomes induced by solvents - Mayra C. G. Lotierzo; Bruna R. Casadei; Raphael Dias de Castro; Barbara Malheiros; Leandro R. S. Barbosa (Drug Delivery and Translational Research, 2020)

Seismic stratigraphy of a deep water basin in the Brazilian equatorial margin: the eastern portion of Potiguar Basin and Touros High - Júlia C. L. G. Fonseca; Helenice Vital; Yoe A. R. Perez; David L. Castro; André G. Aquino da Silva; Moab P. Gomes (Geo-Marine Letters, 2020)

First Spatial Distribution Analysis of Male Sea Turtles in the Southern Gulf of Mexico - Eduardo Cuevas; Nathan F. Putman; Abigail Uribe-Martínez; Melania C. López-Castro; Vicente Guzmán-Hernández; Sandra A. Gallegos-Fernández; María de los Ángeles Liceaga-Correa; Jorge A. Trujillo-Córdova; Raúl de Jesús González-Díaz-Mirón; Ana Negrete-Phillipe; Héctor H. Acosta-Sánchez; Rosa C. Martínez-Portugal; et al. (Frontiers in Marine Science, 2020)
In the Gulf of Mexico, the bulk of published studies for sea turtles have focused on northern (United States) waters where economic resources are centered, with fewer studies in the southern portion of the basin, resulting in significant knowledge gaps in these underrepresented areas. Similarly, publications on adult sea turtles are dominated by research on females that come ashore to nest and can be readily studied (e.g., through the collection of biological samples and the application of satellite-telemetry devices), whereas information on adult male sea turtles is scarce. The goal of this paper is to begin filling these knowledge gaps by synthesizing available data on adult male sea turtles in the southern Gulf of Mexico. We used satellite-telemetry, boat- and drone-based surveys, and stranding records combined with ocean circulation modeling to better understand the spatial distribution of male loggerhead ( Caretta caretta ), green ( Chelonia mydas ), hawksbill ( Eretmochelys imbricata ), and Kemp’s ridley ( Lepidochelys kempii ) sea turtles in the southern Gulf of Mexico. These spatially explicit analyses will provide context for opportunistically collected data on male sea turtles and better contribute to the management and restoration of sea turtle populations that use the Gulf of Mexico. Moreover, this synthesis can serve as a launching point for directed studies on male sea turtles in this region.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Losing Genes: The Evolutionary Remodeling of Cetacea Skin - Gonçalo Espregueira Themudo; Luís Q. Alves; André M. Machado; Mónica Lopes-Marques; Rute R. da Fonseca; Miguel Fonseca; Raquel Ruivo; L. Filipe C. Castro (Frontiers in Marine Science, 2020)

Update on the use of Pristina longiseta Ehrenberg, 1828 (Oligochaeta: Naididae) as a toxicity test organism - Gleyson B. Castro; Fernanda R. Pinheiro; Mayara C. Felipe; Aline C. Bernegossi; Douglas Girolli; Guilherme R. Gorni; Juliano J. Corbi (Environmental Science and Pollution Research, 2020)

Effects of Polyethylene Microplastics on Freshwater Oligochaeta Allonais inaequalis (Stephenson, 1911) Under Conventional and Stressful Exposures - Gleyson B. Castro; Aline C. Bernegossi; Fernanda R. Pinheiro; Mayara C. Felipe; Juliano J. Corbi (Water, Air, & Soil Pollution, 2020)

Retrospective study of porcine circovirus 3 (PCV3) in swine tissue from Brazil (1967–2018) - I. L. F. Rodrigues; A. C. M. Cruz; A. E. Souza; F. B. Knackfuss; C. H. C. Costa; R. L. Silveira; T. X. Castro (Brazilian Journal of Microbiology, 2020)

Latitudinal patterns of species diversity on South American rocky shores: Local processes lead to contrasting trends in regional and local species diversity - Juan J. Cruz‐Motta; Patricia Miloslavich; Edlin Guerra‐Castro; Alejandra Hernández‐Agreda; Cesar Herrera; Francisco Barros; Sergio A. Navarrete; Roger D. Sepúlveda; Tim M. Glasby; Gregorio Bigatti; Maritza Cardenas‐Calle; Pedro B. M. Carneiro; et al. (Journal of Biogeography, 2020)
Aim We evaluated whether patterns of species diversity (α, β and γ) of rocky shore assemblages followed latitudinal gradients (i.e. LDGs) along the South American coasts, and tested hypotheses related to potential processes sustaining or disrupting the expected LDG pattern at various spatial scales. Location Coasts of South America. Taxon Macroalgae and sessile/slow‐moving macrofauna on intertidal rocky shores. Methods We evaluated changes in species composition across 143 sites. The degree of replacement and loss of species at different spatial scales (i.e. coasts, regions and sites) were estimated to help distinguish among ecological, historical and evolutionary hypotheses for explaining LDGs. Furthermore, components of diversity and taxonomic distinctness were measured, and variability in these measures was decomposed using analysis of covariance. Finally, we examined relationships between diversity and a suite of environmental and anthropogenic variables to identify potential mechanisms that may be responsible for the reported spatial relationships. Results Species composition varied with latitude, and this variability was relatively consistent on both coasts. At all spatial scales, replacement of species was the dominant phenomenon (>95%), rather than loss in the total number of species ( Main conclusions Species diversity of South American rocky shores followed, with interruptions, LDGs. The trend of those LDGs, however, depended on the scale and metric used to describe diversity. It is proposed that patterns of LDGs at various scales are not the result of a single overarching process but are strongly influenced by local and regional processes. Although the most evident environmental gradient was the decrease in SST towards the south, it was demonstrated that regional and local environmental variables were also important for understanding the increase in regional β‐diversity towards the tropics.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Oceanographic Determinants of the Abundance of Common Dolphins (Delphinus delphis) in the South of Portugal - Joana Castro; Ana Couto; Francisco O. Borges; André Cid; Marina I. Laborde; Heidi C. Pearson; Rui Rosa (Oceans, 2020)
Off mainland Portugal, the common dolphin (Delphinus delphis) is the most sighted cetacean, although information on this species is limited. The Atlantic coast of Southern Portugal is characterized by an intense wind-driven upwelling, creating ideal conditions for common dolphins. Using data collected aboard whale-watching boats (1929 sightings and 4548 h effort during 2010–2014), this study aims to understand the relationships between abundance rates (AR) of dolphins of different age classes (adults, juveniles, calves and newborns) and oceanographic [chlorophyll a (Chl-a) and sea surface temperature (SST)] variables. Over 70% of the groups contained immature animals. The AR of adults was negatively related with Chl-a, but not related to SST values. The AR of juveniles was positively related with SST. For calves and newborns, although the relationship between SST and AR is similar to that observed for juveniles, the effect could not be distinguished from zero. There was no relationship between Chl-a levels and the AR of juveniles, calves and newborns. These results corroborate previous findings that common dolphins tend to occur in highly productive areas demonstrating linkages between their abundance and oceanographic variables, and that this region may be a potential nursery ground.

Nutritional evaluation and human health-promoting potential of compounds biosynthesized by native microalgae from the Peruvian Amazon - Marianela Cobos; Sheyla Pérez; Janeth Braga; Gabriel Vargas-Arana; Leenin Flores; Jae D. Paredes; J. Dylan Maddox; Jorge L. Marapara; Juan C. Castro (World Journal of Microbiology and Biotechnology, 2020)

Heat-related mortality at the beginning of the twenty-first century in Rio de Janeiro, Brazil - João L. Geirinhas; Ana Russo; Renata Libonati; Ricardo M. Trigo; Lucas C. O. Castro; Leonardo F. Peres; Mônica de Avelar F. M. Magalhães; Baltazar Nunes (International Journal of Biometeorology, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

The use of an Allonais inaequalis reproduction test as an ecotoxicological bioassay - M. C. Felipe; A. C. Bernegossi; G. B. Castro; F. R. Pinheiro; B. L. Nadai; B. N. Cardoso-Silva; J. J. Corbi (Ecotoxicology, 2020)

Leuconostoc mesenteroides subsp. mesenteroides SD23 Prevents Metabolic Dysfunction Associated with High-Fat Diet–Induced Obesity in Male Mice - Diana C. Castro-Rodríguez; Luis A. Reyes-Castro; Claudia C. Vega; Guadalupe L. Rodríguez-González; Jorge Yáñez-Fernández; Elena Zambrano (Probiotics and Antimicrobial Proteins, 2020)

New Aspects of VEGF, GABA, and Glutamate Signaling in the Neocortex of Human Temporal Lobe Pharmacoresistant Epilepsy Revealed by RT-qPCR Arrays - Rubén D. Castro-Torres; Mónica E. Ureña-Guerrero; Lilia M. Morales-Chacón; Lourdes Lorigados-Pedre; Bárbara Estupiñan-Díaz; Luisa Rocha; Sandra Orozco-Suárez; Martha C. Rivera-Cervantes; Mario Alonso-Vanegas; Carlos Beas-Zárate (Journal of Molecular Neuroscience, 2020)

Biosorption of Rhodamine B Using a Low-Cost Biosorbent Prepared from Inactivated Aspergillus oryzae Cells: Kinetic, Equilibrium and Thermodynamic Studies - Flávia H. M. Souza; Vitória F. C. Leme; Giovanna O. B. Costa; Karine C. Castro; Tania R. Giraldi; Grazielle S. S. Andrade (Water, Air, & Soil Pollution, 2020)

Global patterns of reproductive and cytotype diversity in an invasive clonal plant - Victoria Ferrero; Luis Navarro; Sílvia Castro; João Loureiro; José M. Sánchez; Gastón O. Carvallo; Spencer C. H. Barrett (Biological Invasions, 2020)

Role of VEGFs in metabolic disorders - M. di Somma; M. Vliora; E. Grillo; B. Castro; E. Dakou; W. Schaafsma; J. Vanparijs; M. Corsini; C. Ravelli; E. Sakellariou; S. Mitola (Angiogenesis, 2020)

Effects of the Invasion of Honey Locust (Gleditsia triacanthos L.) on Macrophytes and Algae of Pampean Streams (Argentina) - C. Vilches; A. M. Torremorell; M. C. Rodriguez Castro; A. Giorgi (Wetlands, 2020)

Minimal stories in Southeast Buenos Aires grasslands: carabid beetle biodiversity throughout an urban-rural gradient - Adela V. Castro; Darío P. Porrini; Sebastián Lupo; Armando C. Cicchino (Urban Ecosystems, 2020)

Molluscan genomics: the road so far and the way forward - André Gomes-dos-Santos; Manuel Lopes-Lima; L. Filipe C. Castro; Elsa Froufe (Hydrobiologia, 2020)

Shiga Toxin-Producing and Enteroaggregative Escherichia coli in Animal, Foods, and Humans: Pathogenicity Mechanisms, Detection Methods, and Epidemiology - Ana C. C. Paletta; Vinicius S. Castro; Carlos A. Conte-Junior (Current Microbiology, 2020)

A comparison of machine and deep-learning algorithms applied to multisource data for a subtropical forest area classification - C. Sothe; C. M. De Almeida; M. B. Schimalski; V. Liesenberg; L. E. C. La Rosa; J. D. B. Castro; R. Q. Feitosa (International Journal of Remote Sensing, 2020)

Combined effects of land-use intensification and plant invasion on native communities - C. Gutiérrez-Cánovas; D. Sánchez-Fernández; P. González-Moreno; E. Mateos-Naranjo; P. Castro-Díez; M. Vilà (Oecologia, 2020)

Chemical and mineral comparison of fossil insect cuticles from Crato Konservat Lagerstätte, Lower Cretaceous of Brazil - Francisco Irineudo Bezerra; João H. da Silva; Emílio de Castro Miguel; Alexandre R. Paschoal; Daniel R. Nascimento; Paulo T. C. Freire; Bartolomeu C. Viana; Márcio Mendes (Journal of Iberian Geology, 2020)

Assessment of yield gaps on global grazed‐only permanent pasture using climate binning - Leonardo A. Monteiro; Andrew M. Allee; Eleanor E. Campbell; Lee R. Lynd; Johnny R. Soares; Deepak Jaiswal; Julianne de Castro Oliveira; Murilo dos Santos Vianna; Ashley E. Morishige; Gleyce K. D. A. Figueiredo; Rubens A. C. Lamparelli; Nathaniel D. Mueller; et al. (Global Change Biology, 2020)
To meet rising demands for agricultural products, existing agricultural lands must either produce more or expand in area. Yield gaps (YGs)—the difference between current and potential yield of agricultural systems—indicate the ability to increase output while holding land area constant. Here, we assess YGs in global grazed‐only permanent pasture lands using a climate binning approach. We create a snapshot of circa 2000 empirical yields for meat and milk production from cattle, sheep, and goats by sorting pastures into climate bins defined by total annual precipitation and growing degree‐days. We then estimate YGs from intra‐bin yield comparisons. We evaluate YG patterns across three FAO definitions of grazed livestock agroecosystems (arid, humid, and temperate), and groups of animal production systems that vary in animal types and animal products. For all subcategories of grazed‐only permanent pasture assessed, we find potential to increase productivity several‐fold over current levels. However, because productivity of grazed pasture systems is generally low, even large relative increases in yield translated to small absolute gains in global protein production. In our dataset, milk‐focused production systems were found to be seven times as productive as meat‐focused production systems regardless of animal type, while cattle were four times as productive as sheep and goats regardless of animal output type. Sustainable intensification of pasture is most promising for local development, where large relative increases in production can substantially increase incomes or “spare” large amounts of land for other uses. Our results motivate the need for further studies to target agroecological and economic limitations on productivity to improve YG estimates and identify sustainable pathways toward intensification.

Mangifera indica L. as Airborne Metal Biomonitor for Regions of the State of Espírito Santo (Brazil) - Leonardo Z. de Castro; Thaís R. B. da Silva; Silas N. Ronchi; Adriana A. T. Guimarães; Hermínio A. Nalini Júnior; Juliano S. Ribeiro; Silvia C. G. Coutinho; Elisangela F. Pimentel; Denise C. Endringer (Water, Air, & Soil Pollution, 2020)

Removal of Zn and Cd from Overlying Water by Mangrove Sediments: Testing the Effects of Sediment Resuspension/Redeposition Events - K. N. Suzuki; R. J. M. Castro; M. N. Sondermann; E. C. Machado; A. B. Bellido; R. T. Lopes; W. Machado (Water, Air, & Soil Pollution, 2020)

Biogeography, habitat transitions and hybridization in a radiation of South American silverside fishes revealed by mitochondrial and genomic RAD data - Lily C. Hughes; Yamila P. Cardoso; Julie A. Sommer; Roberto Cifuentes; Mariela Cuello; Gustavo M. Somoza; Mariano González‐Castro; Luiz R. Malabarba; Victor Cussac; Evelyn M. Habit; Ricardo Betancur‐R.; Guillermo Ortí (Molecular Ecology, 2020)
Rivers and lake systems in the southern cone of South America have been widely influenced by historical glaciations, carrying important implications for the evolution of aquatic organisms, including prompting transitions between marine and freshwater habitats and by triggering hybridization among incipient species via waterway connectivity and stream capture events. Silverside fishes ( Odontesthes ) in the region comprise a radiation of 19 marine and freshwater species that have been hypothesized on the basis of morphological or mitochondrial DNA data to have either transitioned repeatedly into continental waters from the sea or colonized marine habitats following freshwater diversification. New double digest restriction‐site associated DNA data presented here provide a robust framework to investigate the biogeographical history of and habitat transitions in Odontesthes . We show that Odontesthes silversides originally diversified in the Pacific but independently colonized the Atlantic three times, producing three independent marine‐to‐freshwater transitions. Our results also indicate recent introgression of marine mitochondrial haplotypes into two freshwater clades, with more recurring instances of hybridization among Atlantic‐ versus Pacific‐slope species. In Pacific freshwater drainages, hybridization with a marine species appears to be geographically isolated and may be related to glaciation events. Substantial structural differences of estuarine gradients between these two geographical areas may have influenced the frequency, intensity and evolutionary effects of hybridization events.

Economic Feasibility of Floating Offshore Wind Farms in the North of Spain - Laura Castro-Santos; A. Rute Bento; Dina Silva; Nadia Salvação; C. Guedes Soares (Journal of Marine Science and Engineering, 2020)
This paper assesses the economic feasibility of offshore wind farms installed in deep waters considering their internal rate of return (IRR), net present value (NPV), and levelized cost of energy (LCOE). The method proposed has three phases: geographic phase, economic phase, and restrictions phase. The purpose of the geographic step is to obtain the input values, which will be used in the economic phase. Then, the economic parameters are calculated considering the inputs provided previously. Finally, the bathymetric restriction is added to the economic maps. The case study focused on the Cantabric and North-Atlantic coasts of Spain, areas that have not been studied previously in economic terms regarding floating offshore wind technology. Moreover, several alternatives have been considered, taking into account the type of floating offshore wind structure and the electric tariff. Results indicate which is the best floating offshore wind structure with respect to LCOE, IRR, and NPV, and where is the best location for the connection of a floating offshore wind farm in the region selected.

Root proteome and metabolome reveal a high nutritional dependency of aluminium in Qualea grandiflora Mart. (Vochysiaceae) - Natalia F. Cury; Renata C. C. Silva; Michelle S. F. Andre; Wagner Fontes; Carlos A. O. Ricart; Mariana S. Castro; Conceição E. S. Silveira; Thomas C. R. Williams; Marcelo V. de Sousa; Luiz A. R. Pereira (Plant and Soil, 2020)

Role of inflammation, oxidative stress, and autonomic nervous system activation during the development of right and left cardiac remodeling in experimental pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; A. C. Bahr; P. Türck; A. L. de Castro; C. Campos-Carraro; F. Visioli; T. R. Fernandes-Piedras; K. R. Casali; C. M. C. Scassola; G. Baldo; et al. (Molecular and Cellular Biochemistry, 2020)

Evidence of a landlocked reproducing population of the marine pejerrey Odontesthes argentinensis (Actinopterygii; Atherinopsidae) - Darío C. Colautti; Leandro Miranda; Mariano Gonzalez‐Castro; Vanina Villanova; Carlos A. Strüssmann; Miguel Mancini; Tomas Maiztegui; Gustavo Berasain; Ricardo Hattori; Fabian Grosman; Pablo Sanzano; Ismael Lozano; et al. (Journal of Fish Biology, 2020)
In South America, the order Atheriniformes includes the monophyletic genus Odontesthes with 20 species that inhabit freshwater, estuarine and coastal environments. Pejerrey Odontesthes argentinensis is widely distributed in coastal and estuarine areas of the Atlantic Ocean and is known to foray into estuaries of river systems, particularly in conditions of elevated salinity. However, to our knowledge, a landlocked self‐sustaining population has never been recorded. In this study, we examined the pejerrey population of Salada de Pedro Luro Lake (south‐east of Buenos Aires Province, Argentina) to clarify its taxonomic identity. An integrative taxonomic analysis based on traditional meristic, landmark‐based morphometrics and genetic techniques suggests that the Salada de Pedro Luro pejerrey population represents a novel case of physiological and morphological adaptation of a marine pejerrey species to a landlocked environment and emphasises the environmental plasticity of this group of fishes.

Lime and gypsum combination improves crop and forage yields and estimated meat production and revenue in a variable charge tropical soil - Carlos A. C. Crusciol; Rubia R. Marques; Antonio C. A. Carmeis Filho; Rogério P. Soratto; Claudio H. M. Costa; Jayme Ferrari Neto; Gustavo S. A. Castro; Cristiano M. Pariz; André M. Castilhos; Alan J. Franzluebbers (Nutrient Cycling in Agroecosystems, 2019)

Criollo goats limit their grass intake in the early morning suggesting a prophylactic self-medication behaviour in a heterogeneous vegetation - R. A. Torres-Fajardo; P. G. González-Pech; C. A. Sandoval-Castro; J. Ventura-Cordero; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

The worm burden of tracer kids and lambs browsing heterogeneous vegetation is influenced by strata harvested and not total dry matter intake or plant life form - P. R. Jaimez-Rodríguez; P. G. González-Pech; J. Ventura-Cordero; D. R. B. Brito; L. M. Costa-Júnior; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

Neurocognitive Impairment in mdx Mice - Clarissa M. Comim; Letícia Ventura; Viviane Freiberger; Paula Dias; Daiane Bragagnolo; Matheus L. Dutra; Ricardo A. Amaral; Ana Lucia S. Camargo-Fagundes; Patrícia A. Reis; Hugo C. Castro-Faria-Neto; Mariz Vainzof; Maria I. Rosa (Molecular Neurobiology, 2019)

Identification of Susceptible Rainfall-Induced Landslide Areas Based on Field Experiments and Multi-criteria Analysis in GIS Environment: A Proposal for Non-inventoried Areas - Leonardo C. Assis; Maria L. Calijuri; Mateus M. Salvador; Jackeline de S. Castro; Carolina F. Carvalho (Geotechnical and Geological Engineering, 2019)

Identification and characterization of atypical enteropathogenic and Shiga toxin-producing Escherichia coli isolated from ground beef and poultry breast purchased in Botucatu, Brazil - Rodrigo H. S. Tanabe; Melissa A. Vieira; Noelle A. B. Mariano; Regiane C. B. Dias; Rafael Ventin da Silva; Caroline M. Castro; Luis F. dos Santos; Carlos H. Camargo; Ricardo S. Yamatogi; Vera L. M. Rall; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2019)

Drought decreases incorporation of recent plant photosynthate into soil food webs regardless of their trophic complexity - Mathilde Chomel; Jocelyn M. Lavallee; Nil Alvarez‐Segura; Francisco de Castro; Jennifer M. Rhymes; Tancredi Caruso; Franciska T. de Vries; Elizabeth M. Baggs; Mark C. Emmerson; Richard D. Bardgett; David Johnson (Global Change Biology, 2019)
Theory suggests that more complex food webs promote stability and can buffer the effects of perturbations, such as drought, on soil organisms and ecosystem functions. Here, we tested experimentally how soil food web trophic complexity modulates the response to drought of soil functions related to carbon cycling and the capture and transfer below‐ground of recent photosynthate by plants. We constructed experimental systems comprising soil communities with one, two or three trophic levels (microorganisms, detritivores and predators) and subjected them to drought. We investigated how food web trophic complexity in interaction with drought influenced litter decomposition, soil CO 2 efflux, mycorrhizal colonization, fungal production, microbial communities and soil fauna biomass. Plants were pulse‐labelled after the drought with 13 C‐CO 2 to quantify the capture of recent photosynthate and its transfer below‐ground. Overall, our results show that drought and soil food web trophic complexity do not interact to affect soil functions and microbial community composition, but act independently, with an overall stronger effect of drought. After drought, the net uptake of 13 C by plants was reduced and its retention in plant biomass was greater, leading to a strong decrease in carbon transfer below‐ground. Although food web trophic complexity influenced the biomass of Collembola and fungal hyphal length, 13 C enrichment and the net transfer of carbon from plant shoots to microbes and soil CO 2 efflux were not affected significantly by varying the number of trophic groups. Our results indicate that drought has a strong effect on above‐ground–below‐ground linkages by reducing the flow of recent photosynthate. Our results emphasize the sensitivity of the critical pathway of recent photosynthate transfer from plants to soil organisms to a drought perturbation, and show that these effects may not be mitigated by the trophic complexity of soil communities, at least at the level manipulated in this experiment.

Using Large-Eddy Simulation and Wind-Tunnel Data to Investigate Peak-to-Mean Concentration Ratios in an Urban Environment - J. M. Santos; N. C. Reis; I. P. Castro; E. V. Goulart; Z. T. Xie (Boundary-Layer Meteorology, 2019)

Comparative populational study of Lepidonotothen larseni and L. nudifrons (Teleostei: Nototheniidae) from the Antarctic Peninsula and the South Shetland Islands, Antarctica - Mariana Y. Deli Antoni; Sergio M. Delpiani; Mariano González-Castro; Gabriela E. Blasina; María C. Spath; Gabriela E. Depiani; Fernando Y. Ashikaga; Vanessa P. Cruz; Claudio Oliveira; Juan M. Díaz de Astarloa (Polar Biology, 2019)

Genetic diversity of Fusarium mexicanum, causal agent of mango and big-leaf mahogany malformation in Mexico - Ricardo Santillán-Mendoza; Daniela Pineda-Vaca; Sylvia P. Fernández-Pavía; Juan C. Montero-Castro; Erica M. Goss; Julieta Benítez-Malvido; Gerardo Rodríguez-Alvarado (Molecular Biology Reports, 2019)

Biostimulation of crude oil-polluted soils: influence of initial physicochemical and biological characteristics of soil - C. Calvo; A. Rodríguez-Calvo; T. Robledo-Mahón; M. Manzanera; J. González-López; E. Aranda; G. A. Silva-Castro (International Journal of Environmental Science and Technology, 2019)

Gymnopodium floribundum fodder as a model for the in vivo evaluation of nutraceutical value against Haemonchus contortus - F. A. Méndez-Ortiz; C. A. Sandoval-Castro; J. Ventura-Cordero; L. A. Sarmiento-Franco; R. H. Santos-Ricalde; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Physiological responses of the red algae Gracilaria caudata (Gracilariales) and Laurencia catarinensis (Ceramiales) following treatment with a commercial extract of the brown alga Ascophyllum nodosum (AMPEP) - Jonatas M. C. Souza; Júlia Z. Castro; Alan T. Critchley; Nair S. Yokoya (Journal of Applied Phycology, 2019)

The Impact of the Right Coronary Artery Geometric Parameters on Hemodynamic Performance - N. Pinho; L. C. Sousa; C. F. Castro; C. C. António; M. Carvalho; W. Ferreira; R. Ladeiras-Lopes; N. D. Ferreira; P. Braga; N. Bettencourt; S. I. S. Pinto (Cardiovascular Engineering and Technology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Speciation and periodic restricted environments. The case of genus Ononis L. (subsections Natrix and Viscosae ) - I. Castro; J. Rocha; C. Costa; G. Costa; R. Ramírez-Rodríguez; F. Amich; V. Carnide; A. L. Crespí (Plant Biosystems, 2019)

Vaginal biota number is smaller in tailed than docked hair ewes (Ovis aries), but is not affected by copulation - A. Orihuela; A. Fierros-García; C. Hallal-Calleros; S. R. Robles-Castro; R. Ungerfeld (Tropical Animal Health and Production, 2019)

Convergent inactivation of the skin-specific C-C motif chemokine ligand 27 in mammalian evolution - Mónica Lopes-Marques; Luís Q. Alves; Miguel M. Fonseca; Giulia Secci-Petretto; André M. Machado; Raquel Ruivo; L. Filipe C. Castro (Immunogenetics, 2019)

Two New Species of the Spittlebug Genus Ocoaxo Fennah (Hemiptera: Cercopidae) from Mexico, and Keys for the Groups, Group Three, and First Subgroup - U Castro-Valderrama; G S Carvalho; D C Peck; J M Valdez-Carrasco; J Romero Nápoles (Neotropical Entomology, 2019)

First-order effects of fire and prolonged-drought effects on an undescribed semi-aquatic turtle in Atlantic rainforest in southeastern Brazil - Jane C. F. Oliveira; Thiago Marcial Castro; Thiago Silva-Soares; Carlos Frederico Duarte Rocha (Journal of Coastal Conservation, 2019)

Production of benzyl carbonyl (rose aroma) from whey and its effect on pollutant load removal - L. Conde Báez; J. Castro Rosas; J. R. Villagómez Ibarra; I. Palma Quiroz; J. B. Páez Lerma; C. A. Gómez Aldapa (Environment, Development and Sustainability, 2019)

Draft genome sequence of Lactobacillus plantarum C4 (CECT 9567), a potential probiotic strain isolated from kefir - Soumi De Montijo-Prieto; David J. Castro; Jose C. Reina; Maria Jimenez-Valera; Alfonso Ruiz-Bravo (Archives of Microbiology, 2019)

Do condensed tannins from Lysiloma latisiliquum have a role in its anthelmintic activity? - C. A. Sandoval-Castro (Natural Product Research, 2019)

Correlation between geometric parameters of the left coronary artery and hemodynamic descriptors of atherosclerosis: FSI and statistical study - N. Pinho; C. F. Castro; C. C. António; N. Bettencourt; L. C. Sousa; S. I. S. Pinto (Medical & Biological Engineering & Computing, 2019)

Two epizootic Perkinsus spp. events in commercial oyster farms at Santa Catarina, Brazil - Ana C. Luz Cunha; Vitor de A. Pontinha; Maria Alcina M. de Castro; Simone Sühnel; Sthefanie C. Medeiros; Ângela M. Moura da Luz; Ricardo Harakava; Leonardo Tachibana; Danielle F. Mello; Naissa M. Danielli; Alcir L. Dafre; Aimê R. M. Magalhães; et al. (Journal of Fish Diseases, 2019)
Perkinsus spp. have been detected in various bivalve species from north‐east Brazil. Santa Catarina is a South Brasil state with the highest national oyster production. Considering the pathogenicity of some Perkinsus spp., a study was carried out to survey perkinsosis in two oyster species cultured in this State, the mangrove oyster Crassostrea gasar and the Pacific oyster Crassostrea gigas . Sampling involved eight sites along the state coast, and oyster sampling was collected during the period between January 2013 and December 2014. For the detection of Perkinsus , Ray's fluid thioglycollate medium (RFTM) and histology were used, and for the identification of the species, PCR and DNA sequencing were used. Perkinsus spp. was found by RFTM in C. gigas and C. gasar from São Francisco do Sul. This pathology was also detected in C. gasar from Balneário Barra do Sul both, by RFTM and histology. Perkinsus marinus was identified in C. gigas and C. gasar from São Francisco do Sul and Perkinsus beihaiensis in C. gasar from Balneário Barra do Sul. This is the first report of P. marinus in C. gigas from South America. Results of this preliminary study suggest that both oyster species tolerate the species of Perkinsus identified, without suffering heavy lesions.

Plant interactions shape pollination networks via nonadditive effects - Gianalberto Losapio; Miguel A. Fortuna; Jordi Bascompte; Bernhard Schmid; Richard Michalet; Rainer Neumeyer; Leopoldo Castro; Pierfilippo Cerretti; Christoph Germann; Jean‐Paul Haenni; Seraina Klopfstein; Francisco Javier Ortiz‐Sanchez; et al. (Ecology, 2019)
Plants grow in communities where they interact with other plants and with other living organisms such as pollinators. On the one hand, studies of plant–plant interactions rarely consider how plants interact with other trophic levels such as pollinators. On the other, studies of plant–animal interactions rarely deal with interactions within trophic levels such as plant–plant competition and facilitation. Thus, to what degree plant interactions affect biodiversity and ecological networks across trophic levels is poorly understood. We manipulated plant communities driven by foundation species facilitation and sampled plant–pollinator networks at fine spatial scale in a field experiment in Sierra Nevada, Spain. We found that plant–plant facilitation shaped pollinator diversity and structured pollination networks. Nonadditive effects of plant interactions on pollinator diversity and interaction diversity were synergistic in one foundation species networks while they were additive in another foundation species. Nonadditive effects of plant interactions were due to rewiring of pollination interactions. In addition, plant facilitation had negative effects on the structure of pollination networks likely due to increase in plant competition for pollination. Our results empirically demonstrate how different network types are coupled, revealing pervasive consequences of interaction chains in diverse communities.

Comparative Analysis of the Adhesive Proteins of the Adult Stalked Goose Barnacle Pollicipes pollicipes (Cirripedia: Pedunculata) - Miguel Rocha; Paulo Antas; L. Filipe C. Castro; Alexandre Campos; Vítor Vasconcelos; Filipe Pereira; Isabel Cunha (Marine Biotechnology, 2019)

Climate change resilience of a globally important sea turtle nesting population - Ana R. Patrício; Miguel R. Varela; Castro Barbosa; Annette C. Broderick; Paulo Catry; Lucy A. Hawkes; Aissa Regalla; Brendan J. Godley (Global Change Biology, 2019)
Few studies have looked into climate change resilience of populations of wild animals. We use a model higher vertebrate, the green sea turtle, as its life history is fundamentally affected by climatic conditions, including temperature‐dependent sex determination and obligate use of beaches subject to sea level rise ( SLR ). We use empirical data from a globally important population in West Africa to assess resistance to climate change within a quantitative framework. We project 200 years of primary sex ratios (1900–2100) and create a digital elevation model of the nesting beach to estimate impacts of projected SLR . Primary sex ratio is currently almost balanced, with 52% of hatchlings produced being female. Under IPCC models, we predict: (a) an increase in the proportion of females by 2100 to 76%–93%, but cooler temperatures, both at the end of the nesting season and in shaded areas, will guarantee male hatchling production; (b) IPCC SLR scenarios will lead to 33.4%–43.0% loss of the current nesting area; (c) climate change will contribute to population growth through population feminization, with 32%–64% more nesting females expected by 2120; (d) as incubation temperatures approach lethal levels, however, the population will cease growing and start to decline. Taken together with other factors (degree of foraging plasticity, rookery size and trajectory, and prevailing threats), this nesting population should resist climate change until 2100, and the availability of spatial and temporal microrefugia indicates potential for resilience to predicted impacts, through the evolution of nest site selection or changes in nesting phenology. This represents the most comprehensive assessment to date of climate change resilience of a marine reptile using the most up‐to‐date IPCC models, appraising the impacts of temperature and SLR , integrated with additional ecological and demographic parameters. We suggest this as a framework for other populations, species and taxa.

Identification of a Novel Nucleobase-Ascorbate Transporter Family Member in Fish and Amphibians - Diogo Oliveira; André M. Machado; Tiago Cardoso; Mónica Lopes-Marques; L. Filipe C. Castro; Raquel Ruivo (Fishes, 2019)
Nucleobase-Ascorbate Transporter (NAT) family includes ascorbic acid, nucleobases, and uric acid transporters: With broad evolutionary distribution. In vertebrates, four members have been previously recognized, the ascorbate transporters Slc23a1 and Slc3a2, the nucleobase transporter Slc23a4 and an orphan transporter Slc23a3. Using phylogenetic and synteny analysis, we identify a fifth member of the vertebrate slc23 complement (slc23a5), present in neopterygians (gars and teleosts) and amphibians, and clarify the evolutionary relationships between the novel gene and known slc23 genes. Further comparative analysis puts forward uric acid as the preferred substrate for Slc23a5. Gene expression quantification, using available transcriptomic data, suggests kidney and testis as major expression sites in Xenopus tropicalis (western clawed frog) and Danio rerio (zebrafish). Additional expression in brain was detected in D. rerio, while in the Neoteleostei Oryzias latipes (medaka) slc23a5 expression is restricted to the brain. The biological relevance of the retention of an extra transporter in fish and amphibians is discussed.

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Polymorphisms within the prolactin and growth hormone/insulin-like growth factor-1 functional pathways associated with fertility traits in Holstein cows raised in a hot-humid climate - Jose C. Leyva-Corona; Javier R. Reyna-Granados; Ricardo Zamorano-Algandar; Miguel A. Sanchez-Castro; Milton G. Thomas; R. Mark Enns; Scott E. Speidel; Juan F. Medrano; Gonzalo Rincon; Pablo Luna-Nevarez (Tropical Animal Health and Production, 2018)

Astrogliosis and decreased neural viability as consequences of early consumption of aspartame and acesulfame potassium in male Wistar rats - Anayelly Solis-Medina; José Jaime Martínez-Magaña; Valeria Quintanar-Jurado; Ileana Gallegos-Silva; Isela E. Juárez-Rojop; Carlos Alfonso Tovilla-Zárate; Juan C Díaz-Zagoya; Yazmín Hernández-Díaz; Thelma Beatriz González-Castro; María Lilia López-Narváez; Alma Delia Genis-Mendoza; Humberto Nicolini (Metabolic Brain Disease, 2018)

Genotyping of Antimicrobial Resistance and Virulence in Staphylococcus Isolated from Food of Animal Origin in Mexico - Yosainix C. Gaerste-Díaz; Patricia Lozano-Zarain; Carmen Torres; Numa P. Castro González; Rosa del C. Rocha-Gracia (Indian Journal of Microbiology, 2018)

STMS (sequence tagged microsatellite site) molecular markers as a valuable tool to confirm controlled crosses in chickpea (Cicer arietinum L.) breeding programs - C. Caballo; P. Castro; J. Gil; I. Izquierdo; T. Millan; J. Rubio (Euphytica, 2018)

Optimization of the parameters that affect the synthesis of magnetic copolymer styrene-divinilbezene to be used as efficient matrix for immobilizing lipases - Mateus V. C. Silva; Leandro G. Aguiar; Heizir F. de Castro; Larissa Freitas (World Journal of Microbiology and Biotechnology, 2018)

Cetacea are natural knockouts for IL20 - Mónica Lopes-Marques; André M. Machado; Susana Barbosa; Miguel M. Fonseca; Raquel Ruivo; L. Filipe C. Castro (Immunogenetics, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Aluminum fractionation in acidic soils and river sediments in the Upper Mero basin (Galicia, NW Spain) - L. Palleiro; C. Patinha; M. L. Rodríguez-Blanco; M. M. Taboada-Castro; M. T. Taboada-Castro (Environmental Geochemistry and Health, 2018)

Enzyme-linked immunosorbent assay and agar gel immunodiffusion assay for diagnosis of equine infectious anemia employing p26 protein fused to the maltose-binding protein - Karin F. L. P. Fontes; Luiz C. Silva-Júnior; Sérgio A. Nascimento; Daniel P. Chaves; Jose W. Pinheiro-Júnior; Antonio C. Freitas; Roberto S. Castro; André L. S. Jesus (Archives of Virology, 2018)

Exploring drivers of litter decomposition in a greening Arctic: results from a transplant experiment across a treeline - Thomas C. Parker; Jonathan Sanderman; Robert D. Holden; Gesche Blume‐Werry; Sofie Sjögersten; David Large; Miguel Castro‐Díaz; Lorna E. Street; Jens‐Arne Subke; Philip A. Wookey (Ecology, 2018)
Decomposition of plant litter is a key control over carbon (C) storage in the soil. The biochemistry of the litter being produced, the environment in which the decomposition is taking place, and the community composition and metabolism of the decomposer organisms exert a combined influence over decomposition rates. As deciduous shrubs and trees are expanding into tundra ecosystems as a result of regional climate warming, this change in vegetation represents a change in litter input to tundra soils and a change in the environment in which litter decomposes. To test the importance of litter biochemistry and environment in determining litter mass loss, we reciprocally transplanted litter between heath ( Empetrum nigrum ), shrub ( Betula nana ), and forest ( Betula pubescens ) at a sub‐Arctic treeline in Sweden. As expansion of shrubs and trees promotes deeper snow, we also used a snow fence experiment in a tundra heath environment to understand the importance of snow depth, relative to other factors, in the decomposition of litter. Our results show that B. pubescens and B. nana leaf litter decomposed at faster rates than E. nigrum litter across all environments, while all litter species decomposed at faster rates in the forest and shrub environments than in the tundra heath. The effect of increased snow on decomposition was minimal, leading us to conclude that microbial activity over summer in the productive forest and shrub vegetation is driving increased mass loss compared to the heath. Using B. pubescens and E. nigrum litter, we demonstrate that degradation of carbohydrate‐C is a significant driver of mass loss in the forest. This pathway was less prominent in the heath, which is consistent with observations that tundra soils typically have high concentrations of “labile” C. This experiment suggests that further expansion of shrubs and trees may stimulate the loss of undecomposed carbohydrate C in the tundra.

Characterizing the growth of Sarcoptes scabiei infrapopulations - Inmaculada Castro; José Espinosa; José E. Granados; Francisco J. Cano-Manuel; Paulino Fandos; Arián Ráez-Bravo; Jorge R. López-Olvera; Ramón C. Soriguer; Jesús M. Pérez (Experimental and Applied Acarology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Use of chemometric analyses to assess biological wastewater treatment plants by protozoa and metazoa monitoring - A. Luís Amaral; Cristiano S. Leal; A. Isabel Vaz; J. Carvalho Vieira; Andreia C. Quinteiro; M. Lourdes Costa; L. Miguel Castro (Environmental Monitoring and Assessment, 2018)

Characterization and Comparison of Genetic Variation in Cotesia flavipes (Hymenoptera: Braconidae) Mass Reared for Biological Pest Control Using Microsatellite Markers - F C Freitas; A C Morales-Corrêa e Castro; N C C P Barbosa; O A Fernandes (Neotropical Entomology, 2018)

Dietary Exposure to Tebuconazole Affects Testicular and Epididymal Histomorphometry in Frugivorous Bats - Mariana Machado-Neves; Mário J. O. Neto; Diane C. Miranda; Ana Cláudia F. Souza; Mariana M. Castro; Marcela N. Sertorio; Túlio F. Carvalho; Sérgio L. P. Matta; Mariella B. Freitas (Bulletin of Environmental Contamination and Toxicology, 2018)

Polymorphism of the DRD2 Gene in a Mexican Population with Mental Deviations - M. Salas-Magaña; C. A. Tovilla-Zárate; A. Genis; T. B. González-Castro; I. E. Juárez-Rojop; M. L. López-Narvaez (Neurophysiology, 2018)

Genetic ablation of pannexin1 counteracts liver fibrosis in a chemical, but not in a surgical mouse model - Sara Crespo Yanguas; Tereza C. da Silva; Isabel V. A. Pereira; Michaël Maes; Joost Willebrords; Valery I. Shestopalov; Bruna M. Goes; Marina Sayuri Nogueira; Inar Alves de Castro; Guilherme R. Romualdo; Luís F. Barbisan; Eva Gijbels; et al. (Archives of Toxicology, 2018)

Geostatistical Interplay Between Geophysical and Geochemical Data: Mapping Litho-Structural Assemblages of Mesozoic Igneous Activities in the Parnaíba Basin (NE Brazil) - David L. de Castro; Diógenes C. Oliveira; Maria Helena B. M. Hollanda (Surveys in Geophysics, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Notes on the Occurrence of Oligonychus milleri (McGregor) and Oligonychus ununguis (Jacobi) (Acari: Tetranychidae) in Brazil - E B Castro; O C Zanardi; J Garlet; R Ochoa; R J F Feres (Neotropical Entomology, 2018)

The performance of RegCM4 over the Central America and Caribbean region using different cumulus parameterizations - Daniel Martínez-Castro; Alejandro Vichot-Llano; Arnoldo Bezanilla-Morlot; Abel Centella-Artola; Jayaka Campbell; Filippo Giorgi; Cecilia C. Viloria-Holguin (Climate Dynamics, 2018)

Summer-autumn air pollution in León, Spain: changes in aerosol size distribution and expected effects on the respiratory tract - F. Oduber; A. Castro; A.I. Calvo; C. Blanco-Alegre; E. Alonso-Blanco; P. Belmonte; R. Fraile (Air Quality, Atmosphere & Health, 2018)

Morphological development in the first life phase of Adriatic sturgeon Acipenser naccarii under controlled conditions - R. Cabrera‐Castro; C. Zabala; M. C. Soriguer; A. Domezain; J. A. Hernando (Journal of Fish Biology, 2018)
Early development of the Adriatic sturgeon Acipenser naccarii from its free embryo after hatching (stage 36), until late embryo stage, when the transition to exogenous feeding starts (stage 45) is described. Special emphasis is given to morphological development and description of the different structures that are formed at each life stage. After hatching, free embryos still present embryonic characteristics, little pigmentation and an ovoid yolk sac. The mouth begins to open on the second day post hatch (dph) and is fully open at 3 dph. The head begins to separate from the body at 4 dph and straightens at 6 dph. The first fins to appear are the pectoral fins on the yolk sac and an embryological fin fold that extends from behind the head to the posterior part of the yolk sac. All other fins will develop from this fold. At 7 dph the caudal fin begins to take a heterocercal form and dorsal scutes are observed. This study provides information that will assist aquaculturists by establishing a reference for the normal development of A. naccarii , which may be useful for evaluating the suitability and quality of fish produced for restocking.

Transgenerational Effects of Toxicants: An Extension of the Daphnia 21-day Chronic Assay? - B. B. Castro; A. R. Freches; M. Rodrigues; B. Nunes; S. C. Antunes (Archives of Environmental Contamination and Toxicology, 2018)

Breeding implications of drought stress under future climate for upland rice in Brazil - Julian Ramirez‐Villegas; Alexandre B. Heinemann; Adriano Pereira de Castro; Flávio Breseghello; Carlos Navarro‐Racines; Tao Li; Maria C. Rebolledo; Andrew J. Challinor (Global Change Biology, 2018)
Rice is the most important food crop in the developing world. For rice production systems to address the challenges of increasing demand and climate change, potential and on‐farm yield increases must be increased. Breeding is one of the main strategies toward such aim. Here, we hypothesize that climatic and atmospheric changes for the upland rice growing period in central Brazil are likely to alter environment groupings and drought stress patterns by 2050, leading to changing breeding targets during the 21st century. As a result of changes in drought stress frequency and intensity, we found reductions in productivity in the range of 200–600 kg/ha (up to 20%) and reductions in yield stability throughout virtually the entire upland rice growing area (except for the southeast). In the face of these changes, our crop simulation analysis suggests that the current strategy of the breeding program, which aims at achieving wide adaptation, should be adjusted. Based on the results for current and future climates, a weighted selection strategy for the three environmental groups that characterize the region is suggested. For the highly favorable environment ( HFE , 36%–41% growing area, depending on RCP ), selection should be done under both stress‐free and terminal stress conditions; for the favorable environment ( FE , 27%–40%), selection should aim at testing under reproductive and terminal stress, and for the least favorable environment ( LFE , 23%–27%), selection should be conducted for response to reproductive stress only and for the joint occurrence of reproductive and terminal stress. Even though there are differences in timing, it is noteworthy that stress levels are similar across environments, with 40%–60% of crop water demand unsatisfied. Efficient crop improvement targeted toward adaptive traits for drought tolerance will enhance upland rice crop system resilience under climate change.

Bat and bee pollination in Psittacanthus mistletoes, a genus regarded as exclusively hummingbird‐pollinated - Rodrigo F. Fadini; Erich Fischer; Sônia J. Castro; Andréa C. Araujo; Juan Francisco Ornelas; Paulo R. de Souza (Ecology, 2018)

The cycling gonad: retinoic‐acid synthesis and degradation patterns during adult zebrafish Danio rerio oogenesis - R. Ruivo; A. Capitão; L. F. C. Castro; M. M. Santos (Journal of Fish Biology, 2018)
The expression pattern of genes coding for enzymes of the retinoic acid (RA) synthetic and degradation pathways was characterized in adult female zebrafish Danio rerio . Females were conditioned until maturation and post‐spawn expression dynamics were determined. A striking upregulation of cyp26b1 , but not cyp26a1 , was observed following egg deposition, decreasing to initial levels during recovery. A similar, yet lower, fluctuation was observed for aldh1a2 and rdh10a , the enzymes participating in the two‐step RA biosynthesis cascade. The present work highlights the dynamics of the adult D. rerio oogenesis and uncovers novel, yet elusive, metabolic contributors. Possible compartmentalized roles for the different gene paralogue isoforms are discussed.

Ascorbic acid toxicity is related to oxidative stress and enhanced by high light and knockdown of chloroplast ascorbate peroxidases in rice plants - Jamyla L. S. Castro; Yugo Lima-Melo; Fabricio E. L. Carvalho; Antonio G. S. Feitosa; Milton C. Lima Neto; Andréia Caverzan; Marcia Margis-Pinheiro; Joaquim A. G. Silveira (Theoretical and Experimental Plant Physiology, 2018)

Micropropagation of Asparagus macrorrhizus, a Spanish endemic species in extreme extinction risk - J. J. Regalado; E. Carmona-Martin; M. López-Granero; A. Jiménez-Araujo; P. Castro; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Palatability of the Asian clam Corbicula fluminea (Müller 1774) in an invaded system - P. S. Castro; M. I. Ilarri; V. Modesto; C. Antunes; R. Sousa (Hydrobiologia, 2018)

First evidence of viral and bacterial oyster pathogens in the Brazilian coast - D F Mello; N M Danielli; F Curbani; V A Pontinha; S Suhnel; M A M Castro; S C Medeiros; N C Wendt; R Trevisan; A R M Magalhães; A L Dafre (Journal of Fish Diseases, 2018)

The future of fish passage science, engineering, and practice - Ana T. Silva; Martyn C. Lucas; Theodore Castro‐Santos; Christos Katopodis; Lee J. Baumgartner; Jason D. Thiem; Kim Aarestrup; Paulo S. Pompeu; Gordon C. O'Brien; Douglas C. Braun; Nicholas J. Burnett; David Z. Zhu; et al. (Fish and Fisheries, 2018)
Much effort has been devoted to developing, constructing and refining fish passage facilities to enable target species to pass barriers on fluvial systems, and yet, fishway science, engineering and practice remain imperfect. In this review, 17 experts from different fish passage research fields (i.e., biology, ecology, physiology, ecohydraulics, engineering) and from different continents (i.e., North and South America, Europe, Africa, Australia) identified knowledge gaps and provided a roadmap for research priorities and technical developments. Once dominated by an engineering‐focused approach, fishway science today involves a wide range of disciplines from fish behaviour to socioeconomics to complex modelling of passage prioritization options in river networks. River barrier impacts on fish migration and dispersal are currently better understood than historically, but basic ecological knowledge underpinning the need for effective fish passage in many regions of the world, including in biodiversity hotspots (e.g., equatorial Africa, South‐East Asia), remains largely unknown. Designing efficient fishways, with minimal passage delay and post‐passage impacts, requires adaptive management and continued innovation. While the use of fishways in river restoration demands a transition towards fish passage at the community scale, advances in selective fishways are also needed to manage invasive fish colonization. Because of the erroneous view in some literature and communities of practice that fish passage is largely a proven technology, improved international collaboration, information sharing, method standardization and multidisciplinary training are needed. Further development of regional expertise is needed in South America, Asia and Africa where hydropower dams are currently being planned and constructed.

Bleaching in reef invertebrate larvae associated with Symbiodinium strains within clades A–F - M. Mies; A. Z. Güth; C. B. Castro; D. O. Pires; E. N. Calderon; M. Pompeu; P. Y. G. Sumida (Marine Biology, 2018)

Vertical deformation and sea level changes in the coast of Chile by satellite altimetry and tide gauges - Henry D. C. Montecino; Vagner G. Ferreira; Aharon Cuevas; Leoncio Castro Cabrera; Juan Carlos Soto Báez; Silvio R. C. De Freitas (International Journal of Remote Sensing, 2017)

Substrate influence on aromatic plant growth in extensive green roofs in a Mediterranean climate - Cristina M. Monteiro; Cristina S. C. Calheiros; João P. Martins; Francisco M. Costa; Paulo Palha; Sara de Freitas; Nuno M. M. Ramos; Paula M. L. Castro (Urban Ecosystems, 2017)

Production of three symbiosis-related fatty acids by Symbiodinium types in clades A–F associated with marine invertebrate larvae - M. Mies; A. B. Chaves-Filho; S. Miyamoto; A. Z. Güth; A. A. Tenório; C. B. Castro; D. O. Pires; E. N. Calderon; P. Y. G. Sumida (Coral Reefs, 2017)

Larval fish collected from sound‐scattering layers in an offshore tropical area - M. S. Castro; A. C. T. Bonecker (Journal of Fish Biology, 2017)
The composition of the larval fish assemblage in the sound‐scattering layer of the continental shelf waters off the coast of south‐eastern Brazil (12 and 22° S), a research project that is part of the Brazilian programme Avaliação do Potencial Sustentável de Recursos Vivos na Zona Econômica Exclusiva (REVIZEE), is described. Samples were collected during daylight hours and at dusk at five oceanographic stations in the winter of 1999 using an Isaacs‐Kidd Midwater Trawl (IKMT). The oceanographic stations were chosen based on the detection of plankton layers by acoustic observation. A total of 2192 larval fish were identified, comprising 52 families and 62 species. Maurolicus stehmanni (Sternoptychidae) was the most abundant species found within the study area, comprising 18·5% of all identified larvae, followed by Psilotris celsus (Gobiidae) at 10·9%.

Arsenic in the health of ecosystems: spatial distribution in water, sediment and aquatic biota of Pampean streams - M. C. Rodríguez Castro; L Marcó P; M. C. Ranieri; C. Vázquez; A. Giorgi (Environmental Monitoring and Assessment, 2017)

Short-term and long-term effects of diazepam on the memory for discrimination and generalization of scopolamine - C. Casasola-Castro; L. Weissmann-Sánchez; E. Calixto-González; A. Aguayo-Del Castillo; D. N. Velázquez-Martínez (Psychopharmacology, 2017)

New Species of Tenuisvalvae (Duverger) (Coleoptera: Coccinellidae) Feeding on Parthenolecanium perlatum (Cockerell) (Hemiptera: Coccidae) in Citrus Crop - P B Santos; C F Castro-Guedes; A L B G Peronti; L M Almeida (Neotropical Entomology, 2017)

Asparagus macrorrhizus Pedrol, Regalado et López-Encina, an endemic species from Spain in extreme extinction risk, is a valuable genetic resource for asparagus breeding - J. J. Regalado; R. Moreno; P. Castro; E. Carmona-Martin; R. Rodríguez; J. Pedrol; N. Larrañaga; R. Guillén; J. Gil; C. L. Encina (Genetic Resources and Crop Evolution, 2017)

Vapor-phase cristobalite as a durable indicator of magmatic pore structure and halogen degassing: an example from White Island volcano (New Zealand) - C. Ian Schipper; Céline Mandon; Anton Maksimenko; Jonathan M. Castro; Chris E. Conway; Peter Hauer; Martina Kirilova; Geoff Kilgour (Bulletin of Volcanology, 2017)

A fucan of a brown seaweed and its antitumoral property on HT-29 and immunomodulatory activity in murine RAW 264.7 macrophage cell line - Thuane de Sousa Pinheiro; Marilia da S. Nascimento Santos; Luiza Sheyla E. P. Will Castro; Almino Afonso de O. Paiva; Luciana G. Alves; Ana Katarina M. Cruz; Leonardo Thiago D. B. Nobre; Monique Gabriela das C. F. Alves; Edda Lisboa Leite (Journal of Applied Phycology, 2017)

Search and analysis of genes involved in antibiotic resistance in Chilean strains of Piscirickettsia salmonis - C Cartes; A Isla; F Lagos; D Castro; M Muñoz; A Yañez; D Haussmann; J Figueroa (Journal of Fish Diseases, 2017)
Piscirickettsia salmonis is the pathogen causing Piscirickettsiosis. For treatment, the industry mainly uses oxytetracycline and florfenicol, so it is essential to understand the degree of susceptibility of this pathogen to these drugs. But this is still unknown for a large number of P. salmonis strains, as are the molecular mechanisms responsible for greater or lesser susceptibility. However, genes that confer resistance to these antimicrobials have been reported and characterized for this and other bacterial species, among which are membrane proteins that take out the drug. Our results identified differences in the degree of susceptibility to both antibiotics among different Chilean isolated of these bacteria. We analysed 10 available genomes in our laboratory and identified ~140 genes likely to be involved in antibiotic resistance. We analysed six specific genes, which suggests that some of them would eventually be relevant in conferring resistance to both antibiotics, as they encode for specific transporter proteins, which increase the number of transcripts when grown in media with these antibiotics. Our results were corroborated with EtBr permeability analysis, which revealed that the LF ‐89 strain accumulates this compound and has a reduced capacity to expulse it compared with the field strains.

Bacteriological and histopathological study of farmed rainbow trout, Oncorhynchus mykiss , in Peru - E C Mateo; T Castro; V Sierralta; D R Mateo (Journal of Fish Diseases, 2017)

Case Series Study of Invasive Pulmonary Aspergillosis - Ana I. Aller-García; Carmen Castro-Méndez; Ana Alastruey-Izquierdo; Elena M. Marín-Martínez; Ismail Zakariya-Yousef Breval; Carmen Couto-Caro; Juan C. López-Marín; Nicolás Peña-Griñán; Maite Ruiz de Pipaon; Ana M. Romero-Mejías; Estrella Martín-Mazuelos (Mycopathologia, 2017)

Host status of selected cultivated fruit crops to Meloidogyne enterolobii - Vânia M. Freitas; Joelma G. P. Silva; Cesar B. Gomes; José M. C. Castro; Valdir R. Correa; Regina M. D. G. Carneiro (European Journal of Plant Pathology, 2017)

Quantitative image analysis of polyhydroxyalkanoates inclusions from microbial mixed cultures under different SBR operation strategies - António L. Amaral; Hugo Abreu; Cristiano Leal; Daniela P. Mesquita; Luís M. Castro; Eugénio C. Ferreira (Environmental Science and Pollution Research, 2017)

The role of epigenetic modifiers in extended cultures of functional hepatocyte-like cells derived from human neonatal mesenchymal stem cells - M. Cipriano; J. C. Correia; S. P. Camões; N. G. Oliveira; P. Cruz; H. Cruz; M. Castro; J. L. Ruas; J. M. Santos; J. P. Miranda (Archives of Toxicology, 2017)

Life cycle assessment from early development stages: the case of gelatin extracted from tilapia residues - Ana Paula C. Sampaio; Men de Sá M. de Sousa Filho; Ana Lídia A. Castro; Maria Cléa B. de Figueirêdo (The International Journal of Life Cycle Assessment, 2017)

Recombinant Bacillus thuringiensis subsp. kurstaki HD73 strain that synthesizes Cry1Ac and chimeric ChiA74∆sp chitinase inclusions - Karen S. González-Ponce; Luz E. Casados-Vázquez; Rubén Salcedo-Hernández; Dennis K. Bideshi; María C. del Rincón-Castro; José E. Barboza-Corona (Archives of Microbiology, 2017)

Characterization of bacterial communities from Masseiras, a unique Portuguese greenhouse agricultural system - Cristina Becerra-Castro; Ana Rita Lopes; Sara Teixeira; M. Elisabete F. Silva; Elisabete Pimenta; Célia M. Manaia; Olga C. Nunes (Antonie van Leeuwenhoek, 2017)

Role of internal waves on mixing, nutrient supply and phytoplankton community structure during spring and neap tides in the upwelling ecosystem of Ría de Vigo (NW Iberian Peninsula) - Marina Villamaña; Beatriz Mouriño‐Carballido; Emilio Marañón; Pedro Cermeño; Paloma Chouciño; José C. B. da Silva; Patricio A. Díaz; Bieito Fernández‐Castro; Miguel Gilcoto; Rocío Graña; Mikel Latasa; Jorge M. Magalhaes; et al. (Limnology and Oceanography, 2017)
Despite evidence of internal waves in the NW Iberian upwelling region, their action and role on nutrient supply dynamics and phytoplankton community structure remain unexplored. A multidisciplinary approach, combining analysis of Synthetic Aperture Radar (SAR) images acquired during the summer months of 2008–2011, together with high‐frequency samplings carried out in the Ría de Vigo in August 2013 during spring (CHAOS1) and neap tides (CHAOS2), was used to characterize: (1) the internal wave activity, (2) its influence on mixing and nutrient supply, and (3) its role on phytoplankton community. SAR images revealed that internal waves were more energetic during spring tides. Turbulent mixing was higher during CHAOS1‐springs (Kz =1.3 [1.0–2.0, 95% confidence interval] × 10 −3 m 2 s −1 ) compared to CHAOS2‐neaps (Kz = 0.7 [0.5–1.0] × 10 −3 m 2 s −1 ), and as a result nitrate diffusive fluxes were approximately fourfold higher (35 [17–73] mmol m −2 d −1 ) during CHAOS1‐springs. The sampling covered a transition from relaxation‐stratification (CHAOS1‐springs) to intensifying upwelling (CHAOS2‐neaps) conditions, resulting in nitrate supply (including both diffusive and advective fluxes) being about 50% higher during CHAOS2‐neaps. The phytoplankton community, which was overwhelmingly dominated by diatoms in both cruises, exhibited a shift in species composition, with an increase in the abundance of large Chaetoceros spp. during CHAOS2‐neaps. About 50% of the primary production in the ecosystem during periods of upwelling relaxation‐stratification could be sustained by enhanced nitrate diffusive fluxes during spring tides. Therefore, even in coastal upwelling regions, turbulent mixing driven by internal waves could play an important role in controlling phytoplankton productivity and community structure.

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

The climate in Zafra from 1750 to 1840: temperature indexes from documentary sources - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2017)

Skeletal dissolution kinetics and mechanical tests in response to morphology among coral genera - Orión C. Norzagaray-López; Luis E. Calderon-Aguilera; Ana B. Castro-Ceseña; Gustavo Hirata; José M. Hernández-Ayón (Facies, 2017)

Exploring 1,2,3-triazole derivatives by using in vitro and in silico assays to target new antifungal agents and treat Candidiasis - Taísa F. Santos; Jéssica B. de Jesus; Paulo M. Neufeld; Alessandro K. Jordão; Vinícius R. Campos; Anna C. Cunha; Helena C. Castro; Maria C. B. V. de Souza; Vitor F. Ferreira; Carlos R. Rodrigues; Paula A. Abreu (Medicinal Chemistry Research, 2017)

Obtaining advanced generations from Solanum peruvianum PI 126944 in the genetic background of S. lycopersicum by immature seed culture - G. Campos; C. Gisbert; A. Pérez-de-Castro; M. J. Díez (Euphytica, 2017)

Optimized treatment conditions for textile wastewater reuse using photocatalytic processes under UV and visible light sources - Maria Clara V. M. Starling; Luiz Augusto S. Castro; Rafaela B. P. Marcelino; Mônica M. D. Leão; Camila C. Amorim (Environmental Science and Pollution Research, 2017)

Identification and genetic characterization of classical swine fever virus isolates in Brazil: a new subgenotype - Marta N. F. Silva; Diogo M. F. Silva; Adriana S. Leite; Ana L. V. Gomes; Antonio C. Freitas; Jose W. Pinheiro-Junior; Roberto S. Castro; Andre L. S. Jesus (Archives of Virology, 2017)

Hepatocyte spheroids as a competent in vitro system for drug biotransformation studies: nevirapine as a bioactivation case study - Pedro F. Pinheiro; Sofia A. Pereira; Shrika G. Harjivan; Inês L. Martins; Aline T. Marinho; Madalena Cipriano; Cristina C. Jacob; Nuno G. Oliveira; Matilde F. Castro; M. Matilde Marques; Alexandra M. M. Antunes; Joana P. Miranda (Archives of Toxicology, 2017)

Presence of Ureaplasma diversum in the genital tracts of female dairy cattle in Mato Grosso State, Brazil - Jaqueline B. Azevedo; Gustavo S. Silva; Priscylla S. Rocha; Letícia C. Pitchenin; Valéria Dutra; Luciano Nakazato; Anderson Castro Soares de Oliveira; Caroline A. Pescador (Tropical Animal Health and Production, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Inheritance of type IV glandular trichome density and its association with whitefly resistance from Solanum galapagense accession LA1401 - Marcela Carvalho Andrade; Alex Antônio da Silva; Irã Pinheiro Neiva; Izabela Regina C. Oliveira; Evaristo Mauro De Castro; David Merrill Francis; Wilson Roberto Maluf (Euphytica, 2017)

Life cycle inference and phylogeny of Ortholinea labracis n. sp. (Myxosporea: Ortholineidae), a parasite of the European seabass Dicentrarchus labrax (Teleostei: Moronidae), in a Portuguese fish farm - L F Rangel; S Rocha; G Casal; R Castro; R Severino; C Azevedo; F Cavaleiro; M J Santos (Journal of Fish Diseases, 2017)
Ortholinea labracis n. sp. is described and its life cycle is inferred from a Southern Portuguese fish farm, with basis on microscopic and molecular procedures. This myxosporean parasite infects the urinary bladder of the European seabass Dicentrarchus labrax and the intestinal epithelium of a marine oligochaete of the genus Tectidrilus . Myxospores subspherical in valvular view and ellipsoidal in sutural view measuring 7.6 ± 0.3 (6.8–8.7) μm in length, 7.2 ± 0.2 (6.7–7.7) μm in width and 6.5 ± 0.4 (5.8–7.7) μm in thickness. Two polar capsules, 3.0 ± 0.2 (2.6–3.4) μm long and 2.4 ± 0.1 (2.0–2.9) μm wide, located at the same level, but with divergent orientation and opening to opposite sides of the suture line. Sequencing of the SSU rRNA gene revealed a similarity of 100% between the analysed myxospores and triactinomyxon actinospores. The phylogenetic setting of O. labracis n. sp. shows subgrouping in correlation with tissue tropism, but identifies this parasite as another exception to the main division of Myxosporea into the main freshwater and marine lineages.

Effect of season and breed group on the follicular population and cyclicity of heifers under tropical conditions - Jorge Alonso Peralta-Torres; Jesús Ricardo Aké-López; Fernando Gerardo Centurión-Castro; José C. Segura-Correa (Tropical Animal Health and Production, 2017)

Gastrointestinal nematode infection does not affect selection of tropical foliage by goats in a cafeteria trial - J. Ventura-Cordero; P. G. González-Pech; P. R. Jaimez-Rodriguez; G. I. Ortíz-Ocampo; C. A. Sandoval-Castro; J. F. J. Torres-Acosta (Tropical Animal Health and Production, 2017)

Synthesis and in vitro evaluation of novel triazole/azide chalcones - Fernanda C. G. Evangelista; Maralice O. Bandeira; Graziele D. Silva; Marina G. Silva; Silmara N. Andrade; Deisielly R. Marques; Luciana M. Silva; Whocely V. Castro; Fabio V. Santos; Gustavo H. R. Viana; José A. F. P. Villar; Adriano P. Sabino; et al. (Medicinal Chemistry Research, 2017)

Challenges in the management of patients with maple syrup urine disease diagnosed by newborn screening in a developing country - Leniza G. De Castro-Hamoy; Mary Anne D. Chiong; Sylvia C. Estrada; Cynthia P. Cordero (Journal of Community Genetics, 2017)

The expression patterns of aquaporin 9, vacuolar H+-ATPase, and cytokeratin 5 in the epididymis of the common vampire bat - Mariana M. Castro; Bongki Kim; Eric Hill; Maria C. Q. Fialho; Luciano C. H. P. Puga; Mariella B. Freitas; Sylvie Breton; Mariana Machado-Neves (Histochemistry and Cell Biology, 2017)

Performance and health of Holstein calves fed different levels of milk fortified with symbiotic complex containing pre- and probiotics - M. I. Marcondes; T. R. Pereira; J. C. C. Chagas; E. A. Filgueiras; M. M. D. Castro; G. P. Costa; A. L. L. Sguizzato; R. D. Sainz (Tropical Animal Health and Production, 2016)

Detailed Morphology of All Life Stages of the Agave Red Worm, Comadia redtenbacheri (Hammerschmidt) (Lepidoptera: Cossidae) - R Castro-Torres; C Llanderal-Cázares (Neotropical Entomology, 2016)

Evidence of oxidative stress in brain and liver of young rats submitted to experimental galactosemia - Márcia B. Castro; Bruna K. Ferreira; José Henrique Cararo; Adália E. Chipindo; Marina L. Magenis; Monique Michels; Lucinéia G. Danielski; Marcos R. de Oliveira; Gustavo C. Ferreira; Emilio L. Streck; Fabricia Petronilho; Patrícia F. Schuck (Metabolic Brain Disease, 2016)

An Olive Tree Pruning Biorefinery for Co-Producing High Value-Added Bioproducts and Biofuels: Economic and Energy Efficiency Analysis - J. M. Romero-García; A. Sanchez; G. Rendón-Acosta; J. C. Martínez-Patiño; E. Ruiz; G. Magaña; E. Castro (BioEnergy Research, 2016)

Nitrogen Use Efficiency for Sugarcane-Biofuel Production: What Is Next? - R. Otto; S. A. Q. Castro; E. Mariano; S. G. Q. Castro; H. C. J. Franco; P. C. O. Trivelin (BioEnergy Research, 2016)

Simvastatin Treatment Modulates Mechanically-Induced Injury and Inflammation in Respiratory Epithelial Cells - N. Higuita-Castro; V. C. Shukla; C. Mihai; S. N. Ghadiali (Annals of Biomedical Engineering, 2016)

Asymmetric biocatalysis of the nerve agent VX by human serum paraoxonase 1: molecular docking and reaction mechanism calculations - Jaqueline Sartorelli; Alexandre A. de Castro; Teodorico C. Ramalho; Juliana O. S. Giacoppo; Daiana T. Mancini; Melissa S. Caetano; Elaine F. F. da Cunha (Medicinal Chemistry Research, 2016)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Chemical composition and anti-inflammatory activity of the leaves of Byrsonima verbascifolia - Aline Aparecida Saldanha; Lucas Fernandes do Carmo; Sara Batista do Nascimento; Natália Alves de Matos; Clarice de Carvalho Veloso; Ana Hortência Fonsêca Castro; Ric C. H. De Vos; André Klein; João Máximo de Siqueira; Carlos Alexandre Carollo; Thalita Vieira do Nascimento; Mônica Cristina Toffoli-Kadri; et al. (Journal of Natural Medicines, 2016)

Influence of Mussel Culture on the Vertical Export of Phytoplankton Carbon in a Coastal Upwelling Embayment (Ría de Vigo, NW Iberia) - M. Froján; F. G. Figueiras; D. Zúñiga; F. Alonso-Pérez; B. Arbones; C. G. Castro (Estuaries and Coasts, 2016)

Subaerial biofilms on granitic historic buildings: microbial diversity and development of phototrophic multi-species cultures - D. Vázquez-Nion; J. Rodríguez-Castro; M. C. López-Rodríguez; I. Fernández-Silva; B. Prieto (Biofouling, 2016)

Radial and tangential migration of telencephalic somatostatin neurons originated from the mouse diagonal area - Luis Puelles; N. Morales-Delgado; P. Merchán; B. Castro-Robles; M. Martínez-de-la-Torre; C. Díaz; J. L. Ferran (Brain Structure and Function, 2016)

Particular activation phenotype of T cells expressing HLA-DR but not CD38 in GALT from HIV-controllers is associated with immune regulation and delayed progression to AIDS - Sandra M. Gonzalez; Natalia A. Taborda; Luis A. Correa; Gustavo A. Castro; Juan C. Hernandez; Carlos J. Montoya; Maria T. Rugeles (Immunologic Research, 2016)

Quality of the Solimões River water for domestic use by the riverine community situated in Manacapuru-Amazonas-Brazil - N. G. P. Pantoja; L. M. Castro; S. D. Rocha; J. A. Silva; J. S. P. Ribeiro; A. R. Donald; L. M. Silva; T. C. S. Oliveira (Environmental Science and Pollution Research, 2016)

CMA band variability and physical mapping of 5S and 45S rDNA sites in Brazilian Cactaceae: Pereskioideae and Opuntioideae - Juliana P. Castro; Enoque Medeiros-Neto; Gustavo Souza; Lânia I. F. Alves; Fabiane R. C. Batista; Leonardo P. Felix (Brazilian Journal of Botany, 2016)

Brazilian recreational fisheries: current status, challenges and future direction - K. M. F. Freire; R. A. Tubino; C. Monteiro‐Neto; M. F. Andrade‐Tubino; C. G. Belruss; A. R. G. Tomás; S. L. S. Tutui; P. M. G. Castro; L. S. Maruyama; A. C. Catella; D. V. Crepaldi; C. R. A. Daniel; et al. (Fisheries Management and Ecology, 2016)
Recreational fisheries in Brazil have increased in importance and attracted many foreign recreational fishers. The objectives of this article were to summarise the available data on Brazilian recreational fisheries, to discuss some of their features and to analyse how they are performing in different regions compared with international trends. A review of published and unpublished sources together with data from recreational fishing licences was used. The participation rate was low (0.9%). Overall, there was a high diversity of fish species, with the following species/group of species repeatedly reported: Menticirrhus spp., Centropomus spp., Cynoscion spp., and Micropogonias furnieri (marine/estuarine water), and Cichla spp., Hoplias malabaricus , and Piaractus mesopotamicus , together with the introduced Oreochromis niloticus and Coptodon rendalli (fresh water). The north‐eastern region differs from the other regions: fishing occurs mostly in marine waters and fishers acquire mainly shore‐based licences, have minimum fishing expenditures and rarely release fishes. There is no estimate of the total harvest or economic value. Conflicts include catch‐and‐release‐oriented freshwater and marine recreational fishers vs consumption‐oriented coastal fishers, tournament participants vs non‐participants, commercial fishers and other leisure activities, pollution, ports, species introductions and translocations, protected areas, and federal and state laws. Cases of smooth shifts from artisanal to recreational fishing were detected, possibly associated with changes in the societal relationship with natural resources.

Development of a powder formulation based on Bacillus cereus sensu lato strain B25 spores for biological control of Fusarium verticillioides in maize plants - Juan C. Martínez-Álvarez; Claudia Castro-Martínez; Pedro Sánchez-Peña; Roberto Gutiérrez-Dorado; Ignacio E. Maldonado-Mendoza (World Journal of Microbiology and Biotechnology, 2016)

Insights into the virulence‐related genes of Edwardsiella tarda isolated from turbot in Europe: genetic homogeneity and evidence for vibrioferrin production - N Castro; C R Osorio; N Buján; J C Fuentes; J Rodríguez; M Romero; C Jiménez; A E Toranzo; B Magariños (Journal of Fish Diseases, 2016)
Edwardsiella tarda has long been known as a pathogen that causes severe economic losses in aquaculture industry. Insights gained on E. tarda pathogenesis may prove useful in the development of new methods for the treatment of infections as well as preventive measures against future outbreaks. In this report, we have established the correlation between the presence of virulence genes, related with three aspects typically involved in bacterial pathogenesis (chondroitinase activity, quorum sensing and siderophore‐mediated ferric uptake systems), in the genome of E. tarda strains isolated from turbot in Europe and their phenotypic traits. A total of 8 genes were tested by PCR for their presence in 73 E. tarda isolates. High homogeneity was observed in the presence/absence pattern of all the strains. Positive results in the amplification of virulence‐related genes were correlated with the detection of chondroitinase activity in agar plates, in vivo AHL production during fish infection and determination of type of siderophore produced by E. tarda . To the best of our knowledge, this is the first study carried out with European strains on potential virulence factors. Furthermore, we demonstrated for the first time that E. tarda produces the siderophore vibrioferrin.

Sex steroid imbalances in the muricid Stramonita haemastoma from TBT contaminated sites - M. Rossato; I. B. Castro; C. L. Paganini; E. P. Colares; G. Fillmann; G. L. L. Pinho (Environmental Science and Pollution Research, 2016)

Mine land valorization through energy maize production enhanced by the application of plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi - Helena Moreira; Sofia I. A. Pereira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2016)

Phytotoxicity of natural soils using physiological and biochemical endpoints reveals confounding factors: can a weight of evidence tackle uncertainty? - Sara C. Antunes; Bruno B. Castro; Maria Celeste Dias; José Moutinho-Pereira; Carlos M. Correia; Maria T. Claro; Ana Gavina; Conceição Santos; Fernando Gonçalves; Glória Pinto (Journal of Soils and Sediments, 2016)

Acyl-coenzyme A oxidases 1 and 3 in brown trout (Salmo trutta f. fario): Can peroxisomal fatty acid β-oxidation be regulated by estrogen signaling? - Tânia Vieira Madureira; L. Filipe C. Castro; Eduardo Rocha (Fish Physiology and Biochemistry, 2016)

The impact of salinity on the symbiosis between Casuarina glauca Sieb. ex Spreng. and N2-fixing Frankia bacteria based on the analysis of Nitrogen and Carbon metabolism - Nuno Duro; Paula Batista-Santos; Mário da Costa; Rodrigo Maia; Isabel V. Castro; Margarida Ramos; José C. Ramalho; Katharina Pawlowski; Cristina Máguas; Ana Ribeiro-Barros (Plant and Soil, 2016)

Comparative histology and ontogenetic change in the carapace of armadillos (Mammalia: Dasypodidae) - C. M. Krmpotic; M. R. Ciancio; A. A. Carlini; M. C. Castro; A. C. Scarano; C. G. Barbeito (Zoomorphology, 2015)

Molecular insight into the inhibition mechanism of plant and rat 4-hydroxyphenylpyruvate dioxygenase by molecular docking and DFT calculations - Telles Cardoso Silva; Maíra dos Santos Pires; Alexandre Alves de Castro; Elaine F. F. da Cunha; Melissa Soares Caetano; Teodorico C. Ramalho (Medicinal Chemistry Research, 2015)

Impact of freshwater inputs on the spatial structure of benthic macroinvertebrate communities in two landlocked coastal lagoons - P. M. Félix; M. J. Correia; P. Chainho; J. L. Costa; M. L. Chaves; T. Cruz; J. J. Castro; C. Mirra; I. Domingos; A. C. F. Silva; L. Cancela da Fonseca (Hydrobiologia, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

How pervasive is biotic homogenization in human‐modified tropical forest landscapes? - Ricardo Ribeiro de Castro Solar; Jos Barlow; Joice Ferreira; Erika Berenguer; Alexander C. Lees; James R. Thomson; Júlio Louzada; Márcia Maués; Nárgila G. Moura; Victor H. F. Oliveira; Júlio C. M. Chaul; José Henrique Schoereder; et al. (Ecology Letters, 2015)
Land‐cover change and ecosystem degradation may lead to biotic homogenization, yet our understanding of this phenomenon over large spatial scales and different biotic groups remains weak. We used a multi‐taxa dataset from 335 sites and 36 heterogeneous landscapes in the Brazilian Amazon to examine the potential for landscape‐scale processes to modulate the cumulative effects of local disturbances. Biotic homogenization was high in production areas but much less in disturbed and regenerating forests, where high levels of among‐site and among‐landscape β‐diversity appeared to attenuate species loss at larger scales. We found consistently high levels of β‐diversity among landscapes for all land cover classes, providing support for landscape‐scale divergence in species composition. Our findings support concerns that β‐diversity has been underestimated as a driver of biodiversity change and underscore the importance of maintaining a distributed network of reserves, including remaining areas of undisturbed primary forest, but also disturbed and regenerating forests, to conserve regional biota.

New insights towards the establishment of phycocyanin concentration thresholds considering species-specific variability of bloom-forming cyanobacteria - Inês P. E. Macário; Bruno B. Castro; Maria I. S. Nunes; Sara C. Antunes; Cristina Pizarro; Carla Coelho; Fernando Gonçalves; Daniela R. de Figueiredo (Hydrobiologia, 2015)

Trophoblast expression dynamics of the tumor suppressor gene gastrokine 2 - Fabian B. Fahlbusch; Matthias Ruebner; Hanna Huebner; Gudrun Volkert; Hannah Bartunik; Ilona Winterfeld; Andrea Hartner; Carlos Menendez-Castro; Stephanie C. Noegel; Ines Marek; David Wachter; Regine Schneider-Stock; et al. (Histochemistry and Cell Biology, 2015)

Expression of intercellular lipid transport and cholesterol metabolism genes in eggs and early larvae stages of turbot, Scophthalmus maximus, a marine aquaculture species - I. Cunha; S. Galante-Oliveira; E. Rocha; R. Urbatzka; L. F. C. Castro (Marine Biology, 2015)

Study of the somaclonal variation produced by different methods of polyploidization in Asparagus officinalis L. - J. J. Regalado; E. Carmona Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Evaluation of the use of Olivella minuta (Gastropoda, Olividae) and Hastula cinerea (Gastropoda, Terebridae) as TBT sentinels for sandy coastal habitats - Marcelo Petracco; Rita Monteiro Camargo; Thayana Amorim Berenguel; Noelle C. L. Patrício de Arruda; Lygia A. del Matto; Lílian Lund Amado; Thais Navajas Corbisier; Ítalo Braga Castro; Alexander Turra (Environmental Monitoring and Assessment, 2015)

Micropropagation of wild species of the genus Asparagus L. and their interspecific hybrids with cultivated A. officinalis L., and verification of genetic stability using EST-SSRs - J. J. Regalado; E. Carmona-Martín; P. Castro; R. Moreno; J. Gil; C. L. Encina (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Cristobalite in the 2011–2012 Cordón Caulle eruption (Chile) - C. Ian Schipper; Jonathan M. Castro; Hugh Tuffen; Fabian B. Wadsworth; Debra Chappell; Andres E. Pantoja; Mark P. Simpson; Eric C. Le Ru (Bulletin of Volcanology, 2015)

Invasion genetics of the B ermuda buttercup ( O xalis pes‐caprae ): complex intercontinental patterns of genetic diversity, polyploidy and heterostyly characterize both native and introduced populations - Victoria Ferrero; Spencer C. H. Barrett; Sílvia Castro; Patrícia Caldeirinha; Luis Navarro; João Loureiro; Susana Rodríguez‐Echeverría (Molecular Ecology, 2015)
Genetic diversity in populations of invasive species is influenced by a variety of factors including reproductive systems, ploidy level, stochastic forces associated with colonization and multiple introductions followed by admixture. Here, we compare genetic variation in native and introduced populations of the clonal plant Oxalis pes‐caprae to investigate the influence of reproductive mode and ploidy on levels of diversity. This species is a tristylous geophyte native to South Africa. Invasive populations throughout much of the introduced range are composed of a sterile clonal pentaploid short‐styled form. We examined morph ratios, ploidy level, reproductive mode and genetic diversity at nuclear microsatellite loci in 10 and 12 populations from South Africa and the Western Mediterranean region, respectively. Flow cytometry confirmed earlier reports of diploids and tetraploids in the native range, with a single population containing pentaploid individuals. Introduced populations were composed mainly of pentaploids, but sexual tetraploids were also found. There was clear genetic differentiation between ploidy levels, but sexual populations from both regions were not significantly different in levels of diversity. Invasive populations of the pentaploid exhibited dramatically reduced levels of diversity but were not genetically uniform. The occurrence of mixed ploidy levels and stylar polymorphism in the introduced range is consistent with multiple introductions to the Western Mediterranean. This inference was supported by variation patterns at microsatellite loci. Our study indicates that some invasive populations of Oxalis pes‐caprae are not entirely clonal, as often assumed, and multiple introductions and recombination have the potential to increase genetic variation in the introduced range.

Demographic parameters of the insecticide-exposed predator Podisus nigrispinus: implications for IPM - Ancidériton A. de Castro; Júlio César M. Poderoso; Rafael C. Ribeiro; Jesusa C. Legaspi; José E. Serrão; José C. Zanuncio (BioControl, 2015)

Modulation of apoptosis by sulforaphane is associated with PGC-1α stimulation and decreased oxidative stress in cardiac myoblasts - Rafael O. Fernandes; Jéssica H. P. Bonetto; Boran Baregzay; Alexandre L. de Castro; Stephanie Puukila; Heidi Forsyth; Paulo C. Schenkel; Susana F. Llesuy; Ilma Simoni Brum; Alex Sander R. Araujo; Neelam Khaper; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2015)

The climate in Zafra from 1750 to 1840: precipitation - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. M. Vaquero (Climatic Change, 2015)

HER2 and β-catenin protein location: importance in the prognosis of breast cancer patients and their correlation when breast cancer cells suffer stressful situations - F. Darío Cuello-Carrión; Jorge E. Shortrede; Daiana Alvarez-Olmedo; Niubys Cayado-Gutiérrez; Gisela N. Castro; Felipe C. M. Zoppino; Martín Guerrero; Estefania Martinis; Rodolfo Wuilloud; Nidia N. Gómez; Verónica Biaggio; Javier Orozco; et al. (Clinical & Experimental Metastasis, 2015)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Human T-lymphotropic virus type 2 subtype b in a patient with chronic neurological disorder - Carolina Rosadas; Ana C. P. Vicente; Louise Zanella; Mauro J. Cabral-Castro; José M. Peralta; Marzia Puccioni-Sohler (Journal of NeuroVirology, 2014)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Toward hemodynamic diagnosis of carotid artery stenosis based on ultrasound image data and computational modeling - Luísa C. Sousa; Catarina F. Castro; Carlos C. António; André Miguel F. Santos; Rosa Maria dos Santos; Pedro Miguel A. C. Castro; Elsa Azevedo; João Manuel R. S. Tavares (Medical & Biological Engineering & Computing, 2014)

Predicting climate change impacts on native and invasive tree species using radial growth and twenty-first century climate scenarios - N. González-Muñoz; J. C. Linares; P. Castro-Díez; U. Sass-Klaassen (European Journal of Forest Research, 2014)

Unsteady wall shear stress analysis from image-based computational fluid dynamic aneurysm models under Newtonian and Casson rheological models - Marcelo A. Castro; María C. Ahumada Olivares; Christopher M. Putman; Juan R. Cebral (Medical & Biological Engineering & Computing, 2014)

Identifying oceanic foraging grounds of sea turtles in the Atlantic using lead isotopes - Melania C. López-Castro; Karen A. Bjorndal; George D. Kamenov; Alan B. Bolten (Marine Biology, 2014)

Reference genes for RT-qPCR studies in Corynebacterium pseudotuberculosis identified through analysis of RNA-seq data - Daiane M. Carvalho; Pablo H. de Sá; Thiago L. P. Castro; Rodrigo D. Carvalho; Anne Pinto; Danilo J. P. Gil; Priscilla Bagano; Bruno Bastos; Lilia F. M. Costa; Roberto Meyer; Artur Silva; Vasco Azevedo; et al. (Antonie van Leeuwenhoek, 2014)

Biological and chemical analyses of a laboratory-scale biofilter for oxygenate bioremediation in simulated groundwater - J. Purswani; G. A. Silva-Castro; I. M. Guisado; J. González-López; C. Pozo (International Journal of Environmental Science and Technology, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

The climate in Zafra from 1750 to 1840: history and description of weather observations - M. I. Fernández-Fernández; M. C. Gallego; F. Domínguez-Castro; R. M. Trigo; J. A. García; J. M. Vaquero; J. M. Moreno González; J. Castillo Durán (Climatic Change, 2014)

Carrier state induced by oxytetracycline therapy against streptococcosis in N ile tilapia, O reochromis niloticus ( L .) - F C Faria; C A G Leal; G A Carvalho‐Castro; R C Leite; H C P Figueiredo (Journal of Fish Diseases, 2014)

Fucose-containing sulfated polysaccharides from brown macroalgae Lobophora variegata with antioxidant, anti-inflammatory, and antitumoral effects - Luiza Sheyla E. P. Will Castro; Thuane S. Pinheiro; Allisson J. G. Castro; Celina M. P. G. Dore; Naissandra B. da Silva; Monique Gabriela das C. Faustino Alves; Marilia S. Nascimento Santos; Edda Lisboa Leite (Journal of Applied Phycology, 2014)

Electrochemical removal of synthetic textile dyes from aqueous solutions using Ti/Pt anode: role of dye structure - Cynthia K. C. Araújo; Gustavo R. Oliveira; Nedja S. Fernandes; Carmem L. P. S. Zanta; Suely Souza Leal Castro; Djalma R. da Silva; Carlos A. Martínez-Huitle (Environmental Science and Pollution Research, 2014)

Phytomanagement of Cd-contaminated soils using maize (Zea mays L.) assisted by plant growth-promoting rhizobacteria - Helena Moreira; Ana P. G. C. Marques; Albina R. Franco; António O. S. S. Rangel; Paula M. L. Castro (Environmental Science and Pollution Research, 2014)

Irrigation water quality and the benefits of implementing good agricultural practices during tomato (Lycopersicum esculentum) production - M. Estrada-Acosta; M. Jiménez; C. Chaidez; J. León-Félix; N. Castro-del Campo (Environmental Monitoring and Assessment, 2014)

Mycoses and Antifungals: reviewing the basis of a current problem that still is a biotechnological target for marine products - Luciana Terra; Paula A. Abreu; Valéria L. Teixeira; Izabel C. P. Paixão; Rebeca Pereira; Bruno Leal; André Luiz Lourenço; Pabulo H. Rampelotto; Helena C. Castro (Frontiers in Marine Science, 2014)

Rhizobacterial inoculants can improve nickel phytoextraction by the hyperaccumulator Alyssum pintodasilvae - M. I. Cabello-Conejo; C. Becerra-Castro; A. Prieto-Fernández; C. Monterroso; A. Saavedra-Ferro; M. Mench; P. S. Kidd (Plant and Soil, 2014)

A genome-wide association study on copy-number variation identifies a 11q11 loss as a candidate susceptibility variant for colorectal cancer - C. Fernandez-Rozadilla; J. B. Cazier; I. Tomlinson; A. Brea-Fernández; M. J. Lamas; M. Baiget; L. A. López-Fernández; J. Clofent; L. Bujanda; D. Gonzalez; L. de Castro; K. Hemminki; et al. (Human Genetics, 2014)

Acquisition of resistant microorganisms and infections in HIV-infected patients admitted to the ICU - N. Cobos-Trigueros; M. Rinaudo; M. Solé; P. Castro; J. Pumarol; C. Hernández; S. Fernández; J. M. Nicolás; J. Mallolas; J. Vila; L. Morata; J. M. Gatell; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Is the effect of farming practices on songbird communities landscape dependent? A case study of olive groves in southern Spain - J. C. Castro-Caro; I. C. Barrio; F. S. Tortosa (Journal of Ornithology, 2014)

Early Spanish meteorological records (1780–1850) - F. Domínguez‐Castro; J. M. Vaquero; F. S. Rodrigo; A. M. M. Farrona; M. C. Gallego; R. García‐Herrera; M. Barriendos; A. Sanchez‐Lorenzo (International Journal of Climatology, 2014)
This article summarizes recent efforts on early instrumental data recovery in Spain conducted under the Salvà‐Sinobas project. We have retrieved and digitized more than 100 000 meteorological observations prior to 1850 in Spain. This data set contains measurements of air temperature, atmospheric pressure, wind direction and state of the atmosphere in 16 places located in Iberia and the Balearic Islands. Most of the observations are made on a daily basis. However, monthly and annual information has also been retrieved. The time coverage of the series is not homogeneous, with the earliest records starting in Seville in 1780. Prior to this work only two series were available in Spain (i.e. Cadiz and Barcelona), so this data set represents a great advance in the early data availability for Spain. Due to the lack of metadata in most of the series, their interpretation must be made with caution. © 2013 Royal Meteorological Society

Myofibroblasts and the extracellular matrix network in post-myocardial infarction cardiac remodeling - Yonggang Ma; Lisandra E. de Castro Brás; Hiroe Toba; Rugmani Padmanabhan Iyer; Michael E. Hall; Michael D. Winniford; Richard A. Lange; Suresh C. Tyagi; Merry L. Lindsey (Pflügers Archiv - European Journal of Physiology, 2014)

A new Dasypodini armadillo (Xenarthra: Cingulata) from San Gregorio Formation, Pliocene of Venezuela: affinities and biogeographic interpretations - Mariela C. Castro; Alfredo A. Carlini; Rodolfo Sánchez; Marcelo R. Sánchez-Villagra (The Science of Nature, 2014)

Basin‐scale phenology and effects of climate variability on global timing of initial seaward migration of Atlantic salmon ( Salmo salar ) - Jaime Otero; Jan Henning L'Abée‐Lund; Ted Castro‐Santos; Kjell Leonardsson; Geir O. Storvik; Bror Jonsson; Brian Dempson; Ian C. Russell; Arne J. Jensen; Jean‐Luc Baglinière; Mélanie Dionne; John D. Armstrong; et al. (Global Change Biology, 2014)
Migrations between different habitats are key events in the lives of many organisms. Such movements involve annually recurring travel over long distances usually triggered by seasonal changes in the environment. Often, the migration is associated with travel to or from reproduction areas to regions of growth. Young anadromous Atlantic salmon ( Salmo salar ) emigrate from freshwater nursery areas during spring and early summer to feed and grow in the North Atlantic Ocean. The transition from the freshwater (‘parr’) stage to the migratory stage where they descend streams and enter salt water (‘smolt’) is characterized by morphological, physiological and behavioural changes where the timing of this parr‐smolt transition is cued by photoperiod and water temperature. Environmental conditions in the freshwater habitat control the downstream migration and contribute to within‐ and among‐river variation in migratory timing. Moreover, the timing of the freshwater emigration has likely evolved to meet environmental conditions in the ocean as these affect growth and survival of the post‐smolts. Using generalized additive mixed‐effects modelling, we analysed spatio‐temporal variations in the dates of downstream smolt migration in 67 rivers throughout the North Atlantic during the last five decades and found that migrations were earlier in populations in the east than the west. After accounting for this spatial effect, the initiation of the downstream migration among rivers was positively associated with freshwater temperatures, up to about 10 °C and levelling off at higher values, and with sea‐surface temperatures. Earlier migration occurred when river discharge levels were low but increasing. On average, the initiation of the smolt seaward migration has occurred 2.5 days earlier per decade throughout the basin of the North Atlantic. This shift in phenology matches changes in air, river, and ocean temperatures, suggesting that Atlantic salmon emigration is responding to the current global climate changes.

B-lymphocyte tolerance and effector function in immunity and autoimmunity - Wasif N. Khan; Jacqueline A. Wright; Eden Kleiman; Justin C. Boucher; Iris Castro; Emily S. Clark (Immunologic Research, 2013)

Unintended consequences and trade‐offs of fish passage - Robert L McLaughlin; Eric R B Smyth; Theodore Castro‐Santos; Michael L Jones; Marten A Koops; Thomas C Pratt; Luis‐Antonio Vélez‐Espino (Fish and Fisheries, 2013)
We synthesized evidence for unintended consequences and trade‐offs associated with the passage of fishes. Provisioning of fish passageways at dams and dam removals are being carried out increasingly as resource managers seek ways to reduce fragmentation of migratory fish populations and restore biodiversity and nature‐like ecosystem services in tributaries altered by dams. The benefits of provisioning upstream passage are highlighted widely. Possible unwanted consequences and trade‐offs of upstream passage are coming to light, but remain poorly examined and underappreciated. Unintended consequences arise when passage of native and desirable introduced fishes is delayed, undone (fallback), results in patterns of movement and habitat use that reduce D arwinian fitness (e.g. ecological traps), or is highly selective taxonomically and numerically. Trade‐offs arise when passage decisions intended to benefit native species interfere with management decisions intended to control the unwanted spread of non‐native fishes and aquatic invertebrates, or genes, diseases and contaminants carried by hatchery and wild fishes. These consequences and trade‐offs will vary in importance from system to system and can result in large economic and environmental costs. For some river systems, decisions about how to manage fish passage involve substantial risks and could benefit from use of a formal, structured process that allows transparent, objective and, where possible, quantitative evaluation of these risks. Such a process can also facilitate the design of an adaptive framework that provides valuable insights into future decisions.

Generating anatomical models of the heart and the aorta from medical images for personalized physiological simulations - J. Weese; A. Groth; H. Nickisch; H. Barschdorf; F. M. Weber; J. Velut; M. Castro; C. Toumoulin; J. L. Coatrieux; M. De Craene; G. Piella; C. Tobón-Gomez; et al. (Medical & Biological Engineering & Computing, 2013)

Differential Exoproteome Analysis of Two Corynebacterium pseudotuberculosis Biovar Ovis Strains Isolated from Goat (1002) and Sheep (C231) - Wanderson M. Silva; Núbia Seyffert; Alessandra Ciprandi; Agenor V. Santos; Thiago L. P. Castro; Luis G. C. Pacheco; Debmalya Barh; Yves Le Loir; Adriano M. C. Pimenta; Anderson Miyoshi; Artur Silva; Vasco Azevedo (Current Microbiology, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Nematode diversity in different microhabitats in a mangrove region - Taciana K. Pinto; Melanie C. V. Austen; Richard M. Warwick; Paul J. Somerfield; André M. Esteves; Francisco J. V. Castro; Verônica G. Fonseca‐Genevois; Paulo J. P. Santos (Marine Ecology, 2013)
Mangroves are highly productive environments that play important ecological and socioeconomic roles; however, they have been impacted to different degrees in most countries worldwide. The knowledge of which organisms inhabit this environment and their ecological interactions is the first step towards its conservation. The natural variability of environmental factors in mangroves provides numerous niches available to different species. Meiofauna have patchy patterns of distribution that are related to the availability of resources. Hence, meiofauna are expected to present a high diversity of different taxa occupying the different microhabitats offered by mangroves. This work aims to test the hypothesis that the assemblage structure of N ematoda varies significantly among mangrove microhabitats and to contribute knowledge on the meiofauna diversity in mangrove environments. This work was carried out in a mangrove region at P ernambuco state, N ortheastern B razil. Qualitative samples were collected in nine microhabitats which show different characteristics mainly in terms of presence of vegetation or another organism and sediment grain size. Univariate and multivariate analysis were applied to Nematoda genera abundance data. Our results demonstrate the existence of significant differences among microhabitats regarding nematode assemblage structure corroborating the hypothesis. Different N ematoda assemblages are present in at least seven microhabitats. These assemblages are composed of nematode genera with different trophic and morphological features, demonstrating a strong relationship between morphological diversity and ecological plasticity. Furthermore, this study also demonstrates the importance of the conservation of this ecosystem and its attributes.

Tissue expression of PPAR-alpha isoforms in Scophthalmus maximus and transcriptional response of target genes in the heart after exposure to WY-14643 - R. Urbatzka; S. Galante-Oliveira; E. Rocha; L. F. C. Castro; I. Cunha (Fish Physiology and Biochemistry, 2013)

Red deer (Cervus elaphus) as a host for the cattle tick Rhipicephalus microplus (Acari: Ixodidae) in Yucatan, Mexico - R. I. Rodríguez-Vivas; M. M. Ojeda-Chi; J. A. Rosado-Aguilar; I. C. Trinidad-Martínez; J. F. J. Torres-Acosta; V. Ticante-Perez; J. M. Castro-Marín; C. A. Tapia-Moo; G. Vázquez-Gómez (Experimental and Applied Acarology, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

23Na multiple quantum filtered NMR characterisation of Na+ binding and dynamics in animal cells: a comparative study and effect of Na+/Li+ competition - Carla P. Fonseca; Luís L. Fonseca; Liliana P. Montezinho; Paula M. Alves; Helena Santos; M. Margarida C. A. Castro; Carlos F. G. C. Geraldes (European Biophysics Journal, 2013)

Diversity of Archaea in Brazilian savanna soils - E. Catão; A. P. Castro; C. C. Barreto; R. H. Krüger; C. M. Kyaw (Archives of Microbiology, 2013)

Folate metabolite profiling of different cell types and embryos suggests variation in folate one-carbon metabolism, including developmental changes in human embryonic brain - Kit-Yi Leung; Sandra C. P. De Castro; Filipe Cabreiro; Peter Gustavsson; Andrew J. Copp; Nicholas D. E. Greene (Molecular and Cellular Biochemistry, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Transmission of lymphocystis disease virus to cultured gilthead seabream, S parus aurata L ., larvae - I Cano; E J Valverde; E Garcia‐Rosado; M C Alonso; B Lopez‐Jimena; J B Ortiz‐Delgado; J J Borrego; C Sarasquete; D Castro (Journal of Fish Diseases, 2013)
The transmission of lymphocystis disease virus ( LCDV ) to gilthead seabream, S parus aurata L ., larvae was investigated using fertilized eggs from a farm with previous reports of lymphocystis disease. LCDV genome was detected by PCR ‐hybridization in blood samples from 17.5% of the asymptomatic gilthead seabream broodstock analysed. Using the same methodology, eggs spawned from these animals were LCDV positive, as well as larvae hatched from them. The presence of infective viral particles was confirmed by cytopathic effects development on SAF ‐1 cells. Whole‐mount in situ hybridization ( ISH ) and immunohistochemistry ( IHC ) showed the presence of LCDV in the epidermis of larvae hatched from LCDV ‐positive eggs. When fertilized eggs were disinfected with iodine, no viral DNA was detected either in eggs (analysed by PCR ‐hybridization) or in larvae ( PCR ‐hybridization and ISH ). These results suggest the vertical transmission of LCDV , the virus being transmitted on the egg surface. Larvae hatched from disinfected eggs remain LCDV negative during the endotrophic phase, as showed by PCR ‐hybridization, ISH and IHC . After feeding on LCDV ‐positive rotifers, viral antigens were observed in the digestive tract, which suggests that viral entry could be achieved via the alimentary canal, and that rotifers can act as a vector in LCDV transmission to gilthead seabream larvae.

Cellular and humoral immune responses of S enegalese sole, S olea senegalensis ( K aup), following challenge with two P hotobacterium damselae subsp. piscicida strains from different geographical origins - B Costas; P C N P Rêgo; I Simões; J F Marques; M Castro‐Cunha; A Afonso (Journal of Fish Diseases, 2013)
The present study aimed to investigate leucocyte responses to inflammation as well as some innate immune parameters of S enegalese sole, S olea senegalensis , following challenge with two strains of P hotobacterium damselae subsp. piscicida belonging to the E uropean and J apanese clones described for this bacterium. Pathogenicity assays were performed to assess the virulence of each P hotobacterium damselae subsp. piscicida strain for sole. Subsequently, fish were intraperitoneally injected with phosphate‐buffered saline (control) or two concentrations (2 × 10 2 and 2 × 10 6 CFU mL −1 ) of each bacterial strain and sampled after 6 and 24 h. Results showed that the E uropean isolate induces a higher degree of response than the J apanese strain. While blood neutrophilia and monocytosis correlated well with the increase in neutrophil and macrophage numbers in the peritoneal cavity, fish infected with the E uropean isolate presented higher peritoneal cell numbers than fish challenged with the J apanese strain. In addition, alternative complement pathway activity and respiratory burst of head kidney leucocytes increased significantly in fish infected with the E uropean isolate. The enhanced innate immune response displayed by S enegalese sole challenged with the E uropean isolate is probably due to the higher degree of virulence presented by this P hotobacterium damselae subsp. piscicida strain.

Concentration of ascorbic acid and antioxidant response in early life stages of Engraulis ringens and zooplankton during the spawning seasons of 2006–2009 off central Chile - M. C. Krautz; L. R. Castro; M. González; A. Llanos-Rivera; I. Montes; H. González; R. R. González; J. C. Vera (Marine Biology, 2013)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Effect of the metals iron, copper and silver on fluorobenzene biodegradation by Labrys portucalensis - Irina S. Moreira; Catarina L. Amorim; Maria F. Carvalho; António C. Ferreira; Carlos M. Afonso; Paula M. L. Castro (Biodegradation, 2013)

Dyskinesia associated with hyperglycemia and basal ganglia hyperintensity: report of a rare diabetic complication - Giselle F. Taboada; Giovanna A. B. Lima; José E. C. Castro; Bernardo Liberato (Metabolic Brain Disease, 2013)

Western Mediterranean precipitation over the last 300 years from instrumental observations - D. Camuffo; C. Bertolin; N. Diodato; C. Cocheo; M. Barriendos; F. Dominguez-Castro; E. Garnier; M. J. Alcoforado; M. F. Nunes (Climatic Change, 2013)

Population Fluctuation and Damage Caused by Phytophagous Mites on Three Rubber Tree Clones - E B Castro; F M Nuvoloni; C R R Mattos; R J F Feres (Neotropical Entomology, 2013)

Improving performance of Cytisus striatus on substrates contaminated with hexachlorocyclohexane (HCH) isomers using bacterial inoculants: developing a phytoremediation strategy - C. Becerra-Castro; Á. Prieto-Fernández; P. S. Kidd; N. Weyens; B. Rodríguez-Garrido; M. Touceda-González; M. J. Acea; J. Vangronsveld (Plant and Soil, 2013)

Fertility and Life Expectancy of a Predatory Stinkbug to Sublethal Doses of a Pyrethroid - José C. Zanuncio; Pedro Jusselino-Filho; Rafael C. Ribeiro; Ancidériton A. Castro; Teresinha V. Zanuncio; José E. Serrão (Bulletin of Environmental Contamination and Toxicology, 2013)

Can the red palm mite threaten the Amazon vegetation? - Manoel G. C. Gondim; Tatiane M. M. G. Castro; Alberto L. Marsaro; Denise Navia; José W. S. Melo; Peterson R. Demite; Gilberto J. de Moraes (Systematics and Biodiversity, 2012)

Stunting delays maturation of triceps surae mechanical properties and motor performance in prepubertal children - Maria das Graças Paiva; Thaysa O. L. Souza; Francis Canon; Chantal Pérot; Luciana C. C. Xavier; Karla M. Ferraz; Mônica M. Osório; Raul Manhães-de-Castro; Daniel Lambertz (European Journal of Applied Physiology, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Mechanisms of bubble coalescence in silicic magmas - Jonathan M. Castro; Alain Burgisser; C. Ian Schipper; Simona Mancini (Bulletin of Volcanology, 2012)

Epidemiological aspects of HCV infection in HIV-infected individuals in Piauí State, Northeast Brazil - Aldemir B. Oliveira-Filho; Evaldo H. Oliveira; Jairo A. A. Castro; Letiano V. Silva; Antonio C. R. Vallinoto; José Alexandre R. Lemos (Archives of Virology, 2012)

Effect of Storage Conditions on Total Volatile Base Nitrogen Determinations in Fish Muscle Extracts - P. Castro; R. Millán; J. C. Penedo; E. Sanjuán; A. Santana; M. J. Caballero (Journal of Aquatic Food Product Technology, 2012)

Tauroursodeoxycholic Acid Prevents MPTP-Induced Dopaminergic Cell Death in a Mouse Model of Parkinson’s Disease - M. Castro-Caldas; A. Neves Carvalho; E. Rodrigues; C. J. Henderson; C. R. Wolf; C. M. P. Rodrigues; M. J. Gama (Molecular Neurobiology, 2012)

The effect of biomaterials and antifungals on biofilm formation by Candida species: a review - M. Cuéllar-Cruz; A. Vega-González; B. Mendoza-Novelo; E. López-Romero; E. Ruiz-Baca; M. A. Quintanar-Escorza; J. C. Villagómez-Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Ticks (Ixodida) on humans from central Panama, Panama (2010–2011) - Sergio E. Bermúdez C.; Angélica Castro; Helen Esser; Yorick Liefting; Gleydis García; Roberto J. Miranda (Experimental and Applied Acarology, 2012)

Diet and exercise training reduce blood pressure and improve autonomic modulation in women with prehypertension - Allan R. K. Sales; Bruno M. Silva; Fabricia J. Neves; Natália G. Rocha; Renata F. Medeiros; Renata R. T. Castro; Antonio C. L. Nóbrega (European Journal of Applied Physiology, 2012)

Myrmecofauna of Ironstone Outcrops: Composition and Diversity - Flávia Elizabeth Castro Viana-Silva; C. M. Jacobi (Neotropical Entomology, 2012)

Application of selected microbial consortia combined with inorganic and oleophilic fertilizers to recuperate oil-polluted soil using land farming technology - G. A. Silva-Castro; I. Uad; J. Gónzalez-López; C. G. Fandiño; F. L. Toledo; Concepción Calvo (Clean Technologies and Environmental Policy, 2012)

Further Studies on the Hypothesis of PARP-1 Inhibition as a Strategy for Lessening the Long-Term Effects Produced by Perinatal Asphyxia: Effects of Nicotinamide and Theophylline on PARP-1 Activity in Brain and Peripheral Tissue - C. Allende-Castro; P. Espina-Marchant; D. Bustamante; E. Rojas-Mancilla; T. Neira; M. A. Gutierrez-Hernandez; D. Esmar; J. L. Valdes; P. Morales; P. J. Gebicke-Haerter; M. Herrera-Marschitz (Neurotoxicity Research, 2012)

Adenosine Deaminase Activity in Serum and Lymphocytes of Rats Infected with Sporothrix schenckii - Verônica S. P. Castro; Victor C. Pimentel; Aleksandro S. Da Silva; Gustavo R. Thomé; Patrícia Wolkmer; Jorge L. C. Castro; Márcio M. Costa; Cássia B. da Silva; Daniele C. Oliveira; Sydney H. Alves; Maria R. C. Schetinger; Sonia T. A. Lopes; et al. (Mycopathologia, 2012)

Treatment of diesel-polluted clay soil employing combined biostimulation in microcosms - G. A. Silva-Castro; L. SantaCruz-Calvo; I. Uad; C. Perucha; J. Laguna; J. Gónzalez-López; C. Calvo (International Journal of Environmental Science and Technology, 2012)

Zebrafish (Danio rerio) life-cycle exposure to chronic low doses of ethinylestradiol modulates p53 gene transcription within the gonads, but not NER pathways - J. Soares; L. Filipe C. Castro; M. A. Reis-Henriques; N. M. Monteiro; M. M. Santos (Ecotoxicology, 2012)

Bioconversion of oleuropein to hydroxytyrosol by lactic acid bacteria - M. M. Santos; C. Piccirillo; P. M. L. Castro; N. Kalogerakis; M. E. Pintado (World Journal of Microbiology and Biotechnology, 2012)

Glutathione S-Transferase pi Mediates MPTP-Induced c-Jun N-Terminal Kinase Activation in the Nigrostriatal Pathway - Margarida Castro-Caldas; Andreia Neves Carvalho; Elsa Rodrigues; Colin Henderson; C. Roland Wolf; Maria João Gama (Molecular Neurobiology, 2012)

Obstructive Sleep Apnea Severity Correlates with Cellular and Plasma Oxidative Stress Parameters and Affective Symptoms - C. M. R. Franco; A. M. J. Lima; L. Ataíde; O. G. Lins; C. M. M. Castro; A. A. Bezerra; M. F. de Oliveira; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

The Versatility of Delftia sp. Isolates as Tools for Bioremediation and Biofertilization Technologies - Martha C. Ubalde; Victoria Braña; Fabiana Sueiro; María A. Morel; Cecilia Martínez-Rosales; Carolina Marquez; Susana Castro-Sowinski (Current Microbiology, 2012)

Population genetics of the nurse shark (Ginglymostoma cirratum) in the western Atlantic - Stephen A. Karl; Andrey L. F. Castro; Ricardo C. Garla (Marine Biology, 2012)

Evolutionary Implications of Dental Eruption in Dasypus (Xenarthra) - Martin R. Ciancio; Mariela C. Castro; Fernando C. Galliari; Alfredo A. Carlini; Robert J. Asher (Journal of Mammalian Evolution, 2012)

Concentration of ascorbic acid and innate immune effectors in Engraulis ringens and Strangomera bentincki during their main spawning period (2007–2008) in the Humboldt current system off Chile - M. C. Krautz; L. R. Castro; M. González; J. C. Vera; H. E. González (Marine Biology, 2012)

Purification and partial biochemical characterization of a membrane-bound type II-like α-glucosidase from the yeast morphotype of Sporothrix schenckii - Blanca I. Torres-Rodríguez; Karina Flores-Berrout; Julio C. Villagómez-Castro; Everardo López-Romero (Antonie van Leeuwenhoek, 2012)

Effect of the insect growth regulator diflubenzuron on the predator Podisus nigrispinus (Heteroptera: Pentatomidae) - Ancidériton A. Castro; Mabio C. Lacerda; Teresinha V. Zanuncio; Francisco de S. Ramalho; Ricardo A. Polanczyk; José E. Serrão; José C. Zanuncio (Ecotoxicology, 2012)

Functional dissimilarity of melanomacrophage centres in the liver and spleen from females of the teleost fish Prochilodus argenteus - H. J. Ribeiro; M. S. Procópio; J. M. M. Gomes; F. O. Vieira; R. C. Russo; K. Balzuweit; H. Chiarini-Garcia; Antonio Carlos Santana Castro; E. Rizzo; José Dias Corrêa (Cell and Tissue Research, 2011)

Heavy Metal Accumulation in Plant Species Indigenous to a Contaminated Portuguese Site: Prospects for Phytoremediation - Helena Moreira; Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Water, Air, & Soil Pollution, 2011)

Soluble Fas and Fas ligand in HIV/HCV coinfected patients and impact of HCV therapy - M. Guzmán-Fulgencio; J. Berenguer; M. García-Álvarez; D. Micheloud; J. C. López; J. Cosín; I. Fernández de Castro; P. Catalán; P. Miralles; S. Resino (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Air Mercury Contamination in the Gold Mining Town of Portovelo, Ecuador - Víctor González-Carrasco; Patricio C. Velasquez-Lopez; Jesús Olivero-Verbel; Nerlis Pájaro-Castro (Bulletin of Environmental Contamination and Toxicology, 2011)

Fisheries and trade of seahorses in Brazil: historical perspective, current trends, and future directions - Ierecê L. Rosa; Tacyana P. R. Oliveira; Frederico M. Osório; Luiz E. Moraes; André L. C. Castro; Glaura M. L. Barros; Rômulo R. N. Alves (Biodiversity and Conservation, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Testicular Histomorphometry and Ultrastructure of Rats Treated with Cadmium and Ginkgo biloba - Fabrícia de Souza Predes; Juliana Castro Monteiro; Sérgio Luis Pinto Matta; Márcia C. Garcia; Heidi Dolder (Biological Trace Element Research, 2011)

Evaluation of the Sub-lethal Toxicity of Bleached Kraft Pulp Mill Effluent to Carassius auratus and Dicentrarchus labrax - Mário S. Diniz; Ruth Pereira; Ana C. Freitas; Teresa A. P. Rocha-Santos; Luisa Castro; Isabel Peres; Armando C. Duarte (Water, Air, & Soil Pollution, 2011)

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

RETRACTED: Remediation of Heavy Metal Contaminated Soils: An Overview of Site Remediation Techniques - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2011)

Principal components analysis to evaluate ventilatory variability: comparison of athletes and sedentary men - R. R. T. Castro; M. Magini; S. Pedrosa; A. R. K. Sales; A. C. L. Nóbrega (Medical & Biological Engineering & Computing, 2011)

Toxicity of cadmium and zinc on two microalgae, Scenedesmus obliquus and Desmodesmus pleiomorphus, from Northern Portugal - Cristina M. Monteiro; Susana C. Fonseca; Paula M. L. Castro; F. Xavier Malcata (Journal of Applied Phycology, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Acute Toxicity and Effects Analysis of Endosulfan Sulfate to Freshwater Fish Species - John F. Carriger; Tham C. Hoang; Gary M. Rand; Piero R. Gardinali; Joffre Castro (Archives of Environmental Contamination and Toxicology, 2011)

Anti-Leptospira sp. agglutinins in ewes in the Federal District, Brazil - Luiza de S. Seixas; Cristiano Barros de Melo; Rômulo C. Leite; Élvio C. Moreira; Concepta M. McManus; Márcio B. de Castro (Tropical Animal Health and Production, 2011)

Anti-HIV Drugs Nevirapine and Efavirenz Affect Anxiety-Related Behavior and Cognitive Performance in Mice - Pedro R. T. Romão; Joelson C. Lemos; Jeverson Moreira; Gisele de Chaves; Morgana Moretti; Adalberto A. Castro; Vanessa M. Andrade; Carina R. Boeck; João Quevedo; Elaine C. Gavioli (Neurotoxicity Research, 2011)

Delftia sp. JD2: a potential Cr(VI)-reducing agent with plant growth-promoting activity - María A. Morel; Martha C. Ubalde; Victoria Braña; Susana Castro-Sowinski (Archives of Microbiology, 2011)

Similar Intracellular Peptide Profile of TAP1/β2 Microglobulin Double-Knockout Mice and C57BL/6 Wild-Type Mice as Revealed by Peptidomic Analysis - Leandro M. Castro; Denise A. Berti; Lilian C. Russo; Verônica Coelho; Fábio C. Gozzo; Vitor Oliveira; Emer S. Ferro (The AAPS Journal, 2010)

A new genotype of Lymphocystivirus isolated from cultured gilthead seabream, Sparus aurata L., and Senegalese sole, Solea senegalensis (Kaup) - I Cano; E J Valverde; B Lopez‐Jimena; M C Alonso; E Garcia‐Rosado; C Sarasquete; J J Borrego; D Castro (Journal of Fish Diseases, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Efficacy of various chemical disinfectants on biofilms formed in spacecraft potable water system components - Wing C. Wong; Lynn A. Dudinsky†; Veronica M. Garcia; Charlie M. Ott; Victoria A. Castro (Biofouling, 2010)

Wool-degrading Bacillus isolates: extracellular protease production for microbial processing of fabrics - Inés Infante; Maria A. Morel; Martha C. Ubalde; Cecilia Martínez-Rosales; Silvia Belvisi; Susana Castro-Sowinski (World Journal of Microbiology and Biotechnology, 2010)

Species identification using a small nuclear gene fragment: application to sympatric wild carnivores from South-western Europe - R. Oliveira; D. Castro; R. Godinho; G. Luikart; P. C. Alves (Conservation Genetics, 2010)

Management units of brown trout from Galicia (NW: Spain) based on spatial genetic structure analysis - Román Vilas; C. Bouza; J. Castro; A. López; P. Martínez (Conservation Genetics, 2010)

Oral and parenteral vaccines against Flavobacterium columnare: evaluation of humoral immune response by ELISA and in vivo efficiency in Nile tilapia (Oreochromis niloticus) - C. A. G. Leal; G. A. Carvalho-Castro; P. S. C. Sacchetin; C. O. Lopes; A. M. Moraes; H. C. P. Figueiredo (Aquaculture International, 2010)

Changes in metabolic substrates during early development in anchoveta Engraulis ringens (Jenyns 1842) in the Humboldt Current - M. C. Krautz; S. Vásquez; L. R. Castro; M. González; A. Llanos-Rivera; S. Pantoja (Marine Biology, 2010)

The western Mediterranean climate: how will it respond to global warming? - Dario Camuffo; C. Bertolin; N. Diodato; M. Barriendos; F. Dominguez-Castro; C. Cocheo; A. della Valle; E. Garnier; M. -J. Alcoforado (Climatic Change, 2010)

Antioxidant system activation by mercury in Pfaffia glomerata plantlets - N. S. Calgaroto; G. Y. Castro; D. Cargnelutti; L. B. Pereira; J. F. Gonçalves; L. V. Rossato; F. G. Antes; V. L. Dressler; E. M. M. Flores; M. R. C. Schetinger; F. T. Nicoloso (BioMetals, 2010)

Detection of infectious pancreatic necrosis virus (IPNV) from asymptomatic redbanded seabream, Pagrus auriga Valenciennes, and common seabream, Pagrus pagrus (L.), using a non‐destructive procedure - B Lopez‐Jimena; E Garcia‐Rosado; C Infante; I Cano; M Manchado; D Castro; J J Borrego; M C Alonso (Journal of Fish Diseases, 2010)
A non‐destructive procedure based on nested RT‐PCR and dot‐blot hybridization has been developed for the detection of asymptomatic IPNV‐carrier fish. The pair of primers designed for RT‐PCR amplified a 599‐bp fragment of the pVP2 region within the polyprotein gene, resulting in the detection of IPNV genotype III.1. The use of a nested RT‐PCR allowed the amplification of IPNV genotypes III.1 and I.2. In addition, a 191‐bp probe was designed for hybridization studies used in combination with the nested RT‐PCR. The application of the nested RT‐PCR to analyse blood samples from asymptomatic redbanded seabream, Pagrus auriga , and common seabream, P. pagrus , specimens showed a 53.1% and 77.8% prevalence of IPNV‐carriers, respectively. The combination of nested RT‐PCR and dot‐blot hybridization increased the detection rates up to 100% for redbanded seabream and 94.4% for common seabream. Therefore, the protocol described in this study is highly sensitive and specific for the detection of IPNV in asymptomatic carrier fish, and, in addition, the results demonstrate the carrier state in two newly cultured sparid species in southern Spain.

Leaf litter traits of invasive species slow down decomposition compared to Spanish natives: a broad phylogenetic comparison - Oscar Godoy; Pilar Castro-Díez; Richard S. P. Van Logtestijn; Johannes H. C. Cornelissen; Fernando Valladares (Oecologia, 2010)

Blockade of adenosine A2A receptor counteracts neuropeptide-S-induced hyperlocomotion in mice - Carina R. Boeck; Caroline Martinello; Adalberto A. de Castro; Morgana Moretti; Tiago dos Santos Casagrande; Remo Guerrini; Girolamo Calo’; Elaine C. Gavioli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

A Europe–South America network for climate change assessment and impact studies - Jean-Philippe Boulanger; G. Brasseur; Andrea Fabiana Carril; Manuel de Castro; Nicolas Degallier; Carlos Ereño; H. Le Treut; Jose Antonio Marengo; Claudio Guillermo Menendez; Mario Nestor Nuñez; Olga C. Penalba; Alfredo Luis Rolla; et al. (Climatic Change, 2010)

Downscaling extreme month-long anomalies in southern South America - C. G. Menéndez; M. de Castro; J.-P. Boulanger; A. D’Onofrio; E. Sanchez; A. A. Sörensson; J. Blazquez; A. Elizalde; D. Jacob; H. Le Treut; Z. X. Li; M. N. Núñez; et al. (Climatic Change, 2010)

Frequency distribution of XbaIG > T and HaeIIIT > C GLUT1 polymorphisms among different Brazilian ethnic groups - G. C. S. Costa; L. C. J. Alcantara; R. Azevedo; G. Muricy; S. H. Kashima; D. T. Covas; B. Galvão-Castro; S. R. Gadelha (Molecular Biology Reports, 2010)

Polychlorinated Biphenyls and Biotransformation Enzymes in Three Species of Sea Turtles from the Baja California Peninsula of Mexico - K. L. Richardson; M. Lopez Castro; S. C. Gardner; D. Schlenk (Archives of Environmental Contamination and Toxicology, 2010)

Genotoxic activity of Eucalyptus globulus essential oil in Aspergillus nidulans diploid cells - C. T. Miyamoto; J. Rocha De Sant’anna; C. C. Da Silva Franco; M. M. Cunico; O. G. Miguel; L. C. Côcco; C. I. Yamamoto; C. Corrêa; M. A. A. De Castro-Prado (Folia Microbiologica, 2009)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Leishmania amazonensis Growth Inhibitors: Biological and Theoretical Features of Sulfonamide 4-Methoxychalcone Derivatives - Alessandra M. T. Souza; Helena C. Castro; Monique A. Brito; Carla R. Andrighetti-Fröhner; Uiaran Magalhães; Kely N. Oliveira; Daniela Gaspar-Silva; Letícia K. Pacheco; Antônio C. Joussef; Mário Steindel; Cláudia M. O. Simões; Dilvani O. Santos; et al. (Current Microbiology, 2009)

Characterization of Desmodesmus pleiomorphus isolated from a heavy metal-contaminated site: biosorption of zinc - Cristina M. Monteiro; Ana P. G. C. Marques; Paula M. L. Castro; F. Xavier Malcata (Biodegradation, 2009)

Remediation of Heavy Metal Contaminated Soils: Phytoremediation as a Potentially Promising Clean-Up Technology - Ana P. G. C. Marques; António O. S. S. Rangel; Paula M. L. Castro (Critical Reviews in Environmental Science and Technology, 2009)

Relationship Between pH and Stream Water Total Mercury Concentrations in Shenandoah National Park - C. W. Moore; B. J. Cosby; J. N. Galloway; M. S. Castro (Water, Air, & Soil Pollution, 2009)

High Ag-NOR-site variation associated to a secondary contact in brown trout from the Iberian Peninsula - P. Martínez; J. Castro; B. G. Pardo; C. Bouza; M. Hermida; R. Vilas (Genetica, 2009)

Trophic ecology of the Southern Grey Shrike (Lanius meridionalis) in insular environments: the influence of altitude and seasonality - D. P. Padilla; A. González-Castro; C. Nieves; M. Nogales (Journal of Ornithology, 2009)

Low level and sub-chronic exposure to methylmercury induces hypertension in rats: nitric oxide depletion and oxidative damage as possible mechanisms - Denise Grotto; Michele M. de Castro; Gustavo R. M. Barcelos; Solange C. Garcia; Fernando Barbosa (Archives of Toxicology, 2009)

Intercropped oats (Avena sativa) - common vetch (Vicia sativa) silage in the dry season for small-scale dairy systems in the Highlands of Central Mexico - Y. Garduño-Castro; A. Espinoza-Ortega; C. E. González-Esquivel; B. Mateo-Salazar; C. M. Arriaga-Jordán (Tropical Animal Health and Production, 2009)

Short-term recovery of soil functional parameters and edaphic macro-arthropod community after a forest fire - Sara C. Antunes; Nuno Curado; Bruno B. Castro; Fernando Gonçalves (Journal of Soils and Sediments, 2009)

Phagocytosis, Oxidative Burst, and Produced Reactive Species are Affected by Iron Deficiency Anemia and Anemia of Chronic Diseases in Elderly - I. M. M. Paino; J. C. Miranda; C. M. Marzocchi-Machado; E. J. Cesarino; F. A. de Castro; A. M. de Souza (Biological Trace Element Research, 2009)

High frequency of hemolytic and cytotoxic activity in Aeromonas spp. isolated from clinical, food and environmental in Rio de Janeiro, Brazil - Magda C. B. Castilho; Tatiana L. A. Castro; Viviane S. Araújo; Rosemere S. Trajano; Paula A. Santos; Paula M. C. Pimenta; Kely Lucheze; Janyne T. B. Melo; Aline M. Gonçalves; Raquel T. Nogueira; Maria Graças de Luna; Angela C. Freitas-Almeida (Antonie van Leeuwenhoek, 2009)

Toxicity evaluation of three pesticides on non-target aquatic and soil organisms: commercial formulation versus active ingredient - Joana L. Pereira; Sara C. Antunes; Bruno B. Castro; Catarina R. Marques; Ana M. M. Gonçalves; Fernando Gonçalves; Ruth Pereira (Ecotoxicology, 2009)

Expression of the yggE gene protects Escherichia coli from potassium tellurite-generated oxidative stress - Lillian G. Acuña; Iván L. Calderón; Alex O. Elías; Miguel E. Castro; Claudio C. Vásquez (Archives of Microbiology, 2009)

Digestive enzymes of eight Amazonian teleosts with different feeding habits - K. López‐Vásquez; C. A. Castro‐Pérez; A. L. Val (Journal of Fish Biology, 2009)
The levels of amylase, maltase, lipase and alkaline protease from eight fish species of the Amazon were analysed. The enzyme levels are not related to fish feeding habits, reflecting their ever‐changing habitats and their opportunistic feeding behaviour.

Silage from maize (Zea mays), annual ryegrass (Lolium multiflorum) or their mixture in the dry season feeding of grazing dairy cows in small-scale dairy production systems in the Highlands of Mexico - J. P. Anaya-Ortega; G. Garduño-Castro; A. Espinoza-Ortega; R. Rojo-Rubio; C. M. Arriaga-Jordán (Tropical Animal Health and Production, 2009)

Application of in situ detection techniques to determine the systemic condition of lymphocystis disease virus infection in cultured gilt‐head seabream, Sparus aurata L. - I Cano; P Ferro; M C Alonso; C Sarasquete; E Garcia‐Rosado; J J Borrego; D Castro (Journal of Fish Diseases, 2009)
Immunohistochemistry (IHC) and in situ hybridization (ISH) techniques have been used for the detection of lymphocystis disease virus (LCDV) in formalin‐fixed, paraffin‐embedded tissues from gilt‐head seabream, Sparus aurata L. Diseased and recovered fish from the same population were analysed. IHC was performed with a polyclonal antibody against a 60‐kDa viral protein. A specific digoxigenin‐labelled probe, obtained by PCR amplification of a 270‐bp fragment of the gene coding the LCDV major capsid protein, was used for ISH. LCDV was detected in skin dermis and gill lamellae, as well as in several internal organs such as the intestine, liver, spleen and kidney using both techniques. Fibroblasts, hepatocytes and macrophages seem to be target cells for virus replication. The presence of lymphocystis cells in the dermis of the skin and caudal fin, and necrotic changes in the epithelium of proximal renal tubules were the only histological alterations observed in fish showing signs of the disease.

Observed tendencies in maximum and minimum temperatures in Zacatecas, Mexico and possible causes - Luis Brito‐Castillo; Sara C. Díaz Castro; Raúl S. Ulloa Herrera (International Journal of Climatology, 2009)
At a global level, warming caused by the increase in greenhouse gases has been reported in different parts of the world. This warming resulted in a reduction in the diurnal temperature range (DTR), caused by a faster rate of increase in minimum temperatures. However, the tendency toward warming is not obvious in Zacatecas, Mexico. The tendencies in maximum and minimum temperatures are partly linked to the state of the low frequency variability of large‐scale atmospheric flow patterns, as depicted by the 700‐mb geopotential height anomalies. Analyses of maximum and minimum temperatures from 23 climate stations, from 1963 to 2002, show that the DTR in southern Zacatecas is increasing from a rise in maximum temperatures and drop in minimum temperatures, while the DTR in northern Zacatecas is decreasing from a faster rate of decline in maximum temperatures than the increase in minimum temperatures. The regional series related to the F1 and F2 leading modes, after applying a Varimax‐rotated empirical orthogonal function analysis to the 23 DTR series, acceptably reproduce the north–south dipole of DTR changes, while the point‐correlation analysis between the two regional series, the 700‐mb geopotential height anomalies and the indices of Pacific Decadal Oscillation and Atlantic Multidecadal Oscillation indicate that the DTR in Zacatecas, Mexico is related to fluctuations in subtropical and extratropical circulations. Copyright © 2008 Royal Meteorological Society

Chemical composition of urban aerosols in Toulouse, France during CAPITOUL experiment - A. I. Calvo; V. Pont; C. Liousse; B. Dupré; A. Mariscal; C. Zouiten; E. Gardrat; P. Castera; C. G. Lacaux; A. Castro; R. Fraile (Meteorology and Atmospheric Physics, 2008)

Molecular epidemiology of hepatitis B virus in an isolated Afro-Brazilian community - A. R. C. Motta-Castro; R. M. B. Martins; N. M. Araujo; C. Niel; G. B. Facholi; B. V. Lago; F. C. A. Mello; S. A. Gomes (Archives of Virology, 2008)

Numerical study of circulation on the inner Amazon Shelf - Roberto Fioravanti Carelli Fontes; Belmiro Mendes Castro; Robert C. Beardsley (Ocean Dynamics, 2008)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

The Effects of Tannery Wastewater on the Development of Different Plant Species and Chromium Accumulation in Phragmites australis - Cristina S. C. Calheiros; António O. S. S. Rangel; Paula M. L. Castro (Archives of Environmental Contamination and Toxicology, 2008)

Benzodiazepine-Mediated Structural Changes in the Multidrug Transporter P-Glycoprotein: An Intrinsic Fluorescence Quenching Analysis - Sofia A. C. Lima; Anabela Cordeiro-da-Silva; Baltazar de Castro; Paula Gameiro (The Journal of Membrane Biology, 2008)

Immune Response to Nocardia brasiliensis Extracellular Antigens in Patients with Mycetoma - Bárbara Castro-Matteotti; Lucio Vera-Cabrera; Jorge Ocampo-Candiani; Adrián Rendón; Mario C. Salinas-Carmona; Oliverio Welsh (Mycopathologia, 2008)

A Novel Approach for Bioremediation of a Coastal Marine Wastewater Effluent Based on Artificial Microbial Mats - J. Zamora-Castro; J. Paniagua-Michel; C. Lezama-Cervantes (Marine Biotechnology, 2008)

Role of respiration and glutathione in cadmium-induced oxidative stress in Escherichia coli K-12 - Catarina C. Pacheco; João F. Passos; A. Rita Castro; Pedro Moradas-Ferreira; Paolo De Marco (Archives of Microbiology, 2008)

Enzymatic hydrolysis of soybean oil using lipase from different sources to yield concentrated of polyunsaturated fatty acids - Larissa Freitas; Tânia Bueno; Victor H. Perez; Júlio C. Santos; Heizir Ferreira de Castro (World Journal of Microbiology and Biotechnology, 2007)

Flow cytometric and cytogenetic analyses of Iberian Peninsula Festuca spp. - J. Loureiro; D. Kopecký; S. Castro; C. Santos; P. Silveira (Plant Systematics and Evolution, 2007)

Analysis of a secondary contact between divergent lineages of brown trout Salmo trutta L. from Duero basin using microsatellites and mtDNA RFLPs - P. Martínez; C. Bouza; J. Castro; M. Hermida; B. G. Pardo; L. Sánchez (Journal of Fish Biology, 2007)
The analysis of 12 microsatellite loci in 16 native populations of Salmo trutta from Duero basin evidenced a strong genetic differentiation in accordance with the existence of two divergent Atlantic mtDNA lineages, Atlantic (AT) and Duero (DU). These lineages were observed spatially segregated mainly in the Lower‐course and in the inner part of the basin. Unlike previous isozyme information, microsatellite data suggested a more downstream location of the sharpest genetic divergence in Duero basin and a more complex structure in the inward area. Putative hybrid populations evidenced higher Hardy–Weinberg and gametic disequilibria than pure ones (Pisuerga, Lower‐course), not explained by mixture due to differential immigration pattern across the basin. Hybridization indexes suggested a bimodal pattern of hybridization and a higher weight of Pisuerga region in the genetic composition of hybrid samples in accordance with mtDNA data. The results suggested a limited introgression between AT and DU lineages. Taking into account the time of divergence between both lineages, selection and/or genetic incompatibility appeared necessary to explain the genetic structure observed and the ancient location of DU lineage restricted to this area.

Assessment of the spread of chestnut ink disease using remote sensing and geostatistical methods - L. Martins; J. Castro; W. Macedo; C. Marques; C. Abreu (European Journal of Plant Pathology, 2007)

Validation of a QTL for resistance to ascochyta blight linked to resistance to fusarium wilt race 5 in chickpea (Cicer arietinum L.) - M. Iruela; P. Castro; J. Rubio; J. I. Cubero; C. Jacinto; T. Millán; J. Gil (European Journal of Plant Pathology, 2007)

A linearization technique for multi-species transport problems - Neyva M. L. Romeiro; Rigoberto G. S. Castro; Sandra M. C. Malta; Luiz Landau (Transport in Porous Media, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Impacts of a change in vegetation description on simulated European summer present-day and future climates - E. Sánchez; M. A. Gaertner; C. Gallardo; E. Padorno; A. Arribas; M. Castro (Climate Dynamics, 2007)

The use of a climate-type classification for assessing climate change effects in Europe from an ensemble of nine regional climate models - M. de Castro; C. Gallardo; K. Jylha; H. Tuomenvirta (Climatic Change, 2007)

Different native arbuscular mycorrhizal fungi influence the coexistence of two plant species in a highly alkaline anthropogenic sediment - Rui S. Oliveira; Paula M. L. Castro; John C. Dodd; Miroslav Vosátka (Plant and Soil, 2006)

Optimization of Lipase-catalysed Synthesis of Butyl Butyrate Using a Factorial Design - J. C. Santos; H. F. de Castro (World Journal of Microbiology and Biotechnology, 2006)

Ticks (Acari: Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Matias P. J. Szabó; Marcelo B. Labruna; Karina C. Castagnolli; Marcos V. Garcia; Adriano Pinter; Viviane A. Veronez; Geórgia M. Magalhães; Márcio B. Castro; Alexandre Vogliotti (Experimental and Applied Acarology, 2006)

Coat protein gene sequence of a Mexican isolate of Sugarcane mosaic virus and its infectivity in maize and sugarcane plants - F. Espejel; D. Jeffers; J. C. Noa-Carrazana; S. Ruiz-Castro; L. Silva-Rosales (Archives of Virology, 2006)

Apoptotic effect of fludarabine is independent of expression of IAPs in B-cell chronic lymphocytic leukemia - K. L. Silva; D. V. Vasconcellos; E. D. de Paula Castro; A. M. Coelho; R. Linden; R. C. Maia (Apoptosis, 2006)

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

Interaction of stannous chloride leads to alteration in DNA, triphosphate nucleotides and isolated bases - José C. P. de Mattos; Claudia Lage; Flávio J. S. Dantas; Milton O. Moraes; Ana P. M. Nunes; Roberto J. A. C. Bezerra; Mauro V. Castro Faria; Alvaro C. Leitão; Adriano Caldeira-de-Araujo (Molecular and Cellular Biochemistry, 2005)

The expression of neurokinin-1 and preprotachykinin-1 in breast cancer cells depends on the relative degree of invasive and metastatic potential - Tammy A. Castro; Marion C. Cohen; Pranela Rameshwar (Clinical & Experimental Metastasis, 2005)

Studies on the diversity of arbuscular mycorrhizal fungi and the efficacy of two native isolates in a highly alkaline anthropogenic sediment - R. S. Oliveira; M. Vosátka; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2005)

Isolation in cell culture and detection by PCR‐based technology of IPNV‐like virus from leucocytes of carrier turbot, Scophthalmus maximus (L.) - J M Cutrín; C López‐Vázquez; J G Olveira; S Castro; C P Dopazo; I Bandín (Journal of Fish Diseases, 2005)
A non‐destructive procedure was utilized to determine the infectious pancreatic necrosis virus (IPNV) status of an apparently healthy turbot broodstock. Blood samples were used to detect IPNV by reverse transcriptase‐polymerase chain reaction (RT‐PCR), Southern blot hybridization and nested PCR. In addition, viral isolation from turbot leucocytes was performed. Around 22% of the fish were IPNV positive by RT‐PCR, and this increased to close to 60% when nested PCR was performed. The present report supports the use of blood samples for the detection of IPNV‐like viruses in brood fish. In addition, we demonstrate that it is possible to isolate the virus from the blood of carrier fish, as a non‐lethal detection method, although it is much less sensitive than RT‐PCR and nested PCR as a IPNV‐like strain was isolated from only five of the 15 blood sample pools assayed. The viral isolate was identified as type Dry Mills (genogroup I) by means of restriction fragment length polymorphisms and DNA sequencing.

Phytostructural characterization of several vegetation types in northern Portugal. II. The structural expressivity and the resistance of the vegetation - A. Crespí; S. Bernardos; A. Castro; C. P. Fernandes; F. Amich (Plant Biosystems, 2005)

Persistent Organochlorine Pesticide Levels in Breast Adipose Tissue in Women with Malignant and Benign Breast Tumors - S. M. Waliszewski; M. T. Bermudez; R. M. Infanzon; C. S. Silva; O. Carvajal; P. Trujillo; S. Gomez Arroyo; R. Villalobos Pietrini; V. A. Saldanña; G. Melo; S. Esquivel; F. Castro; et al. (Bulletin of Environmental Contamination and Toxicology, 2005)

Biosynthesis of Glycoproteins in the Human Pathogenic Fungus Sporothrix Schenckii: Synthesis of Dolichol Phosphate Mannose and Mannoproteins by Membrane-Bound and Solubilized Mannosyl Transferases - Estela Ruiz-Baca; Julio C. Villagómez-Castro; Carlos A. Leal-Morales; Myrna Sabanero-López; Arturo Flores-Carreón; Everardo López-Romero (Antonie van Leeuwenhoek, 2005)

The panmixia paradigm of eastern Pacific olive ridley turtles revised: consequences for their conservation and evolutionary biology - M. C. LÓPEZ‐CASTRO; A. ROCHA‐OLIVARES (Molecular Ecology, 2005)
Previous studies of the olive ridley Lepidochelys olivacea population structure in the tropical eastern Pacific have indicated the existence of a single panmictic population ranging from Costa Rica to Mexico. This information has been used to design specific management measures to conserve primary nesting beaches in Mexico. However, little is known about olive ridleys in the Baja California Peninsula, their northernmost reproductive limit, where recent observations have shown differences in nesting female behaviour and size of hatchlings relative to other continental rookeries. We used mtDNA control region sequences from 137 turtles from five continental and four peninsular nesting sites to determine whether such differences correspond to a genetic distinction of Baja California olive ridleys or to phenotypic plasticity associated with the extreme environmental nesting conditions of this region. We found that genetic diversity in peninsular turtles was significantly lower than in continental nesting colonies. Analysis of molecular variance revealed a significant population structure (Φ ST = 0.048, P = 0.006) with the inclusion of peninsular samples. Our results: (i) suggest that the observed phenotypic variation may be associated with genetic differentiation and reproductive isolation; (ii) support the recent colonization of the eastern Pacific by Lepidochelys ; ( iii) reveal genetic signatures of historical expansion and colonization events; and (iv) significantly challenge the notion of a single genetic and conservation unit of olive ridleys in the eastern Pacific. We conclude that conservation measures for olive ridleys in Mexico should be revised to grant peninsular beaches special attention.

Linezolid treatment of ventriculoperitoneal shunt infection without implant removal - P. Castro; A. Soriano; C. Escrich; G. Villalba; M. Sarasa; J. Mensa (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Geochemical evolution of groundwater in the Maneadero coastal aquifer during a dry year in Baja California, Mexico - L. Walter Daesslé; Edith C. Sánchez; Victor F. Camacho-Ibar; Leopoldo G. Mendoza-Espinosa; José D. Carriquiry; Victor A. Macias; Pedro G. Castro (Hydrogeology Journal, 2005)

Reduced phospholipid breakdown in Alzheimer’s brains: a 31P spectroscopy study - Orestes V. Forlenza; Priscilla Wacker; Paula V. Nunes; Juliana Yacubian; Claudio C. Castro; Maria C. G. Otaduy; Wagner F. Gattaz (Psychopharmacology, 2005)

Rotifer community structure in three shallow lakes: seasonal fluctuations and explanatory factors - Bruno B. Castro; Sara C. Antunes; Ruth Pereira; Amadeu M. V. M. Soares; Fernando Gonçalves (Hydrobiologia, 2005)

Structural study of synthetic mica–montmorillonite by means of 2D MAS NMR experiments - M. D. Alba; M. A. Castro; P. Chain; M. Naranjo; A. C. Perdigón (Physics and Chemistry of Minerals, 2005)

Stable isotope probing analysis of the influence of liming on root exudate utilization by soil microorganisms - J. Ignacio Rangel‐Castro; Ken Killham; Nick Ostle; Graeme W. Nicol; Ian C. Anderson; Charlie M. Scrimgeour; Phil Ineson; Andy Meharg; Jim I. Prosser (Environmental Microbiology, 2005)
Summary Rhizosphere microorganisms play an important role in soil carbon flow, through turnover of root exudates, but there is little information on which organisms are actively involved or on the influence of environmental conditions on active communities. In this study, a 13 CO 2 pulse labelling field experiment was performed in an upland grassland soil, followed by RNA‐stable isotope probing (SIP) analysis, to determine the effect of liming on the structure of the rhizosphere microbial community metabolizing root exudates. The lower limit of detection for SIP was determined in soil samples inoculated with a range of concentrations of 13 C‐labelled Pseudomonas fluorescens and was found to lie between 10 5 and 10 6 cells per gram of soil. The technique was capable of detecting microbial communities actively assimilating root exudates derived from recent photo‐assimilate in the field. Denaturing gradient gel electrophoresis (DGGE) profiles of bacteria, archaea and fungi derived from fractions obtained from caesium trifluoroacetate (CsTFA) density gradient ultracentrifugation indicated that active communities in limed soils were more complex than those in unlimed soils and were more active in utilization of recently exuded 13 C compounds. In limed soils, the majority of the community detected by standard RNA‐DGGE analysis appeared to be utilizing root exudates. In unlimed soils, DGGE profiles from 12 C and 13 C RNA fractions differed, suggesting that a proportion of the active community was utilizing other sources of organic carbon. These differences may reflect differences in the amount of root exudation under the different conditions.

Isolation of lymphocystis disease virus from sole, Solea senegalensis Kaup, and blackspot sea bream, Pagellus bogaraveo (Brünnich) - M C Alonso; I Cano; E Garcia‐Rosado; D Castro; J Lamas; J L Barja; J J Borrego (Journal of Fish Diseases, 2005)
Two viruses were isolated from cultured sole, Solea senegalensis , and wild blackspot sea bream, Pagellus bogaraveo , and preliminarily characterized as lymphocystis disease viruses (LCDVs). Viral isolates were characterized by morphological, biochemical and biophysical properties. In addition, the susceptibility of four fish cell lines was also tested. LCDV isolates developed cytopathic effects on the SAF‐1 cell line at 5 and 6 days post‐infection and reached titres of 10 6 TCID 50 mL −1 . The antigenic and structural protein analysis of the two new LCDV isolates showed identical profiles to that obtained for LCDV strain Leetown NFH (ATCC VR‐342), used as a reference viral strain, and for an LCDV isolate collected from gilt‐head sea bream, Sparus aurata , cultured in southern Spain. Molecular confirmation was performed by polymerase chain reaction. Specific primers for LCDV produced a 270‐bp DNA fragment, the expected size for LCDV.

Construction and characterization of a plant transformation-competent BIBAC library of the black Sigatoka-resistant banana Musa acuminata cv. Tuu Gia (AA) - E. Ortiz-Vázquez; D. Kaemmer; H-B. Zhang; J. Muth; M. Rodríguez-Mendiola; C. Arias-Castro; Andrew James (Theoretical and Applied Genetics, 2005)

Isolation and properties of a pure bacterial strain capable of fluorobenzene degradation as sole carbon and energy source - M. F. Carvalho; R. Ferreira Jorge; C. C. Pacheco; P. De Marco; P. M. L. Castro (Environmental Microbiology, 2005)
Summary A pure bacterial strain capable of aerobic biodegradation of fluorobenzene (FB) as the sole carbon and energy source was isolated by selective enrichment from sediments collected from a polluted site. 16S rRNA and fatty acid analyses support that strain F11 belongs to a novel genus within the α‐2 subgroup of the Proteobacteria, possibly within a new clade related to the order Rhizobiales . In batch cultures, growth of strain F11 on FB led to stoichiometric release of fluoride ion. Maximum experimental growth rate of 0.04 h −1 was obtained at FB concentration of 0.4 mM. Growth kinetics were described by the Luong model. An inhibitory effect with increasing FB concentrations was observed, with no growth occurring at concentrations higher than 3.9 mM. Strain F11 was shown to be able to use a range of other organic compounds, including other fluorinated compounds such as 2‐fluorobenzoate, 4‐fluorobenzoate and 4‐fluorophenol. To our knowledge, this is the first time biodegradation of FB, as the sole carbon and energy source, by a pure bacterium has been reported.

High prevalence of hepatitis B virus infection among tuberculosis patients with and without HIV in Rio de Janeiro, Brazil - C. A. Blal; S. R. L. Passos; C. Horn; I. Georg; M. G. Bonecini-Almeida; V. C. Rolla; L. Castro (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

First records of lice (Insecta: Phthiraptera) from wild southern pudu, Pudu puda (Mammalia: Artiodactyla: Cervidae) - Daniel González-Acuña; Dolores C. del Castro; Lucila Moreno; Eberhard Mey (European Journal of Wildlife Research, 2004)

Parameiosis inAspergillus nidulans in response to doxorubicin - T. C. A. Becker; M. A. A. de Castro-Prado (Folia Microbiologica, 2004)

High CO2 Levels in Boreholes at El Teide Volcano Complex (Tenerife, Canary Islands): Implications for Volcanic Activity Monitoring - V. Soler; J. A. Castro-Almazán; R. T. Viñas; A. Eff-Darwich; S. Sánchez-Moral; C. Hillaire-Marcel; I. Farrujia; J. Coello; J. de la Nuez; M. C. Martín; M. L. Quesada; E. Santana (Pure and Applied Geophysics, 2004)

Structural localization of Al 3+ ions in aluminosilicates: application of heteronuclear chemical shift correlation to 2:1 phyllosilicates - M. D. Alba; M. A. Castro; M. Naranjo; A. C. Perdign (Physics and Chemistry of Minerals, 2004)

An antecedent of the MHC-linked genomic region in amphioxus - L. Filipe C. Castro; Rebecca F. Furlong; Peter W. H. Holland (Immunogenetics, 2004)

On the Composition of Airborne Particles Influenced by Emissions of the Volcano Popocatépetl in Mexico - J. C. Jiménez; G. B. Raga; D. Baumgardner; T. Castro; I. Rosas; A. Báez; O. Morton (Natural Hazards, 2004)

Gynogenesis Assessment Using Microsatellite Genetic Markers in Turbot ( Scophthalmus maximus ) - J. Castro; C. Bouza; L. Snchez; R. M. Cal; F. Piferrer; P. Martnez (Marine Biotechnology, 2003)

Role of nitric oxide in thermoregulation during septic shock: involvement of vasopressin - Alexandre Giusti-Paiva; Luiz G. S. Branco; Margareth de Castro; José Antunes-Rodrigues; Evelin C. Carnio (Pflügers Archiv - European Journal of Physiology, 2003)

Assessment of regional seasonal rainfall predictability using the CPTEC/COLA atmospheric GCM - J. A. Marengo; I. F. A. Cavalcanti; P. Satyamurty; I. Trosnikov; C. A. Nobre; J. P. Bonatti; H. Camargo; G. Sampaio; M. B. Sanches; A. O. Manzi; C. A. C. Castro; C. D'Almeida; et al. (Climate Dynamics, 2003)

Mapping and pyramiding of qualitative and quantitative resistance to stripe rust in barley - A. J. Castro; F. Capettini; A. E. Corey; T. Filichkina; P. M. Hayes; A. Kleinhofs; D. Kudrna; K. Richardson; S. Sandoval-Islas; C. Rossi; H. Vivar (Theoretical and Applied Genetics, 2003)

Nesting characteristics of the olive ridley turtle ( Lepidochelys olivacea ) in Cabo Pulmo, southern Baja California - M. C. Lpez-Castro; R. Carmona; W. J. Nichols (Marine Biology, 2003)

Sensitivity of the Iberian Peninsula climate to a land degradation - A. Arribas; C. Gallardo; M. Gaertner; M. Castro (Climate Dynamics, 2003)

Effects of extremely hot days on people older than 65 years in Seville (Spain) from 1986 to 1997 - Díaz J.; García R.; F. Velázquez de Castro; Hernández E.; López C.; Otero A. (International Journal of Biometeorology, 2002)

Microbiological and Sanitary Quality of Recreational Seawaters of Southern Portugal - Lidia P. C. Dionisio; Esther Garcia-Rosado; Lourdes Lopez-Cortes; Dolores Castro; Juan J. Borrego (Water, Air, & Soil Pollution, 2002)

Morphophysiological studies on alligator gar (Atractosteus spatula) larval development as a basis for their culture and repopulation of their natural habitats - R. Mendoza; C. Aguilera; G. Rodríguez; M. González; R. Castro (Reviews in Fish Biology and Fisheries, 2002)

Enrichment of microbial cultures able to degrade1,3-dichloro-2-propanol: A comparison between batch and continuous methods - Filipe Bastos; José Bessa; Catarina C. Pacheco; Paolo De Marco; Paula M.L. Castro; Manuel Silva; Ruben Ferreira Jorge (Biodegradation, 2002)

Numerical Analysis of Space–Time Finite Element Formulations for Miscible Displacements - Rigoberto G. Sanabria Castro; Sandra M. C. Malta; Abimael F. D. Loula; Luiz Landau (Computational Geosciences, 2001)

Hydrogenated fish fat for grazing dairy cows in summer - M. R. Gallardo; S. E. Valtorta; P. E. Leva; H. C. Castro; J. A. Maiztegui (International Journal of Biometeorology, 2001)

The Basques according to polymorphic Alu insertions - M. de Pancorbo; López-Martínez M.; Martínez-Bouzas C.; Castro A.; Fernández-Fernández I.; G. Antúnez de Mayolo; A. Antúnez de Mayolo; P. Antúnez de Mayolo; Rowold D.; Herrera R. (Human Genetics, 2001)

The Itacolomis: large and unexplored reefs at the arrival point of the first Europeans in Brazil - C. B. Castro; B. Segal (Coral Reefs, 2001)

The impact of deforestation on the hydrological cycle in the western Mediterranean: an ensemble study with two regional climate models - M. A. Gaertner; O. B. Christensen; J. A. Prego; J. Polcher; C. Gallardo; M. Castro (Climate Dynamics, 2001)

Allozymic evidence of parapatric differentiation of brown trout ( Salmo trutta L.) within an Atlantic river basin of the Iberian Peninsula - C. Bouza; J. Castro; L. Sánchez; P. Martínez (Molecular Ecology, 2001)
The genetic variation of brown trout from Duero, one of the main Atlantic Iberian river basins, was assessed at 34 enzymatic loci in 62 native populations. A strong intrabasin differentiation was detected ( G ST = 0.46; range D : 0–0.066), mainly attributable to the existence of two divergent groups of populations within Duero: southern and northern groups. This divergence was mainly a consequence of the unequal distribution of *75 and *100 alleles at s MDH ‐B1,2* isoloci, which were correlated with substantial differences in genetic diversity among regions. The Lower Course region (nearly fixed for the *100 allele) and Pisuerga River (nearly fixed for the *75 allele) showed lower heterozygosities ( H ≈ 0.8%) in contrast with adjacent areas, which evidenced intermediate frequencies for both alleles and higher heterozygosities ( H : 2.2–3.1%). Vicariance appeared as the more probable explanation for the significant positive correlation detected between genetic and geographical distances in Duero Basin. Genetic relationships with adjacent Iberian drainages indicate a close similarity between the southern group and Cantabric trout, whereas the northern group constitutes an ancient form from this basin. This study confirmed complex genetic relationships in brown trout from northwest Iberia, reasserting the existence of clines at several loci and for genetic diversity. The interaction between Cantabric and Duero trout , as well as the location of the limit of the anadromous form around the 42° N parallel, are both required to understand the genetic characteristics of brown trout from this area.

Expression of the Major Heat Shock Proteins DnaK and GroEL in Streptococcus pyogenes : A Comparison to Enterococcus faecalis and Staphylococcus aureus - Marinella S. Laport; Angela C.D. de Castro; Adriana Villardo; Jose Abelardo C. Lemos; Maria do Carmo F. Bastos; Marcia Giambiagi-deMarval (Current Microbiology, 2001)

The mycorrhizal status of Phragmites australis in several polluted soils and sediments of an industrialised region of Northern Portugal - R.S. Oliveira; J. C. Dodd; P. M. L. Castro (Mycorrhiza, 2001)

Lowest effective and optimum poultry manure dose for reclaiming burnt soils: pot experiments - A. Castro; S. J. González-Prieto; M. C. Villar; T. Carballas (Biology and Fertility of Soils, 2000)

Nosocomial Spread of Hepatitis B Virus in Two Hemodialysis Units, Investigated by Restriction Fragment Length Polymorphism Analysis - L. De Castro; N. M. Araujo; R. R. Sabino; F. Alvarenga; C. F. T. Yoshida; S. A. Gomes (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Behavioral and demographic changes following the loss of the breeding female in cooperatively breeding marmosets - C. Lazaro-Perea; C. S. S. Castro; R. Harrison; A. Araujo; M. F. Arruda; C. T. Snowdon (Behavioral Ecology and Sociobiology, 2000)

An artificial grasping evaluation system for the paralysed hand - M. C. Ferrari de Castro; A. Cliquet (Medical & Biological Engineering & Computing, 2000)

Coat protein sequence comparisons of three Mexican isolates of papaya ringspot virus with other geographical isolates reveal a close relationship to American and Australian isolates - L. Silva-Rosales; N. Becerra-Leor; S. Ruiz-Castro; D. Téliz-Ortiz; J. C. Noa-Carrazana (Archives of Virology, 2000)

Reef coral reproduction in the Abrolhos Reef Complex, Brazil: the endemic genus Mussismilia - D. O. Pires; C. B. Castro; C. C. Ratto (Marine Biology, 1999)

Genetic structure of brown trout, Salmo trutta L., at the southern limit of the distribution range of the anadromous form - C. Bouza; J. Arias; J. Castro; L. Sánchez; P. Martínez (Molecular Ecology, 1999)
Genetic variation at 33 protein loci was investigated in 41 wild brown trout populations from four river basins in Galicia (northwest Spain) to analyse the amount and distribution of genetic diversity in a marginal area, located in the distribution limit of the anadromous form of this species. The genetic diversity detected within populations ( H between 0 and 6%) lies within the range quoted for this species in previous reports. The Miño, the most southern river basin analysed, showed a significantly lower genetic diversity and the highest genetic differentiation among the river basins studied. The hierarchical gene diversity analysis showed high population differentiation in a restricted area ( G ST = 27%), mostly due to differences among populations within basins ( G SC = 22%). The reduction of G ST observed when the isolated samples were excluded from the analysis ( G ST = 17%) showed the importance of habitat fragmentation on the heterogeneity detected. Gene flow among populations was comparatively evaluated by three indirect methods, which in general revealed low figures of absolute number of migrants per generation, slightly higher than 1. The gene flow among basins reflected a positive relationship with geographical distance. This trend was confirmed by the significant correlation observed between geographical and genetic distances, including all population pairs, which suggests a component of isolation by distance in brown trout genetic structure. Nevertheless, the nonsignificant intrabasin correlation demonstrates the complexity of genetic relationships among populations in this species. The model of genetic structure in brown trout is discussed in the light of the results obtained.

Activity, feeding behaviour and diet of Ogcocephalus vespertilio in southern west Atlantic - F. Z. Gibran; R. M. C. Castro (Journal of Fish Biology, 1999)
The Brazilian batfish Ogcocephalus vespertilio is a nocturnal and early morning predator on bottom invertebrates, staying stationary and hidden in rock holes, crevices or among bottom rocks during the day. While active, it searches for prey walking along the bottom with the help of its specialized paired fins, with the illicium protracted and oscillating or exploring the substrate. The prey are either snapped up from the bottom, after visual detection, or dug out with use of the mouth and rostrum. It feeds on crustaceans (hermit crabs, true crabs, shrimps, amphipods, porcelain crabs, isopods and mysid shrimps), molluscs (snails, sea slugs and clams), polychaete worms (mostly Errantia) and echinoderms (sea urchins and brittle stars).

Obtainment of a carbon-13-, nitrogen-15-labelled burnt soil - S. J. González-Prieto; A. Cabaneiro; A. Castro; M. C. Villar; A. Martín; T. Carballas (Biology and Fertility of Soils, 1999)

Age constraints to the relationships between magmatism, metamorphism and tectonism in the Aracena metamorphic belt, southern Spain - A. Castro; C. Fernández; H. El-Hmidi; M. El-Biad; M. Díaz; J. de la Rosa; F. Stuart (International Journal of Earth Sciences, 1999)

β-Tubulin accumulation and DNA synthesis are sequentially resumed in embryo organs of cucumber (Cucumis sativus L.) seeds during germination - Hai -Chun Jing; André A. M. van Lammeren; Renato D. de Castro; Raoul J. Bino; Henk W. M. Hilhorst; Steven P. C. Groot (Protoplasma, 1999)

Stem anatomy and relative growth rate in seedlings of a wide range of woody plant species and types - P. Castro-Díez; J. P. Puyravaud; J. H. C. Cornelissen; P. Villar-Salvador (Oecologia, 1998)

Use of a microquantity enzyme immunoassay in a large-scale study of measles, mumps, and rubella immunity in Italy - F. Condorelli; A. Stivala; R. Gallo; A. Marino; C. M. Battaglini; A. Messina; G. Russo; A. Castro; G. Scalia (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Numerical analyses of distributions of Iberian and Balearic endemic monocotyledons - J. C. Moreno Saiz; I Castro Parga; H Sainz Ollero (Journal of Biogeography, 1998)
Chorological information concerning 182 taxa of monocotyledons endemic to the Iberian Peninsula and Balearic Islands was compiled and related to the 100×100 km, 50×50 km and 10×10 km UTM grids. Distributions were analysed using multivariate methods (two‐way indicator species analysis and detrended correspondence analysis) for each scale. Comparison of results allows recognition of several floristic elements and sectors (i.e. Balearic, Murcian‐Almerian, south western) common to all three scales, whereas other regions are assigned to different sectors depending on the grid size considered. As a consequence of the increase in detail, characteristics such as number of sectors, the outline of boundaries and continuity or fragmentation of the areas also change. These factors are discussed.

Detection and preliminary characterization of extracellular proteolytic activities of the haloalkaliphilic archaeon Natronococcus occultus - C. A. Studdert; Rosana E. De Castro; Karina Herrera Seitz; Jorge J. Sánchez (Archives of Microbiology, 1997)

Validation of present-day regional climate simulations over Europe: LAM simulations with observed boundary conditions - J. H. Christensen; B. Machenhauer; R. G. Jones; C. Schär; P. M. Ruti; M. Castro; G. Visconti (Climate Dynamics, 1997)

An objective method for partitioning dendrograms based on entropy parameters - M. A. Casado; L. Ramírez-Sanz; I. Castro; J. M. de Miguel; C. L. de Pablo (Plant Ecology, 1997)

Follow-up of mercury levels in fish, human hair and urine in the Madeira and Tapajós basins, Amazon, Brazil - O. Malm; J. R. D. Guimarães; M. B. Castro; W. R. Bastos; J. P. Viana; F. J. P. Branches; E. G. Silveira; W. C. Pfeiffer (Water, Air, & Soil Pollution, 1997)

Simulation of a long-lived meso-? scale convective system over the mediterranean coast of Spain. Part II: Sensitivity to external forcings - C. Fernndez; M. A. Gaertner; C. Gallardo; M. Castro (Meteorology and Atmospheric Physics, 1997)

Identification and partial characterization of three chitinase forms in Entamoeba invadens with emphasis on their inhibition by allosamidin - Julio C. Villagmez-Castro; Everardo Lpez-Romero (Antonie van Leeuwenhoek, 1996)

Biosynthesis of cyclic ?-(1,2)-glucans in Rhizobium leguminosarum biovars viciae, phaseoli and trifolii - Olga A. Castro; A. Zorreguieta; C. Semino; Luis Ielpi (Archives of Microbiology, 1995)

Direct detection of the porcine reproductive and respiratory syndrome (PRRS) virus by reverse polymerase chain reaction (RT-PCR) - P. Suárez; R. Zardoya; C. Prieto; A. Solana; E. Tabarés; J. M. Bautista; J. M. Castro (Archives of Virology, 1994)

A diagnostic method to detect alcelaphine herpesvirus-1 of malignant catarrhal fever using the polymerase chain reaction - D. Hsu; L. M. Shih; A. E. Castro; Y. C. Zee (Archives of Virology, 1990)

Late preventive effects against carbon tetrachloride-induced liver necrosis of the calcium chelating agent calcion - E. C. de Ferreyra; M. C. Villarruel; A. S. Bernacchi; G. Fernández; O. M. de Fenos; J. A. Castro (Archives of Toxicology, 1989)

Comparison of genomes of malignant catarrhal fever-associated herpesviruses by restriction endonuclease analysis - L. M. Shih; Y. C. Zee; A. E. Castro (Archives of Virology, 1989)

Cholinesterase activities in developing amphibian embryos following exposure to the insecticides dieldrin and malathion - Monica C. de Llamas; Adriana C. de Castro; Ana M. Pechen de D'Angelo (Archives of Environmental Contamination and Toxicology, 1985)

African swine fever virus - R. C. Wardley; C. de M. Andrade; D. N. Black; F. L. de Castro Portugal; L. Enjuanes; W. R. Hess; C. Mebus; A. Ordas; D. Rutili; J. Sanchez Vizcaino; J. D. Vigario; P. J. Wilkinson; et al. (Archives of Virology, 1983)

The effect of nitrogen fertilization on the composition of the free amino acid pool of poato tubers - J. E. Hoff; C. M. Jones; G. E. Wilcox; Marlene D. Castro (American Journal of Potato Research, 1971)

Developmental genetics of the alcohol dehydrogenase locus of the Japanese quail - S. Ohno; L. Christian; C. Stenius; E. Castro-Sierra; J. Muramoto (Biochemical Genetics, 1969)